Generation of miR-141/200c conditional knockout mice from knockout-first, reporter-tagged parent and functional validation of the floxed allele - Sanjeev Kumar Yadav; Rashmi Srivastava; Mary-Katherine Cormier; Katie Lowther; Siu-Pok Yee; Rajkumar Verma (Mammalian Genome, 2026)

Dual facets of copper in the malignant transformation of oral submucous fibrosis: A narrative review - Gomathi Priyanka S; Divya Bose; Dineshkumar Thayalan; Nagarathinam AE; Rajkumar Krishnan; Rameshkumar A (Molecular Biology Reports, 2026)

Emerging RNA biomarkers for diabetes: Mechanistic insights and clinical relevance - Venkatesan Karthick; Muthineni Haneesh; Sharan Kumar Karthikeyan; Singamoorthy Amalraj; Rajkumar Thamarai; Abdul Abduz Zahir (Molecular Biology Reports, 2026)

Developmental stage-specific expression of the phytase1 gene and its association with phytase activity in maize kernel - Botta Thandava Ganesh; Ashvinkumar Katral; Vignesh Muthusamy; Rajkumar U. Zunjare; Parameshwaran Mathavaraj; Amitkumar Dilipbhai Kyada; Gaurav Sharma; Govinda Rai Sarma; Jayanthi Madhavan; Chirravuri Naga Neeraja; Firoz Hossain (Molecular Biology Reports, 2026)

Tissue distribution of Orientia tsutsugamushi in rodents: a molecular and immune diagnostic approach - Venkatesan Rajkumar; Gani Taju; Seepoo Abdul Majeed; Paulraj Philip Samuel; Renu Govindarajan; Subbiah Gowri Sankar; Sreedhar Kuttiatt Vijesh; Mohamed Jaffer Abdul Wazith; Kumarasamy Kanimozhi; Azeez Sait Sahul Hameed (Molecular Biology Reports, 2026)

Evaluating the future of climate modeling: A critical review of CMIP6 applications and their role in climate risk and impact assessments - Rajkumar Guria; Manoranjan Mishra; Richarde Marques da Silva; Celso Augusto Guimarães Santos; Biswaranjan Baraj (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Corrigendum to “Adulteration in paneer (Indian cottage cheese): A review of practices, detection, and public health implications – a critical analysis”[Food Control 187 (2026) 112163] - A. Surendra Babu; P. Sankarganesh; V. Parthasarathy; K. Rajkumar; Meenatai Gunderao Kamble (Food Control, 2026)

Retraction notice to “Systematic green synthesis of silver oxide nanoparticles for antimicrobial activity” [Environ. Res. 202 (2021) 111627] - M. Mani; R. Harikrishnan; P. Purushothaman; S. Pavithra; P. Rajkumar; S. Kumaresan; Dunia A. Al Farraj; Mohamed Soliman Elshikh; Balamuralikrishnan Balasubramanian; K. Kaviyarasu (Environmental Research, 2026)

Deconstructing Microplastic Pollution in Terrestrial and Freshwater Environs: Holistic Assessment of Source Apportionment, Polymer-driven Ecological Hazard, and Human Exposure - Kiruthika Mohan; Vignesh Rajkumar Lakshmanan (Water, Air, & Soil Pollution, 2026)

Curcumin nanoformulations for modulating neuroinflammation and oxidative stress in Alzheimer’s disease: blood–brain barrier transport, formulation strategies and therapeutic applications - M. Yasmin Begum; Manickam Rajkumar; Prabha Govindaraj; Nadarajan Prathap; Parappurath Narayanan Sudha; Mona Al Hamod; Hamoud Alotaibi; Deenathayalan Uvarajan (Inflammopharmacology, 2026)

Antarctic sea ice concentration and extent from SARAL/AltiKa: validation, seasonal performance and long-term trend consistency - Chungkham Thombson; Rajkumar Kamaljit Singh; Sandip Rashmikant Oja; Purvee Nisarg Joshi; Sushil Kumar Singh; Mamata Maisnam (International Journal of Remote Sensing, 2026)

Adulteration in paneer (Indian cottage cheese): A review of practices, detection, and public health implications – a critical analysis - A. Surendra Babu; P. Sankarganesh; V. Parthasarathy; K. Rajkumar; Meenatai Gunderao Kamble (Food Control, 2026)

Introgression of teosinte branched1 gene from wild-progenitor enhances prolificacy in subtropically-adapted maize - Firoz Hossain; Rajkumar Uttamrao Zunjare; Rashmi Chhabra; Irum Gul; Amitkumar D. Kyada; Elizabeth Mathew; Ravindra K. Kasana; Nitish R. Prakash; Vinay Bhatt; Sunil Neelam; Vignesh Muthusamy (Planta, 2026)

Unravelling Novel Polymorphism and Developing a Breeder-Friendly Functional Marker in Dwarf8 Gene Associated with Dwarfism in Zea mays - Govinda Rai Sarma; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Amitkumar D. Kyada; Vinay Bhatt; Botta Thandava Ganesh; Vinay Rojaria; Viswanathan Chinnusamy; Firoz Hossain (Journal of Plant Growth Regulation, 2026)

A high-resolution remote sensing-based composite index for monitoring agricultural drought in India - Alka Rani; Vinay Kumar Sehgal; Rajkumar Dhakar; Ravinder Kaur; Rabi Narayan Sahoo; Vijay Kumar Prajapati; Christopher Neal; Michael Hayes; Mark Svoboda; Tsegaye Tadesse; Brian Wardlow; John Swigwart (Environment, Development and Sustainability, 2026)

Taxonomy of Euonymus vagans Wall. and nomenclature note on Euonymus vagans Wall. subsp. macrophyllus Kanjilal, P. C. Kanjilal, Das and Purkayastha (Celastraceae: Celastroideae) - Ajay Mondal; Pradhyumnan Madappallam Ramakrishnan; Chidambaram Murugan; S. Dominic Rajkumar (Vegetos, 2026)

Integrated experimental and machine learning framework for optimizing dual fuel combustion of bio-oil yielded from hydrothermal liquefaction of coconut shell wastes and diesel/biodiesel in a diesel engine - C. Parthasarathy; Sundararajan Rajkumar (Process Safety and Environmental Protection, 2026)

Engineering oxovanadium(IV)-gold nanorod nanoconjugates (VO@AuNRs) for enhanced mitochondria-targeted photodynamic cancer therapy in red-light - Gobinda Bag; Souma Ghosh; Ushasri Chilakamarthi; Rajkumar Banerjee; Th. David Singh; Mithun Roy (Journal of Photochemistry and Photobiology B: Biology, 2026)

Phytofabrication of Chitosan–MgO nanocomposites: Evaluation of their antioxidant, antibacterial, anticancer, and zebrafish embryo biocompatibility properties - M. Yasmin Begum; Manickam Rajkumar; Prabha Govindaraj; Krishnan Meenambigai; Mona Alhamod; Hamoud Alotaibi (Journal of Photochemistry and Photobiology B: Biology, 2026)

Three decades of livestock-relevant heat stress intensification along the Indian West Coast: a gridded THI trend and temperature-humidity contribution analysis - Subhradip Bhattacharjee; R. Solomon Rajkumar; V. Paramesha; Parveen Kumar; Basavareddy; Amitava Panja; Subham Singha; Dipak Dey; Prasanna Pal; Rakesh Kumar; Dinesh Kumar (Theoretical and Applied Climatology, 2026)

Development of subtropically-adapted indeterminate gametophyte1 (ig1) gene-based paternal haploid inducer lines in maize through molecular breeding - Amitkumar D. Kyada; Vignesh Muthusamy; Rashmi Chhabra; Botta T. Ganesh; Gulab Chand; Gaurav Sharma; Hriipulou Duo; Govinda R. Sarma; Ravindra K. Kasana; Jayanthi Madhavan; Rajkumar U. Zunjare; Firoz Hossain (Planta, 2026)

Research trends and bibliometric insights into the Sundarbans mangrove forest: bridging knowledge gaps and shaping future directions - Suman Paul; Manoranjan Mishra; Rajkumar Guria; Richarde Marques da Silva; Celso Augusto Guimarães Santos (Journal of Coastal Conservation, 2026)

Development of a novel rabeprazole modified release formulation to reduce the dosing frequency: A trial and triumph with physiologically based biopharmaceutics modeling - Harika Maddukuri; Rajkumar Boddu; Sangmesh Mallikarjun Chaudhari; Anup Avijit Choudhury; Veena Kambam; Sohel Mohammed Khan; Venkat Ramana Naidu; Sanjay Kumar Singh; Anuj Kumar Saini; Sivacharan Kollipara (Journal of Pharmacokinetics and Pharmacodynamics, 2026)

Promoting sustainable pest management through digital decision support tools: Insights from India - Justice A. Tambo; Malvika Chaudhary; Idah Mugambi; Madhu Manjari; Mahesh H. Munireddappa; Kritika Khanna; J.V. Mohan Rao; M. Bheemanna; Prabhuraj Aralimarad; Rajkumar Ramasamy (Agricultural Systems, 2026)

Comparative microbiome profiling of plant- and animal-derived traditional fermented foods from Mizoram, India using full-length 16S rRNA sequencing - Jacinta Lalhmunsangi; Rajkumar Sudharsan; Gracy Laldinmawii; Rebecca Lalngaihzuali; Madhuchhanda Das; Samaresh Das; Subhankar Mukherjee; Soumyadeb Bhattacharyya; T. Ramamurthy; Parimal Roychoudhury; Fatema Akter; Ashis Mukhopadhyay; et al. (Antonie van Leeuwenhoek, 2026)

Development of in vitro germination and cryopreservation protocols of pollen in wild Lathyrus species to overcome longevity and asynchronous flowering constraints - Rinky Resma Panda; Padmavati G. Gore; Aishmita Gantait; Esha Singh; Mahesh Rao; S. Rajkumar; Shiv Kumar; Kuldeep Tripathi; Sandhya Gupta (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Stem Cells-Based Strategies for Skin Regeneration and Repair: Current Approaches, Pre-Clinical, and Clinical Evidence - Keerthiraj Kalmantidoddi Shivaji; Balamuralidhara Veeranna; Soundarya Raju; Baviya Priyadharshini Rajkumar; Sagar Guruswamy (Current Stem Cell Reports, 2026)

Unravelling the temporal accumulation of provitamin-A carotenoids and tocopherols during kernel development in biofortified sweet corn hybrids - Hema S. Chauhan; Vignesh Muthusamy; Tuhin Rashmi; Brijesh K. Mehta; Subhra J. Mishra; Abhijit K. Das; Rajkumar U. Zunjare; Ashok K. Singh; Hari S. Gupta; Firoz Hossain (Journal of Plant Biochemistry and Biotechnology, 2026)

Distinct epigenetic ageing patterns are associated with heterogeneity in kidney function decline in type 2 diabetes - Resham Lal Gurung; Hao Wu; Huili Zheng; Sylvia Liu; Jia Le Ivan Tan; Jian-Jun Liu; Jian Hua Tay; Kar Seng Sim; Jian Jun Liu; Rajkumar Dorajoo; Su Chi Lim (GeroScience, 2026)

Development and evaluation of sub-tropically adapted sweet corn hybrids for dual-purpose utilization with emphasis on yield and fodder quality traits - Puja Mandal; Babu Chakrapani; Vignesh Muthusamy; Brijesh Kumar Mehta; Parameshwaran Mathavaraj; Rashmi Chhabra; Senthil Natesan; Chandrakumar Kalichamy; Kumari Vinodhana Natarajan; Rajkumar Uttamrao Zunjare; Javaji Chandra Sekhar; Ravikesavan Rajasekaran; et al. (The Nucleus, 2026)

Toxicological profiling of 1-octen-3-ol against the rice weevil, Sitophilus oryzae (L.) - Anandhakumar Renuka; Vallavan Rajkumar; Kavumkunnel Rasack Sajinu; Sonaimuthu Nivithasri; Chinnappan Gunasekaran (International Journal of Tropical Insect Science, 2026)

Functional characterization of cultivable endophytic bacteria from wild cotton Gossypium aridum and exploration of potent strain as seed bio-priming agent - Preeti R. Parmar; B.K. Rajkumar; Nitin Varshney; Diya Patel (Biocatalysis and Agricultural Biotechnology, 2026)

Temperature stress induced anatomical and histological alterations in reproductive organs of Capsicum annuum L - Sikha Manoharan; Arpita Srivastava; Manisha Mangal; Bhoopal Singh Tomar; Subramani Rajkumar; Hari Krishna; Anjali Anand; Lakshman Prasad; Hemlata Bharti; Sethu Lakshmi Suseelan (Protoplasma, 2026)

Integrated in silico docking, ADMET, and network pharmacology evaluation of Althaea officinalis L. phytocompounds targeting Park2 for the management of Parkinson’s disease - M. Heshetha; Muthineni Haneesh; Venkatesan Karthick; Rajkumar Thamarai; Singamoorthy Amalraj (Inflammopharmacology, 2026)

New distributional records of grasses (Poaceae) from Maharashtra, India - Vaghmare Jalander; Jetti Swamy; Naziroddin Fakaroddin Shaikh; Vishal Rajkumar Marathe (Vegetos, 2026)

Polymorphism analysis and development of PCR-based haplotype-linked markers for the NAC78 gene associated with enhanced kernel iron content in subtropical maize - Rajesh Kumar; Parameshwaran Mathavaraj; Satyam Raina; Mamta Sharma; Ashvinkumar Katral; Anurag Awasthi; Vinay Bhatt; Debasis Golui; Rajkumar Uttamrao Zunjare; Firoz Hossain; Vignesh Muthusamy (The Nucleus, 2026)

Large-scale distortion of the dayside magnetopause under radial interplanetary magnetic field - Jin Guo; San Lu; Quanming Lu; Boyi Wang; Shimou Wang; Junyi Ren; Jiuqi Ma; Xinliang Gao; Rajkumar Hajra; Rongsheng Wang (Science Bulletin, 2026)

First report on whole genome sequencing of Chaetomium strumarium BRFC4 and its antagonistic activity against Fusarium wilt of banana - Arutselvan Vanitha; Rajkumar Sudharsan; Chinnan Kannan; Annadurai Praveen; Pulapet Sowmya; Jaganathan Gowrishankar; Markkandan Kesavan; Mathiyalagan Ramya; Rajapandiyan Krishnamoorthy; Mohammad A. Alshuniaber; Magdi A. Osman; Mansour K. Gatasheh (Phytochemistry, 2026)

Integrating Machine Learning and Geospatial Analysis for Flood Hazard, Vulnerability, and Risk Assessment in Odisha, India - Manoranjan Mishra; Rajkumar Guria; Richarde Marques da Silva; Somanath Sethi; Minati Mishra; Mansour Almazroui; Rabin Chakrabortty; Celso Augusto Guimarães Santos (Water Resources Management, 2026)

Integrated spatio-temporal analysis of historical and future projections precipitation variability alongside agricultural production trends in the North Western Himalayan Region - Neha; Sanjeev Dwivedi; V. Kumar; Rajkumar Guria; Manoranjan Mishra; S. K. Srivastava (Theoretical and Applied Climatology, 2026)

CRISP-PTG-Assembler Ver. 1.0: a primer design tool for polycistronic tRNA-gRNA (PTG) assembly for Cas9-based multiplex genome editing in plants - Soham Ray; Joshitha Vijayan; S. Vanchinathan; Rajkumar Dhakar; Nazima Nasrullah; Shivani Nagar; Tushar Kanti Dutta; Viswanthan Chinnusamy (Planta, 2026)

Exploring wild rices for photosynthetic efficiency improvement in rice - Kanchan Jumrani; Dipti Ranjan Pani; Mridul Chakraborti; Mirza Jaynul Baig; Viswanathan Chinnusamy; Palanisamy Veeraya; Ritu Tiwari; Dhammaprakash P. Wankhede; Rajkumar Subramani; Kanakasabapathi Pradheep; Parimalan Rangan (Physiology and Molecular Biology of Plants, 2026)
Photosynthesis is a key determinant for plant productivity, understanding its genetic basis will aid its improvement. The photosynthesis trait is primarily measured in terms of carbon and light utilization, using gas exchange and chlorophyll fluorescence methods. We report in this study, the extent of variability for photosynthetic trait in wild rice relatives, comprising a total of 26 taxa (22 wild species), using an infrared gas analyzer. The scale of measures used were, PN (net photosynthetic rate), E (transpiration), gs (stomatal conductance), Ci (intercellular CO 2 ), Ci/Ca (ratio of intercellular to ambient CO 2 ), WUE (water use efficiency), CE (carboxylation efficiency), Fv′/Fm′ (ratio of variable to maximum fluorescence, photosynthesis efficiency), qP (photochemical quenching), qN (non-photochemical quenching), ΦPSII (quantum yield of photosystemII), and ETR (electron transport rate). These were subjected to variability (ANOVA and PCA) and association (correlation matrices and path analysis) studies. The maximum PN was observed in Oryza australiensis , followed by Oryza officinalis and Oryza barthii . Maximum qP was observed in Oryza latifolia which was at par with O . australiensis , and Oryza alta . Highest CE was observed in O . australiensis . The CE values for O . barthii , Oryza grandiglumis and O. latifolia were at par with O . australiensis . Transcriptomic analysis for flag leaf between APO, the high efficient photosynthetic genotype with indica rice cultivar BAM4234 revealed key candidate genes underlying photosynthesis traits. These findings underscore the value of wild species and their alleles in expanding the photosynthetic capacity of rice potentially using classical breeding approaches.

Synergistic Application of Bone-derived Biochar and Plant Growth-promoting Rhizobacteria for Enhanced Chromium Phytoremediation Using Pearl Millet - Minisha Udhayakumar; Mohammed Safvan Pazhedath; Rashi Jeru; Muhammad Azeem; Rajkumar Mani; Ayyappa Das Madhubala Parameswaran; Thumadath Palayullaparambil Ajeesh Krishna; Parimala Gnana Soundari Arockiam Jeyasundar; Stanislaus Antony Ceasar (Journal of Soil Science and Plant Nutrition, 2026)

Multi-organ histological assessment of Agrococcus sp. RKDAS_1 reveals tissue-level biocompatibility in Oreochromis niloticus - Venkatesan Karthick; Arun Venkatesh; Singamoorthy Amalraj; Sulochana Sonti; Rajkumar Thamarai; Rajkumar Prabhakaran (Journal of Molecular Histology, 2026)

WHO-2021 compliance and dust-day screening framework for small-island air quality management: development and application in Trinidad & Tobago - Treina Dinoo Ramlochan; Koffka Khan; Wayne Rajkumar; Shanta Ramnath; Steven Rampersad; Winston Elibox (Air Quality, Atmosphere & Health, 2026)

Phytochemical and Molecular Insights Into the Antiviral Efficacy of Juglans regia (Walnut) Leaf Ethanolic Extract and Cydonia oblonga (Quince) Fruit Acetone Extract in Litopenaeus vannamei Infected With White Spot Syndrome Virus ( WSSV ) - Betty Mary Divya; Feroz Ahmad Shah; Azeez Sait Sahul Hameed; Venkatesan Rajkumar; Qadiri Syed Shariq Nazir; Asimi Oyas Ahmed; Gani Taju; Seepoo Abdul Majeed; Sofi Nazir Ahmad; Mohd Ishrat (Journal of Fish Diseases, 2026)
White Spot Syndrome Virus (WSSV) is known to cause significant mortality in farmed shrimp, including black tiger shrimp ( Penaeus monodon ) and white leg shrimp ( Litopenaeus vannamei ) across several countries. Prolonged infections with WSSV are difficult to eliminate with traditional methods like vaccinations, probiotics, and immunostimulants. Herein, we assessed the antiviral effectiveness of two medicinal plants, Cydonia oblonga and Juglans regia , against WSSV. The crude ethanolic leaf extract of J. regia and the acetone fruit extract of C. oblonga were evaluated through phytochemical analysis, GC–MS profiling, in silico studies, in vivo toxicity assessment, and antiviral validation. The presence of bioactive substances, such as phenolics, flavonoids, and antioxidants known for their strong antiviral and immunomodulatory properties, was verified by phytochemical analysis. In particular, the important bioactive constituents with known antiviral potential, including naringenin, juglone, kaempferol, beta‐sitosterol, quercetin, and epicatechin, were confirmed in these plant extracts by GC–MS analysis. Strong binding affinities of these medicines to the VP28 envelope protein of WSSV were shown in silico molecular docking studies, with the binding energies ranging from −6.0 to −8.9 kcal/mol. Significant protection against WSSV challenge was demonstrated by in vivo neutralisation tests. Pairwise comparisons confirmed extremely significant differences between the treated and untreated infected groups, and these results were statistically significant ( p ≤ 0.05). Molecular diagnostics by PCR provided additional confirmation of the antiviral activity of the medicinal plants, coupled with a Western blot assay and an indirect ELISA. Taken together, the findings suggest that the studied medicinal plants can offer a safe, affordable, and environmentally beneficial substitute for synthetic antiviral drugs in aquaculture.

Minimal Adverse Effects of lpa1 and lpa2 Mutations on Seed Germination and Vigour in Low-Phytate Maize - Vinay Rojaria; Ashvinkumar Katral; Sudipta Basu; Rajkumar Uttamrao Zunjare; Govinda Rai Sarma; Vinay Bhatt; Atul Kumar; Ashwani Kumar; Gyanendra Singh; Firoz Hossain; Vignesh Muthusamy (Journal of Plant Growth Regulation, 2026)

Understanding the Impact of Particle Size and Crystal Habit of Mesalamine Drug Substances on Their Packing, Wetting, and Dissolution Behaviour: A Science-based Approach for Selection of API Vendor - Prakash Kumar Sirvi; Ayush Rohila; Sakshi Kunjir; Sadhana Dhyagala; Ankit Kumar; Rajkumar Malayandi (AAPS PharmSciTech, 2026)

Ichnofabrics of the Barail Group (Priabonian-Chattian), Manipur-Nagaland Section, India - Hemanta S Rajkumar; Echeni Heni (Journal of Earth System Science, 2026)

In vitro cleavage validation assay of myostatin gene by CRISPR-Cas9 ribonucleoprotein complex: from PCR amplification to cleavage assay - Hazra Mohammad; Rudra Nath Chatterjee; Sai Prasanna Jammula; Chaitra Kumboju; Himabindu Vadlapally; Ashwini Ramidi; Rajashree Ambalavanan; Faisal Yousuf; Priyanka Tetarwal; Anuradha Chelliah; Satyapal Yadav; Shyam Sundar Paul; et al. (The Nucleus, 2026)

A Review on Multi-functional Chitosan Derivatives for Diabetes Management: Mucoadhesive Drug Delivery and Diabetic Wound-healing Applications - Venkatesan Karthick; Rajkumar Thamarai; Singamoorthy Amalraj; Kavitha Narayanasamy (Current Pharmacology Reports, 2026)

Understanding the Influence of Molarity, Buffer Capacity, and pH on Product-specific Guidance Dissolution Method for Developing a Discriminatory Dissolution Method for the Development of Mesalamine Products - Ankit Kumar; Sakshi Kunjir; Prakash Kumar Sirvi; Ayush Rohila; Sadhana Dhyagala; Rajkumar Malayandi (AAPS PharmSciTech, 2026)

Eco-epidemiological dynamics of Vibrio-associated vibriosis in freshwater fish farms: Implications for aquatic health and food safety - Rajkumar Thamarai; Venkatesh Arun; Venkatesan Karthick; Singamoorthy Amalraj; Rajkumar Prabhakaran; Kalidass Subramaniam (Regional Studies in Marine Science, 2026)

Genomic insights into endophytic Bacillus amyloliquefaciens BBE16 and Bacillus velezensis BBE18 reveal their biocontrol potential against Fusarium wilt in banana - Rajkumar Sudharsan; Chinnan Kannan; Arutselvan Vanitha; Annadurai Praveen; Pulapet Sowmya; Jaganathan Gowri Shankar; Markkandan Kesavan; Rajapandiyan Krishnamoorthy; Mohammad A. Alshuniaber; Magdi A. Osman; Mansour K. Gatasheh; Rasheed A. Abdulraheem (Physiological and Molecular Plant Pathology, 2026)

Exposome-induced dysregulation of glycemic homeostasis: Emerging biomarkers for diabetes risk and progression - Singamoorthy Amalraj; Venkatesan Karthick; Rajkumar Thamarai; Mani Suganya (Environmental Pollution, 2026)

Ectoparasite diversity and Orientia tsutsugamushi infection in rodent hosts from scrub typhus-endemic areas of the Western Himalayas, India - Govindarajan Renu; Nagaraj Jaganathasamy; Krishnamoorthi Ranganathan; Rajamannar Veeramanoharan; Rajkumar Venkatesan; Taju Gani; Abdul Majeed Seepoo; Sahul Hameed Azeez Sait; Manju Rahi; Paramasivan Rajaiah; Philip Samuel Paulraj (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Thermally Stressed Solid-State Stability of Semaglutide: Understanding the Influence of Temperature on Protein Content, Secondary Structure, Phase Transition, and Chemical Degradation - Sideequl Akbar; Adarsh Malgave; Anumol Joseph; Ankit Kumar; Rajkumar Malayandi (Pharmaceutical Research, 2026)

Correction to: Dynamics of accumulation of lysine and tryptophan, and kernel modification in opaque2, opaque16, and double mutant (opaque2/opaque16) genotypes during kernel development in maize - Gulab Chand; Vignesh Muthusamy; Tanu Allen; Nisrita Gain; Bhavna Singh; Suman Dutta; Nitish R. Prakash; Sohini Singh; Konsam Sarika; Gautam Chawla; Rajkumar U. Zunjare; Firoz Hossain (Journal of Applied Genetics, 2026)

Glucocorticoid receptor-targeted liposomal delivery of wnt/β-catenin pathway inhibitor selectively induces efficient colorectal tumor regression - Pritam Das; Tithi Bhattacharyya; Aasia Ansari; Anjaneyulu Eanti; Yogesh Chandra; Rajkumar Banerjee (Drug Delivery and Translational Research, 2026)

Advancing sustainable environmental flow management for the Narmada River - Rewa Bochare; Vikas Patel; Rajkumar Patel (Arabian Journal of Geosciences, 2026)

Microbial Mediation of Biogeochemical Cycles in Seagrass Ecosystems: Functions, Stressors, and Technological Innovations - Kasturi Taneti; Elavumkudi Paulose Nobi; Sigamani Sivaraj; Jayaraj Rajkumar; Elangovan Dilipan (Marine Ecology, 2026)
Seagrass ecosystems are vital coastal habitats that deliver essential ecological services such as nutrient cycling, sediment stabilization, and long‐term carbon sequestration. As key blue carbon sinks, they play a pivotal role in regulating major biogeochemical cycles, particularly nitrogen, carbon, phosphorus, and sulfur through complex interactions between seagrass roots and associated microbial communities. Microbial functions like nitrogen fixation, phosphorus solubilization, and sulfide detoxification are integral to maintaining seagrass productivity, especially in nutrient‐poor, anoxic sediments. However, these ecosystems face increasing threats from anthropogenic activities such as eutrophication, habitat destruction, chemical pollution, and climate change, all of which disrupt microbial processes and nutrient fluxes. Such disruptions may transform seagrass meadows from carbon sinks to carbon sources, intensifying climate feedback mechanisms. This review emphasizes current knowledge on the ecological and microbial roles within seagrass systems, drawing attention to case studies from Indian coastal regions that highlight the impact of natural and human‐induced stressors on seagrass decline. Additionally, it explores the promise of advanced technologies such as artificial intelligence, remote sensing, and genomics for improving the monitoring, restoration, and spatial planning of seagrass habitats. Tools like deep learning algorithms, satellite imagery, and SNP genotyping provide precise data on ecosystem health and resilience. Integrating these innovations with national policies such as the National Environment Policy, Wildlife Action Plan, and Coastal Regulation Zone (CRZ) guidelines is essential for effective conservation. A multidisciplinary, ecosystem‐based strategy that emphasizes microbial diversity, genetic adaptation, and technological innovation is imperative to safeguard these critical marine habitats amid rapid environmental change.

Novel P2X4 Receptor Antagonist MRS4719 Improves Ischemia/reperfusion Injury in Mice - Rajkumar Verma; Jinting Zhang; Sanjeev Kumar Yadav; Jianlin Feng; Chunxia C. Cronin; Daylin Gamiotea-Turro; Kiran S. Toti; Zhiwei Wen; Kenneth A. Jacobson; Bruce T Liang (Medicinal Chemistry Research, 2026)

Influence of pH, Buffering Capacity, Ionic Strength, Bile Salts, and Model Drugs on Micellization Behaviour of Salcaprozate Sodium in Physiological Range pH Buffers - Sideequl Akbar; Anumol Joseph; Adarsh Malgave; Ankit Kumar; Priyambada Bej; Rajkumar Malayandi (AAPS PharmSciTech, 2026)

Folate receptor-mediated delivery of doxorubicin modulates tumor-associated macrophages for effective anti-oral cancer therapy - Dwaipayan Bhattacharya; Kalyani Sakhare; Aasia Ansari; Abhiram Kumar; Piyush Khandelia; Rajkumar Banerjee; Kumar Pranav Narayan (The Nucleus, 2026)

Charting the future of coastal resilience: A three-decade global exploration of coastal vulnerability science and strategic gaps - Santu Guchhait; Manoranjan Mishra; Shreerup Goswami; Suman Paul; Rajkumar Guria; Richarde Marques da Silva; Celso Augusto Guimarães Santos; Manjula Ranagalage; Abu Reza Md. Towfiqul Islam (Regional Studies in Marine Science, 2026)

Spatiotemporal drought drivers in rainfed agroecosystems: A hybrid geospatial and machine learning approach for LULC-specific Vegetation Health Index (VHI) trends and yield loss assessment in the Eastern Ghats region (Odisha), India - Rajkumar Guria; Manoranjan Mishra; Celso Augusto Guimarães Santos; Richarde Marques da Silva; Pijus Hatui (Remote Sensing Applications: Society and Environment, 2026)

Early discrimination of conservation tillage practices in wheat using a novel spectral index from Sentinel-2 time series - Rajkumar Dhakar; Vinay Kumar Sehgal; Parmod Kumar; Niveta Jain (Remote Sensing Applications: Society and Environment, 2026)

Hierarchical SPEES nanocomposite ionomer with phosphomolybdic acid decorated Co3O4 nanofiller as PEM for microbial fuel cells: An anti-biofouling and scale-up approach - John Solomon; Akshaya Senthilkumar; Naveen Rajkumar Sivakumar; R. Devi; Sangeetha Dharmalingam (Journal of Environmental Management, 2026)

Pan-transcriptome analysis of diverse chickpea accessions reveals specific expression patterns and genetic variations associated with agronomic traits - Mohan Singh Rajkumar; Ayushman Kumar Banerjee; Juhi Bansal; Mukesh Jain; Rohini Garg (Plant Molecular Biology, 2026)

Simulations of Sun-Induced Fluorescence in Wheat Under Water and Nitrogen Levels Using SCOPE Radiative Transfer Model - Shreya Gupta; Vinay Kumar Sehgal; Rajkumar Dhakar; Rakesh Pandey; Joydeep Mukherjee; Karun Kumar Choudhary; Niveta Jain; Koushik Bag; Dipankar Barman (Journal of the Indian Society of Remote Sensing, 2026)

The role of microbiota derived metabolites in modulating diabetic inflammation: a systematic review - Venkatesan Karthick; Rajkumar Thamarai; Singamoorthy Amalraj; Kalimuthu Nagarajan; Ganesan Manimegalai (Journal of Molecular Histology, 2026)

A potassium titanate whisker-assisted method for genetic transformation of Phanerochaete chrysosporium using a Cas9-sGFP expression vector - Falguni Aggarwal; Simran Jatwani; Rishabh Rajkumar Jadhav; Rachana Yadav; Saurabh Jyoti Sarma; Deepa Khare (World Journal of Microbiology and Biotechnology, 2026)

Discovery of putative G-protein-biased µ-opioid agonists via hierarchical virtual screening of ultra-large chemical space - Rajkumar R; Tanmaykumar Varma; Prabha Garg (Molecular Diversity, 2026)

Corticomorphic Hybrid CNN-SNN Architecture for EEG-Based Low-Footprint Low-Latency Auditory Attention Detection - Richard Gall; Deniz Kocanaogullari; Murat Akcakaya; Nicole Laffan; Deniz Erdogmus; Rajkumar Kubendran (Annals of Biomedical Engineering, 2026)

Doxorubicin-Induced Cardiotoxicity: Molecular Mechanisms to Novel Therapeutic Frontiers of Recent Preclinical Discoveries - Nandini Dubey; Satnam Singh; Pranav Panchbhai; Gauri Chaturvedi; Ahsas Goyal; Nirmal Singh; Jagriti Bhatia; Rajkumar Yadav; Sudhir Kumar Arava; Arvind Kumar; Mayank Yadav; Abhishek Yadav; et al. (Cell Biochemistry and Biophysics, 2026)

Unveiling the Link Between Expression of Aspartate Kinase2 (ask2) Gene and Accumulation of Methionine in Developing Maize Kernels - Hriipulou Duo; Rashmi Chhabra; Rajkumar U. Zunjare; Gaurav Sharma; Subhra J. Mishra; Vignesh Muthusamy; Firoz Hossain (Biochemical Genetics, 2026)

Geospatial analysis of Cyclone Remal's impact on the Sundarbans Biosphere Reserve: Insights into vegetation loss, shoreline changes, and flooding dynamics - Manoranjan Mishra; Debdeep Bhattacharyya; Tamoghna Acharyya; Rajkumar Guria; Suman Paul; Chandra Shekhar Dwivedi; Palash Naiya; Richarde Marques da Silva; Celso Augusto Guimarães Santos (Regional Studies in Marine Science, 2026)

Deciphering biocontrol efficacy and in silico mechanistic elucidation of Trichoderma asperellum and Bacillus licheniformis against groundnut stem rot caused by Sclerotium rolfsii - Sivaji Jeevanantham; Renganathan Periyasamy; Suthin Raj Thankaraj; Meena V. Ruppavalli; Annadurai Praveen; Rajendiran Livitha; Rajkumar Sudharsan; Muthusamy Karthikeyan (Physiological and Molecular Plant Pathology, 2026)

The Significance of Serum Beta-Hydroxybutyrate and Urine Biochemical Markers in Determining the Severity of COVID-19 Infection - K. Ambedkar Priyan; Nirmala Hazari; Jyoti Sitaram Ugalmugale; S. Shagana; Jayshree Suhas Bavikar; S. Rajkumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Integrating critical nitrogen dilution curve, nitrogen nutrition index, and yield response modelling to optimize nitrogen requirement in spring wheat - Koushik Bag; Vinay Kumar Sehgal; Rajkumar Dhakar; Kalikinkar Bandyopadhyay; Manoj Shrivastava; Tapan Jyoti Purakayastha; Soumen Pal (Plant Physiology Reports, 2026)

Spatiotemporal assessment of extreme rainfall events in the Wainganga river basin using CMIP6 climate models - Gupta Abhishek Rajkumar; Manish Kumar Nema; Deepak Khare (Natural Hazards, 2026)

Long-term Conservation Agriculture with Subsurface Nitrogen Placement Enhances Wheat yield, Soil Nitrogen retention, and Nitrogen Use Efficiency in the North-west Indo-Gangetic Plains - Kiranmoy Patra; C. M. Parihar; Ayan Sarkar; K. Srikanth Reddy; D. R. Sena; Rajkumar Dhakar; Sneha Bharadwaj; Alok Sinha; Susnigdha Sengupta; Manojit Chowdhury; Hüdaverdi Gürkan; Hari Sankar Nayak (International Journal of Plant Production, 2026)

Genetic analysis of tasselseed4 (ts4) regulating APETALA2 floral homeotic transcription factor and its interactions with silkless1 (sk1) and tasselseed2 (ts2) genes for innovative silkless baby corn breeding - Anurag Awasthi; Rajkumar Uttamrao Zunjare; Firoz Hossain; Vignesh Muthusamy; Ashvinkumar Katral (Euphytica, 2026)

Haploids (n) possess significantly compromised morphological, physiological and biochemical attributes over diploid (2n) plants in maize - Suman Dutta; Sudhir Kumar; Vignesh Muthusamy; Rajkumar U. Zunjare; Subhra J. Mishra; Nisrita Gain; Botta T. Ganesh; Ravindra K. Kasana; Jayanthi Madhavan; Rajkumar Subramani; Firoz Hossain (Cereal Research Communications, 2026)

Reverse Engineering of Branded Mesalamine Prolonged Release Granules for Synthesis of QTPP and FMEA: A Systematic Approach for Oral Complex Generic Product Development - Sadhana Dhyagala; Ankit Kumar; Prakash Kumar Sirvi; Sakshi Kunjir; Ayush Rohila; Rajkumar Malayandi (AAPS PharmSciTech, 2026)

Drain, gain and sustain waterlogged-saline lands: assessing the impact of sub-surface drainage in India for policy perspectives - Suresh Kumar; Satyendra Kumar; Pratap Singh Birthal; Ranjay K. Singh; Rajkumar; Bhupender; Rohtash Kumar; Anil Kumar; R. K. Yadav (Environment, Development and Sustainability, 2026)

Molecular characterization of novel sex determining genes (silkless1-, tasselseed1-, tasselseed2- and tasselseed4-) based maize genotypes using genic- and genomic- SSR markers - Anurag Awasthi; Rajkumar Uttamrao Zunjare; Firoz Hossain; Vignesh Muthusamy; Gulab Chand; Ashvinkumar Katral (The Nucleus, 2026)

Functional genomics and Pan-genome mining of endophytic Streptomyces rochei BBE1 reveal plant growth-promoting traits and biocontrol potential against banana Fusarium wilt - Rajkumar Sudharsan; Arutselvan Vanitha; Chinnan Kannan; Sivaji Jeevanantham; Nelaturi Hima Shankar Reddy; Pulapet Sowmya; Jaganathan Gowri Shankar; Markkandan Kesavan; Rajapandiyan Krishnamoorthy; Mohammad A. Alshuniaber; Magdi A. Osman; Mansour K. Gatasheh (World Journal of Microbiology and Biotechnology, 2026)

Targeted metabolomic approach to elucidate flavonoid profiles employing LC-MS/MS in leaves and pseudo-fruit of Indian Cashew cultivars (Anacardium occidentale L.) - Manjesh Guligenahalli Narayanappa; Veena Gonibeedu Lakshmana; Rajkumar Arjun Dagadkhair; Shamsudheen Mangalassery; Jamboor Dinakara Adiga; Bratati Chowdhury; Dalasanuru Chandregowda Manjunathagowda; Tadagavadi Nagaraju Madhu; Lokesha Ankanahalli Narayanashetty (South African Journal of Botany, 2026)

Coastal futures at risk: Adaptive coastal management and policy insights from sea-level rise and shoreline change in West Bengal, India - Manoranjan Mishra; Bilel Zerouali; Suman Paul; Debdeep Bhattacharyya; Rajkumar Guria; Mousumi Suna; Richarde Marques da Silva; Manjula Ranagalage; Celso Augusto Guimarães Santos (Science of The Total Environment, 2026)

Entomovectoring: a green technology for crop protection - Venkatesan Deva Dharshini; Madapuji Rajagopalan Srinivasan; Vangili Ramasamy Saminathan; Marimuthu Murugan; Kathithachalam Angappan; Eswaran Kokiladevi; Kuppusamy Rameash; Rajkumar Promoth Kumar; Mohammad Ikram; Sankar Raman; Ramasamy Premika (Journal of Plant Diseases and Protection, 2026)

Molecular docking in histological biomarker discovery and disease modeling: techniques, validation, and translational perspectives - Venkatesan Karthick; Singamoorthy Amalraj; Rajkumar Thamarai; Sampath Paventhan (Journal of Molecular Histology, 2026)

Identification of subtropical breeding lines for ideal plant architecture in maize through multiple selection indices - Govinda Rai Sarma; Rajkumar U. Zunjare; Vignesh Muthusamy; Ravindra K. Kasana; Ikkurti Gopinath; Bhavna Singh; Godawari S. Pawar; Neha Sharma; Hriipulou Duo; Rashmi Chhabra; Rakesh K. Devlash; Satish K. Guleria; et al. (Journal of Applied Genetics, 2026)

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Process Optimisation, Pharmaceutical Characterisation, and in vitro Activity of Mesalamine Nanocrystals in PMA-differentiated THP-1 cell Lines in the Late Inflammatory and Profibrotic Phase - Sonam Sharma; Sakshi Kunjir; Sadhana Dhyagala; Abhishek Sahu; Subramanian Natesan; Rajkumar Malayandi (AAPS PharmSciTech, 2026)

Marker Assisted Development of Region-Specific In Vivo Haploid Inducers to Enhance Maize Breeding in Northeast India - Konsam Sarika; Firoz Hossain; Elangbam Lamalakshmi Devi; Vignesh Muthusamy; Rajkumar U. Zunjare; Chongtham Chinglen Meetei; Thokchom Nepolian Singh; Thokchom Repahini Devi; Takhenchangbam Oshin Sharma; Basudha Chanamthabam; Samarendra Hazarika (Agricultural Research, 2026)

Numerical modelling of fate and transport of heavy metal contaminant in an open dumping yard, South India - Arumugasamy Thangapandian Venkatesh; Velvizhi Gokuladoss; Lagudu Surinaidu; Sujatha Rajkumar; Upaka Rathnayake; Uma Shankar Masilamani (Environmental Monitoring and Assessment, 2026)

Demystifying the association of the gut–TMAO–heart axis: focusing on gut microbiota in myocardial infarction - Krushna Ch Maharana; Mayuri Adsule; M Rajkumar; Gopal Vishwas; Sanjiv Singh (Next Research, 2026)

Tamarind preservation: The impact of packaging and storage conditions on quality - Sreedevi Melya Sanjeevappa; Rajkumar Perumal; Vellingiri Palanimuthu; Krishnamma Peetal Narasaiah; Ramya Channarayanahalli Srirama (Journal of Stored Products Research, 2026)

Utilization of Genetically Engineered RuBisCO Enzyme for Capturing Carbon Dioxide to Address Environmental Challenges-An Overview - Priya Gupta; Rajkumar Prabhakaran; Nalini Soni; Sangeeta Devendra Kumar Singh; Chinnaperumal Kamaraj; Silambarasan Tamil Selvan; Neethu Asokan; Sudheer D. V. N. Pamidimarri; Balasubramanian Velramar (Water, Air, & Soil Pollution, 2026)

Cellular and Extracellular MicroRNA Dysregulation in LRRK2-Linked Parkinson’s Disease - Felix Knab; Jun-Hoe Lee; Raja Nirujogi; Kevin Menden; Luca Braunger; Lambrianna Logarnudi; Benjamin Riebenbauer; Fatma Busra Isik; Anto Praveen Rajkumar; Stefan Czemmel; Julia Fitzgerald; Thomas Gasser; et al. (Molecular Neurobiology, 2026)
Cell-free microRNAs in body fluids have emerged as promising biomarker candidates in neurodegenerative diseases. While several studies have identified dysregulated miRNAs in sporadic Parkinson’s disease, it remains unclear whether distinguishable alterations of cell-free miRNAs occur in genetic forms of the disease, such as those associated with the LRRK2 G2019S mutation. In this proof-of-concept study, we used a human induced pluripotent stem cell-derived dopaminergic neuron model to investigate whether the LRRK2 G2019S mutation induces detectable changes in the intra- and extracellular miRNAome, and whether miRNA signatures identified in vitro can be validated in patient-derived cerebrospinal fluid. We differentiated dopaminergic neurons from induced pluripotent stem cells carrying the LRRK2 G2019S mutation and an isogenic gene-corrected control. Extracellular vesicles were isolated from the culture medium and used as a source of cell-free miRNA. Next, small RNA libraries were generated and analyzed. Differentially expressed microRNAs were validated in an independent batch using RT-qPCR. We further quantified candidate microRNAs in cerebrospinal fluid samples from five LRRK2 G2019S patients and matching healthy controls. The patient cohort included the fibroblast donor from whom the stem cells were originally derived. We successfully isolated extracellular vesicles from induced pluripotent stem cell-derived human dopaminergic neurons. We identified a distinct set of differentially expressed miRNAs in cellular and cell-free RNA, among which let-7g-5p and miR-21-5p were consistently upregulated and validated across independent replicates. These alterations were reflected in the cerebrospinal fluid of the original donor and partially reproduced in additional LRRK2 patients, supporting the concept of patient-specific signatures. A strong correlation between intra- and extracellular miRNA expression was observed. Our findings demonstrate that induced pluripotent stem cell-derived dopaminergic neurons can serve as a model to identify individualized, cell-free microRNA signatures associated with the LRRK2 G2019S mutation. The dysregulated miRNAs detected in vitro were mirrored in patient cerebrospinal fluid, supporting their potential as accessible molecular readouts. These results lay the groundwork for personalized biomarker strategies in genetic forms of Parkinson’s disease and warrant further validation in larger patient cohorts.

Meta-QTL Analysis Explores Key Candidate Gene(s) for Ear Prolificacy in ‘Sikkim Primitive’: A Unique Maize Landrace of North Eastern Himalaya - Nitish Ranjan Prakash; Rajkumar Uttamrao Zunjare; Kuldeep Kumar; Sanchika Snehi; Vignesh Muthusamy; Firoz Hossain (Journal of Plant Growth Regulation, 2026)

Microplastic exposure causes organ damage in Puntius sophore - Aritha Sakthivel Mohana; Sangeetha Soundararajan; Koushikaa Shri Suresh; Kungumapriya Rajkumar (Environmental Monitoring and Assessment, 2025)

Prevalence of cyprinid herpesvirus-2 in goldfish aquarium shops in Tamil Nadu, India: a case report - Kumarasamy Kanimozhi; Allahbagash Badhusha; Gani Taju; Sivaraj Mithra; Seepoo Abdul Majeed; Mohamed Jaffer Abdul Wazith; Venkatesan Rajkumar; Azeez Sait Sahul Hameed (In Vitro Cellular & Developmental Biology - Animal, 2025)

Do human-modified landscapes influence composition and diversity of foraging guilds in mixed-species bird flocks in Wayanad, southern Western Ghats, India? - Karthika Chandran; K.P. Rajkumar; Roshin Tom; Nithin Divakar; Habeebrehman Hameed (Forest Ecology and Management, 2025)

Molecular delineation, development and validation of functional markers for brachytic2 (br2) gene governing dwarfing plant height in maize - Govinda Rai Sarma; Rashmi Chhabra; Vignesh Muthusamy; Shanmugavadivel P. Subramaniam; Gaurav Sharma; Hriipulou Duo; Vinay Rojaria; Rajkumar U. Zunjare; Viswanathan Chinnusamy; Firoz Hossain (Physiology and Molecular Biology of Plants, 2025)

Molecular characterization of T-, C- and S- specific cytoplasmic male sterile (CMS) maize inbreds using mitochondrial SSRs for its utilization in baby corn breeding - Saikat Pal; Rajkumar Uttamrao Zunjare; Vignesh Muthusamy; Munegowda Manoj Gowda; Hriipulou Duo; Rashmi Chhabra; Ravindra Kumar Kasana; Shalma Maman; Ashvinkumar Katral; Prolay Kumar Bhowmick; Firoz Hossain (Molecular Biology Reports, 2025)

Silkless1 gene in maize: development and validation of the gene-based markers for breeding silkless baby corn - Gulab Chand; Rajkumar Uttamrao Zunjare; Firoz Hossain; Vignesh Muthusamy; Ashvinkumar Katral; Priyanka Chauhan; Aayushi Singh Rathore; Subhra Jyotshna Mishra (Molecular Biology Reports, 2025)

Patent Landscaping of Time-dependent Mesalamine Prolonged-release Granules: A Case Study for Generic Formulation Development - Ayush Rohila; Ankit Kumar; Prakash Kumar Sirvi; Sadhana Dhyagala; Sakshi Kunjir; Rajkumar Malayandi (Journal of Pharmaceutical Innovation, 2025)

Assessing shoreline dynamics and human impacts on horseshoe crab habitats along the Balasore coast, India - Manoranjan Mishra; Bisnu Prasad Dash; Pritam Chand; Suman Paul; Debdeep Bhattacharyya; Rajkumar Guria; Shreerup Goswami; Rinku Kumar; Richarde Marques da Silva; Celso Augusto Guimarães Santos (Journal of Coastal Conservation, 2025)

Dynamics of accumulation of lysine and tryptophan, and kernel modification in opaque2, opaque16, and double mutant (opaque2/opaque16) genotypes during kernel development in maize - Gulab Chand; Vignesh Muthusamy; Tanu Allen; Nisrita Gain; Bhavna Singh; Suman Dutta; Nitish R. Prakash; Sohini Singh; Konsam Sarika; Gautam Chawla; Rajkumar U. Zunjare; Firoz Hossain (Journal of Applied Genetics, 2025)

Enrichment of phytoglycogen in sweet corn kernels through genomics-assisted selection - Rashmi Chhabra; Rajkumar U. Zunjare; Irum Gul; Subhra J. Mishra; Hriipulou Duo; Vinay Bhatt; Nisrita Gain; Ravindra K. Kasana; Vignesh Muthusamy; Firoz Hossain (Functional & Integrative Genomics, 2025)

Genomics-assisted stacking of waxy1, opaque2, and crtRB1 genes for enhancing amylopectin in biofortified maize for industrial utilization and nutritional security - Subhra J. Mishra; Firoz Hossain; Rajkumar U. Zunjare; Rashmi Chhabra; Ashvinkumar Katral; Ikkurti Gopinath; Vinay Bhatt; Govinda Rai Sarma; Zahirul A. Talukder; Ravindra K. Kasana; Elangbam L. Devi; Konsam Sarika; et al. (Functional & Integrative Genomics, 2025)

A Resident’s Risk: An Assessment of Pesticide Residues in the Tissues of Sarus Cranes (Antigone antigone) from Agricultural Foraging Grounds in Uttar Pradesh, India - Madhumita Rajkumar; Kanthan Nambirajan; Subramanian Muralidharan; Gaurav S. Singh; Gautam Kadam; Karthikeyan Prakasham; E. Jeevitha (Bulletin of Environmental Contamination and Toxicology, 2025)

Beyond the standard: a comprehensive review of innovative experimental models using Tenebrio molitor larvae - Anamaria Mendonça Santos; Cláudio Carvalho Santana Júnior; José Adão Carvalho Nascimento Júnior; Ana Maria Santos Oliveira; Gomathi Rajkumar; Izabel Almeida Alves; Mairim Russo Serafini (Biologia Futura, 2025)

Integrative bioinformatics and chemotactic insights into p-nitrophenol bioremediation by halotolerant aquatic Pseudomonas sp. strain PNPBRP5(2) - Sk Aftabul Alam; Biswajit Khan; Debabrata Karmakar; Rajkumar Mandal; Pradipta Saha (Archives of Microbiology, 2025)

Immune Response and Protective Efficacy of Quercetin in Tilapia, Oreochromis niloticus Against Tilapia Parvovirus - Badhusha Allahbagash; Taju Gani; Abdul Majeed Seepoo; Abdul Wazith Mohamed Jaffer; Nafeez Ahmed Abdul; Mithra Sivaraj; Rajkumar Venkatesan; Kanimozhi Kumarasamy; Vimal Sugumar; Sahul Hameed Azeez Sait (Journal of Fish Diseases, 2025)
The global tilapia farming industry is facing challenges due to tilapia parvovirus (TiPV), an emerging viral pathogen affecting cultured tilapia populations worldwide. It causes mass mortality in tilapia and high economic loss. Hence, an effective treatment is needed to control TiPV infection. Quercetin is one of the polyphenolic flavonoid compounds found in many natural products and could effectively inhibit various aquatic viral pathogens. Investigating the immunological response, virus clearance, and survival of tilapia fed quercetin‐formulated feed is the primary intent of this research venture. Tilapia gill cell line (TG) exposed with quercetin up to 50 μg/mL did not show any significant morphological changes. The MTT assay was performed to assess the toxic effects of quercetin on the TG cell line. Immune‐responsive genes ( TNF‐α , TLR‐7 , IL‐1β , IL‐8 , IL‐10 , MHC‐II , IFNγ , NF‐κβ , CD4 , and CD8 ) were studied in the head‐kidney and spleen samples of fish fed with quercetin‐formulated diets at different time intervals using RT‐qPCR. On 10 days post‐administration, all immune‐related genes were significantly upregulated in the fish fed quercetin‐formulated feed at a 50 mg/kg of feed. After receiving quercetin‐formulated feed for 10 days post administration, the experimental fish was challenged intraperitoneally with TiPV. The viral clearance and viral load were determined by PCR and qPCR. The survival of 90% was observed in fish fed with quercetin formulated feed after TiPV challenge. Our results revealed that quercetin is an effective compound to protect tilapia from TiPV infection and also help to trigger the immune response in tilapia.

Amino acid composition of pigeon pea varieties through HPTLC - Kirankumar P. Suthar; Diwakar Singh; Nitin B. Patel; Digvijay A. Chauhan; Rajkumar B. Katagi; Komal G. Lakhani (Vegetos, 2025)

MOF derived ZnO nanostructures modified with CoW12-polyoxometalates for enhanced sunlight driven degradation of methylene blue, ofloxacin and their mixtures - Nitin A. Tupsamindar; Arun S. Chopade; Sagar A. Chaudhari; Abhijit N. Kadam; Sandip R. Sabale; Vaishali Patil; Mohaseen S. Tamboli; Raisuddin Ali; Nguyen Tam Nguyen Truong; Vashishtha M. Gurame; Dattakumar S. Mhamane; Vijaykumar P. Ubale; et al. (Journal of Water Process Engineering, 2025)

Tailored BaZrO3 nanostructures for enhanced electrochemical performance in asymmetric supercapacitors - S. Rajkumar; Jiaqian Qin (Journal of Water Process Engineering, 2025)

Groundwater usage characterization in a tribal stretch infected with chronic kidney disease of unknown etiology (CKDu) - Herojeet Rajkumar; Rakesh K. Dewangan; Pradeep K. Naik; Janak R. Verma; Prabir K. Naik (Journal of Environmental Sciences, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Sustainable innovative technologies for a circular economy: Artificial photosynthesis, photobiorefineries, bioplastics, waste-to-wealth, and thermoelectric generators - Ganeshraja Ayyakannu Sundaram; Rajkumar Kanniah; Mani Sivakumar; Jenif D'souza Antonisamy (Biomass and Bioenergy, 2025)

Biogenic synthesis of CuO-TiO2 nanocomposites from Senna auriculata (L.) Roxb. Plant extract and its evaluation of antioxidant, antibacterial and anticancer activity of HepG2 cell lines - Manickam Rajkumar; S.I. Davis Presley; M. Yasmin Begum; Ali Alamri; Adel Al Fatease; Koyeli Girigoswami; Prabha Govindaraj; Shobana Sampath; Rajaram Madhankumar; Paramasivam Deepak (Biocatalysis and Agricultural Biotechnology, 2025)

Geospatial analysis of shoreline dynamics and drivers in the Sundarbans Biosphere Reserve (1990–2020): Integrating natural and anthropogenic influences for coastal resilience - Suman Paul; Manoranjan Mishra; Rajkumar Guria; Richarde Marques da Silva; Celso Augusto Guimarães Santos (Science of The Total Environment, 2025)

Enhanced dual removal of chromium and lead ions from water using biopolymer modified ferric–alumina layered double hydroxides - V. Nithya Priya; D. Karthigaimuthu; S.Sasi Florence; M. Rajkumar; S.P.Linto Sibi; M.S. Sobana; J. Mobika; V. Vijayalakshmi; P. Ahila (Journal of Environmental Chemical Engineering, 2025)

A Nanocomposite Approach for Efficient Removal of Acidic and Basic Dyes from Wastewater Using Polypyrrole-Grafted Sodium Alginate with Bentonite Integration - A. Rajkumar; N. Sivarajasekar; Mohammad Rafe Hatshan; Shamshad Khan (Water, Air, & Soil Pollution, 2025)

Accelerated development of MTL and DMP gene-based subtropically-adapted maternal haploid inducer lines in maize using molecular breeding - Nisrita Gain; Vignesh Muthusamy; Rashmi Chhabra; Amitkumar D. Kyada; Suman Dutta; Gulab Chand; Ravindra K. Kasana; Konsam Sarika; Elangbam L. Devi; Jayanthi Madhavan; Rajkumar Subramani; Rajkumar U. Zunjare; et al. (Planta, 2025)

Geospatial analysis of lightning-related deaths in a single day induced by extreme weather: are these fatalities avoidable? - Manoranjan Mishra; Rajkumar Guria; Umasankar Das; Celso Augusto Guimarães Santos; Richarde Marques da Silva (Natural Hazards, 2025)

Potential Soil Loss Estimation Using Machine Learning and Geospatial Technology in Part of the Eastern Plateau and Hill Region of West Bengal - Arindam Chattaraj; Amrita Daripa; Sudipta Chattaraj; Sah Kausar Reza; Sudip Dey; Swapan Paul; Rajkumar Porel; Feroze Hasan Rahman (Journal of the Indian Society of Remote Sensing, 2025)

Exosomes in pancreatic islet biology and diabetes: Mechanisms, Biomarkers, and potential therapeutic perspectives - Venkatesan Karthick; Rajkumar Thamarai; Singamoorthy Amalraj; Mani Suganya; Panneerselvam Suganya (Journal of Molecular Histology, 2025)

Comparative analysis of genetic diversity and population structure in safflower using simple sequence repeat (SSR) and single nucleotide polymorphism (SNP) markers - Prasanna Kumar Gaddam; Pooja Pathania; Parimalan Rangan; Prabhanshu Kumar; Kusuma Kumari Panda; S. Rajkumar (Genetic Resources and Crop Evolution, 2025)

Allelic Diversity and Development of Breeder-Friendly Marker Specific to floury2 Gene Regulating the Accumulation of α-Zeins and Essential Amino Acids in Maize Kernel - Hriipulou Duo; Rashmi Chhabra; Vignesh Muthusamy; Suman Dutta; Ashvinkumar Katral; Govinda Rai Sarma; Gulab Chand; Subhra J. Mishra; Rajkumar U. Zunjare; Firoz Hossain (Biochemical Genetics, 2025)

Flurbiprofen restores rifampicin and isoniazid sensitivity in multidrug-resistant Mycobacterium tuberculosis putatively by inhibiting efflux pumps Rv0194 and Rv0933 - Padmasini Elango; Christy Rosaline Nirmal; Sam Ebenezer Rajadas; Rajkumar Ravi; Naresh Babu Chilamakuru; Azger Dusthackeer V. N. (Folia Microbiologica, 2025)

Fabrication of ZrMo2O8-warpped g-C3N4 composite for effective photocatalytic degradation of methylene blue under LED illumination for environmental applications - J. John Christopher; S. Rajkumar; J. Princy Merlin; Jiaqian Qin (Journal of Water Process Engineering, 2025)

Marine Brachyuran Crabs of Gujarat waters, India: An Updated Checklist with Fifteen New Records - Piyush Vadher; Hitesh Kardani; Ondřej Radosta; Rajkumar Dabhi; Imtiyaz Beleem (Thalassas: An International Journal of Marine Sciences, 2025)

Seismological evidence and source characteristics of 28 April 2021 Assam valley earthquake sequence in Northeast India: Kopili fault activation and seismic hazard implications - Ajay Pratap Singh; Sanjay Kumar Prajapati; Babita Sharma; Rajkumar; Prabhat Pandey; Vikas Kumar; Om Prakash Mishra (Natural Hazards, 2025)

Unraveling the multifaceted role of ethephon in plant physiology: from seed germination to crop maturation and harvesting - Kumaresan Kowsalya; Jayachandran Halka; Muthukrishnan Anand; Jesudass Joseph Sahayarayan; Renganathan Rajkumar; Muthukrishnan Arun (Journal of Plant Biochemistry and Biotechnology, 2025)

Behaviour of prestressed hollow core slabs after exposure to elevated temperatures: an experimental and numerical approach - T M Jeyashree; P R Kannan Rajkumar (Innovative Infrastructure Solutions, 2025)

LC-ESI-HRMS-Based Evaluation of Antioxidants as Additives to Inhibit Genotoxic Nitrosamine Formation in Metformin Hydrochloride Tablets - Aishwarya Dande; Nikhil Pallaprolu; Sangita Gadilohar; Sushmita Mishra; Rajkumar Malayandi; Subramanian Natesan; Abhishek Sahu; Murali Kumarasamy; Ravichandiran Velayutham; Ramalingam Peraman (AAPS PharmSciTech, 2025)

Computational discovery of ATP-competitive GSK3β inhibitors using database-driven virtual screening and deep learning - Tanmaykumar Varma; Pradnya Kamble; R. Rajkumar; Prabha Garg (Molecular Diversity, 2025)

Influence of Milling Parameters on Crystal Morphology, Thermal Behavior, and Dissolution of Mesalamine Nanocrystals - Sakshi Kunjir; Prajakta Pathare; Sonam Sharma; Jyoti Deoriya; Subramanian Natesan; Rajkumar Malayandi (Pharmaceutical Research, 2025)

Dissolution Profiles Comparison Using Various Model Independent Statistical Approaches: Can We Increase Chance of Similarity? - Rajkumar Boddu; Karthik Parsa; Priyansh Pandya; Sivacharan Kollipara (Pharmaceutical Research, 2025)

Effect of hybrid fiber and hybrid rebars on flexural strength of reinforced concrete beams - R. Rajkumar; Abhay Yadav; C. Arunkumar (Innovative Infrastructure Solutions, 2025)

Magma heterogeneity in the generation of ophiolitic mafic rocks on the eastern flank of the Indian plate - Sashimeren Imtisunep; Athokpam Krishnakanta Singh; Monika Chaubey; Rajkumar Bikrmaditya Singh; Bendangtola Longchar; Shoraisam Khogenkumar; Amrita Dutt (Acta Geochimica, 2025)

Association of Lasiodiplodia theobromae and L. iraniensis with spindle rot of coconut, Cocos nucifera L. as revealed through polyphasic approach - V.H. Prathibha; M.K. Rajesh; Daliyamol; Rajkumar; J. Keerthana; K.P. Thejasri; B.J. Nirmal Kumar; K.R. Latha; P. Subramanian; Vinayaka Hegde (Physiological and Molecular Plant Pathology, 2025)

Unveiling the functionality of phytase activity in maize for enhanced bioavailability of minerals: a new avenue for nutritional security - Botta Thandava Ganesh; Vignesh Muthusamy; Ashvinkumar Katral; Ikkurti Gopinath; Amitkumar D. Kyada; Gaurav Sharma; Jayanthi Madhavan; Rajkumar U. Zunjare; Firoz Hossain (Journal of Cereal Science, 2025)

Unveiling tree species resilience to Lantana camara allelopathy for forest landscape restoration in Central India - Neeraj Prajapati; Surjeet Singh Dhaka; Shivani Rohilla; Neelu Singh; Arunachalam Rajasekaran; Muthu Rajkumar; Ajit Kumar Maurya (Plant Ecology, 2025)

Development and performance analysis of PVA-polyester fiber reinforced cementitious composites incorporating manufactured sand - Chintada Chandrasekhar; G.D Ransinchung R.N.; Galipelli Rajkumar (European Journal of Environmental and Civil Engineering, 2025)

Natural products-based cancer vaccination strategy - Archishman Ash; Prashasti Arora; Lauren Sharel Christopher; Shivani Rajkumar; Soham Bindu; Koustav Sarkar (Next Research, 2025)

Resistance mechanism of energy canes developed from Saccharum spontaenum and Erianthus arundinaceus against sugarcane borer pests - M. Punithavalli; P. Govindaraj; M. Balaji Rajkumar (Journal of Asia-Pacific Entomology, 2025)

Effect of temperature on the replication of striped jack nervous necrosis virus in kidney cell line of rainbow trout (RTK) - Suryakodi Selvam; Nafeez Ahmed Abdul; Mithra Sivaraj; Kanimozhi Kumarasamy; Rajkumar Venkatesan; Taju Gani; Abdul Majeed Seepoo; Sahul Hameed Azeez Sait (VirusDisease, 2025)

Sodicity tolerance in Jamun (Syzygium cumini L. Skeels) genotypes based upon growth and physiological traits - Rajkumar; Ashwani Kumar; Anshuman Singh; Nirmal Singh; Akshay Kumar; Pratibha Poonia; Antim Kundu (Plant Physiology Reports, 2025)

Temporal gene expression profiling suggests stage-specific regulation of apocarotenoid biosynthesis genes during stigma development in Crocus sativus L. - Khushboo Gupta; Mohan Singh Rajkumar; Vaishali Singh; Pooja Rani; Aijaz A. Wani; Ashwani Pareek; Rohini Garg; Mukesh Jain (Physiology and Molecular Biology of Plants, 2025)

A comprehensive 120-year assessment of drought dynamics and climate teleconnections in Odisha, India (1901–2020): insights from SPI and trend evaluation - Rajkumar Guria; Sanjeev Dwivedi; Pujyasmita Nayak; Shreerup Goswami; Richarde Marques da Silva; Celso Augusto Guimarães Santos; Prakash Chandra Dash; Manoranjan Mishra; Muhammad Mubashar Dogar; Gowhar Meraj; Mansour Almazroui (Natural Hazards, 2025)

Multifaceted Traits of Osmotic Stress Tolerance in Vigna Species: A Study of Section Aconitifoliae from India - Nitin T. Gore; Ganesh D. Mankar; Sumaiya S. Shaikh; Rajkumar B. Barmukh; Pankaj S. Mundada; Suraj D. Umdale; Gayacharan; Nikhil B. Gaikwad; Tukaram D. Nikam; Vitthal T. Barvkar; Mahendra L. Ahire (Journal of Crop Health, 2025)

Exploring global trends and future research directions in Shoreline Analysis Systems (SAS): a bibliometric analysis - Manoranjan Mishra; Desul Sudarsan; Pritam Chand; Suman Paul; Abera Abiyo Dofee; Richarde Marques da Silva; Carlos Antonio Costa dos Santos; Rajkumar Guria; Celso Augusto Guimarães Santos (Journal of Coastal Conservation, 2025)

Predictive Role of Serotonin Receptor (5HTR2A) and Dopamine Receptor (DRD2) gene polymorphisms in risperidone-induced weight gain and hyperprolactinemia in patients with schizophrenia - Alladi Charanraj Goud; Ravi Philip Rajkumar; Deepak Gopal Shewade; Luxitaa Goenka; Suresh Kumar Srinivasamurthy (European Journal of Clinical Pharmacology, 2025)

Geochemical characterization of groundwater and source apportionment of potential pollutants in a tribal stretch infected with chronic kidney disease of unknown etiology - Herojeet Rajkumar; Pradeep K. Naik; Rakesh K. Dewangan; Janak R. Verma; Prabir K. Naik (Chemosphere, 2025)

Medicinal plant-product encapsulated with herb-hydrogel for ammonia removal and stress alleviation in semi-biofloc system containing aquaponics water cultured with Pangasianodon hypophthalmus - Kalpana Arambam; Kishore Kumar Krishnani; Rajkumar Debarjeet Singh; Ajit Kumar Verma; Kaushik Banerjee; Thongam Ibemcha Chanu; Neeraj Kumar (Aquaculture, 2025)

Forecasting shoreline dynamics and land use/land cover changes in Balukhand-Konark Wildlife Sanctuary (India) using geospatial techniques and machine learning - Manoranjan Mishra; Debdeep Bhattacharyya; Brihaspati Mondal; Suman Paul; Richarde Marques da Silva; Celso Augusto Guimarães Santos; Rajkumar Guria (Science of The Total Environment, 2025)

A review on green hydrogen production pathways and optimization techniques - S. Shanmugasundaram; J. Thangaraja; Sundararajan Rajkumar; S. Denis Ashok; Akella Sivaramakrishna; Tariq Shamim (Process Safety and Environmental Protection, 2025)

Revolutionizing the synergistic effect of filtration, pasteurization and bio-preservative on quality and microbiological shelf life of palm sap - Reena Das; Deiva Kani Rajkumar; Aamira Afrin Abdul; Madhuvantii Narayanan; Pachaiyappan Saravana Kumar (Food and Humanity, 2025)

Optimization of callus induction and cell suspension system in Hemidesmus indicus (L.) R. Br. for improved production of lupeol - Jayachandran Halka; Kumaresan Kowsalya; Nandakumar Vidya; Krishnagowdu Saravanan; Jaganathan Sakthi Yazhini Preetha; Rajkumar Vasanthkumar; Packiaraj Gurusaravanan; Muthukrishnan Anand; Muthuswamy Razia; Muthukrishnan Arun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

High amylopectin in waxy maize synergistically affects seed germination and seedling vigour over traditional maize genotypes - Zahirul A. Talukder; Rashmi Chhabra; Sudipta Basu; Nisrita Gain; Subhra J. Mishra; Ashwani Kumar; Rajkumar U. Zunjare; Vignesh Muthusamy; Firoz Hossain (Journal of Applied Genetics, 2025)

Detection of Tilapia parvovirus in farm-reared tilapia in India and its isolation using fish cell lines - Allahbagash Badhusha; Sivaraj Mithra; Gani Taju; Venkatesan Rajkumar; Seepoo Abdul Majeed; Selvam Suryakodi; Lekshmi Haridas; Divya Haridas; Pramoda Kumar Sahoo; Jyotirmaya Mohanty; Anirban Paul; Snatashree Mohanty; et al. (In Vitro Cellular & Developmental Biology - Animal, 2025)

Climate variability and forest fires: Trends, correlation, spatiotemporal patterns in the Seven Sister States of northeastern India (2001–2022) - Manoranjan Mishra; Rajkumar Guria; Biswaranjan Baraj; Celso Augusto Guimarães Santos; Richarde Marques da Silva; Carlos Antonio Costa dos Santos; Karma Detsen Ongmu Bhutia (Remote Sensing Applications: Society and Environment, 2025)

Lipoxygenases (LOXs): Will turning off this genetic switch help safeguard the flavor and nutritional quality of stored lipid-rich staple foods? - Parameshwaran Mathavaraj; Vignesh Muthusamy; Ashvinkumar Katral; Puja Mandal; Rajkumar Uttamrao Zunjare; Firoz Hossain (Food Chemistry, 2025)

Geospatial assessment of paddy crop water requirement using remote sensing and GIS in semiarid Ludhiana area of Indian Punjab - Harkanwal Jot Singh; Dnyaneshwar Arjun Madane; Rajkumar Pal; Reenu Sharma (Theoretical and Applied Climatology, 2025)

UTF1 Expression is Important for the Generation and Maintenance of Human iPSCs - Khyati Raina; Kirti Modak; Chitra Premkumar; Gaurav Joshi; Dhavapriya Palani; Krittika Nandy; Yazhini Sivamani; Shaji R. Velayudhan; Rajkumar P. Thummer (Stem Cell Reviews and Reports, 2025)

Analysis of lightning strikes and associated fatalities in Jharkhand, India from 2000 to 2020 - Manoranjan Mishra; Rajkumar Guria; Sanjay Srivastava; Richarde Marques da Silva; Celso Augusto Guimarães Santos (Natural Hazards, 2025)

An in silico approach to identify novel and potential Akt1 (protein kinase B-alpha) inhibitors as anticancer drugs - Umadevi Etikyala; Rajkumar Reddyrajula; T. Vani; Vinutha Kuchana; Udayakumar Dalimba; Vijjulatha Manga (Molecular Diversity, 2025)

First report of crown rot of coconut (Cocos nucifera L.) caused by Neodeightonia phoenicum in India - Daliyamol; Keerthana Jayarajan; Thamban Chendalam; Prathibha Veerappa Hanumanthappa; Sabana Abdulla Abdulla; Rajkumar; Vinayaka Hegde (Australasian Plant Pathology, 2025)

Porous lignocellulosic biomass enhances ammonia biotransformation in aquaponics water - Rajkumar Debarjeet Singh; Kishore Kumar Krishnani; Kalpana Arambam; Narinder Kumar Chadha; Kapil Sukhdhane; Madhuri S. Pathak; Ajit Kumar Verma (Aquaculture International, 2025)

First record of fruit rot in soursop caused by Lasiodiplodia theobromae in India - Prathibha V. H.; Panjavarnam G.; Daliyamol; Rajkumar; Keerthana S.; Thejasri K. P.; Gangaraj K. P.; Rajesh M. K.; Vinayaka Hegde (Journal of Plant Pathology, 2025)

Hydrogeochemical forecasting in a tribal stretch infected with chronic kidney disease of unknown etiology - Herojeet Rajkumar; Pradeep K. Naik; Rakesh K. Dewangan; Janak R. Verma; Prabir K. Naik (Science of The Total Environment, 2025)

Molecular Diversity Studies and Core Development in Sesame Germplasm (Sesamum indicum L.) Using SSR Markers - Rasna Maurya; Shivani Singh; Yangala Sudheer Babu; Fatima Nazish Khan; Bhagwat Nawade; Harinder Vishwakarma; Ajay Kumar; Rashmi Yadav; Radhamani Jalli; Mahalingam Angamuthu; Mothilal Alagirisamy; Rajkumar Subramani; et al. (Plant Molecular Biology Reporter, 2025)

Rice Transcriptomics Reveal the Genetic Determinants of An In Planta Photorespiratory Bypass: a Novel Way to Increase Biomass in C3 Plants - Parimalan Rangan; Dhammaprakash P. Wankhede; Rajkumar Subramani; Viswanathan Chinnusamy; Pooja Pathania; Arti Bartwal; Surendra K. Malik; Mirza Jaynul Baig; Anil Rai; Kuldeep Singh (Plant Molecular Biology Reporter, 2025)

Surface Melt Onset on Antarctic Sea Ice from India’s Oceansat-Series Scatterometers - Kamaljit Singh Rajkumar (Journal of the Indian Society of Remote Sensing, 2025)

Simplified mechanistic model for estimating leaf wetness - Rajkumar Dhakar; Basavaraj R. Amogi; Gajanan S. Kothawade; Lav R. Khot (Agricultural and Forest Meteorology, 2025)

Impact of land use change on the urban wetlands of the Imphal Valley in northeast India: an analysis of dying habitats of the endangered Manipuri pony—the original ponies of modern polo - Khoinaijam Sashikanta Meitei; Maibam Dhanaraj Meitei; Rajkumar Chingkhei; Anjali Waikhom; Waikhom Tomthinnganba Mangang (Environmental Science and Pollution Research, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Exploring shifting patterns of land use and land cover dynamics in the Khangchendzonga Biosphere Reserve (1992–2032): a geospatial forecasting approach - Karma Detsen Ongmu Bhutia; Harekrishna Manna; Rajkumar Guria; Celso Augusto Guimarães Santos; Sanjit Sarkar; Richarde Marques da Silva; FX Anjar Tri Laksono; Manoranjan Mishra (Environmental Monitoring and Assessment, 2025)

Effect of dwarfism and endogenous gibberellin modulation via growth regulators on heat stress tolerance in wheat - Shivani Nagar; V.P. Singh; Rajkumar Dhakar; Ajay Arora; Deepika Kumar Umesh; Ekta Joshi; Chandana Behera; Ravi Prakash Saini (South African Journal of Botany, 2025)

The impact of mercury exposure on male reproduction: Mechanistic insights - Bhawna Kushawaha; Rajkumar Yadav; Satish Kumar Garg; Emanuele Pelosi (Journal of Trace Elements in Medicine and Biology, 2025)

Development of stacking algorithm for bias-correcting the precipitation projections using a multi-model ensemble of CMIP6 GCMs in a semi-arid basin, India - Hemanandhini Shanmugam; Vignesh Rajkumar Lakshmanan (Theoretical and Applied Climatology, 2025)

Unveiling a novel morphometric approach in claws and canines for species discrimination and age stratification in leopard (Panthera pardus fusca) - Rajkumar Pavithra; Abu Muhsina Thunnisa; Dhayanithi Vasanthakumari; A. Udhayan (The Science of Nature, 2025)

Analysis of nutritional composition in opaque2- and crtRB1-based single- and double-biofortified super sweet corn - Bhavna Singh; Vignesh Muthusamy; Smriti Shrivastava; Gulab Chand; Nisrita Gain; Vinay Bhatt; Rajkumar U. Zunjare; Firoz Hossain (Journal of Applied Genetics, 2025)

Production of biologically active recombinant salmon calcitonin in Escherichia coli and fish cell line - A. Nafeez Ahmed; S. Abdul Majeed; G. Taju; S. Suryakodi; S. Mithra; M. J. Abdul Wazith; K. Kanimozhi; V. Rajkumar; A. Badhusha; A. S. Sahul Hameed (Archives of Microbiology, 2025)

Drip irrigation for sustaining high sugarcane ( Saccharum officinarum ) yield in marginally to moderately waterlogged saline vertisols of Karnataka, India - Rajkumar R.H.; Vishwanath J.; Annanagouda V. Karegoudar; Malharimartand J. Kaledhonkar; Anand S.R.; Anilkumar T. Dandekar; Raj Kumar Thakur (Irrigation and Drainage, 2025)
In the Tungabhadra project command, subsurface drainage is used to reclaim waterlogged saline areas, but its adoption is lower due to its high cost and highly skilled in nature. Irrigation water management could sustain high cane yields in mildly affected areas. A field experiment was conducted on waterlogged saline vertisols with sugarcane crops using surface drip, subsurface drip and furrow irrigation with water application amounts of 0.8, 1.0 and 1.2 of evapotranspiration (ET). The subsurface drip at 1.2 ET resulted in more leaching of salts and a higher moisture content. Also it had the highest cane yield (131.0 t ha −1 ), water productivity (WP) (8.30 kg m −3 ) and sugar WP (1.72 kg m −3 ) among the different methods. Among the irrigation levels, the 1.2 ET level had the highest cane yield (124.7 t ha −1 ), lowest WP (6.89 kg m −3 ) and highest sugar WP (1.43 kg m −3 ). The highest benefit–cost ratio was recorded for the subsurface drip treatment. Depth to water table was greater for the subsurface drip treatment compared to the furrow treatment. Therefore, subsurface drip irrigation at 1.2 ET for sugarcane can act as a viable preventive measure for sustaining high cane yield in mildly waterlogged saline vertisols in the command.

Forest fire probability zonation using dNBR and machine learning models: a case study at the Similipal Biosphere Reserve (SBR), Odisha, India - Rajkumar Guria; Manoranjan Mishra; Samiksha Mohanta; Suman Paul (Environmental Science and Pollution Research, 2025)

Sarcoptic mange in domestic rabbits: Pathogenesis, impact, and control strategies - Shanker K. Singh; Mukesh K. Srivastava; Rajkumar S. Yadav; Jitendra S. Gandhar; Sanju Kumari; Pooja Dawar; Krishna Verma (Veterinary Parasitology, 2025)

Multisensor Integrated Drought Severity Index (IDSI) for assessing agricultural drought in Odisha, India - Rajkumar Guria; Manoranjan Mishra; Richarde Marques da Silva; Carlos Antonio Costa dos Santos; Celso Augusto Guimarães Santos (Remote Sensing Applications: Society and Environment, 2025)

Sustainable selenium ions adsorption of cyclodextrin and cellulose functionalized layered double hydroxide/reduced graphene oxide nanocomposites - V. Nithya Priya; M. Rajkumar; V. Rajendran; J. Mobika; S.P. Linto Sibi; B. Veena; V. Vijayalakshmi; P. Ahila (Journal of Water Process Engineering, 2025)

Long-term shoreline dynamics of South Kerala Coast using satellite images - Shanmuga Priyaa S.; Rajkumar J.; Basanta Kumar Jena (Earth Science Informatics, 2025)

Compact, low-cost GNSS modules for efficient ionospheric probing: a case study from India during amplitude scintillation events of autumnal equinox 2022 - Sukabya Dan; Satarupa Chatterjee; Rajkumar Mandal; Chaitali Koley; Anindya Bose (GPS Solutions, 2025)

Melatonin induces endoreduplication through oxidative DNA damage triggering lateral root formation in onions - Sukhendu Maity; Rajkumar Guchhait; Kousik Pramanick (Acta Physiologiae Plantarum, 2025)

Characterisation of 3D printing cake batter with xanthan gum and optimization of printing parameters using response surface methodology - Pentala Mallesham; S. Parveen; R. Pandiselvam; P. Rajkumar; Ravindra Naik (International Journal of Gastronomy and Food Science, 2024)

The qualitative and molecular categorization for genetic diversity in Withania somnifera (L.) Dunal - S. Venugopal; M. Padma; M. Rajkumar; N. Seenivasan; P. Saidaiah; G. Sathish; A.C. Jnanesha; R.S. Kumar; R.K. Lal (Ecological Genetics and Genomics, 2024)

Remote sensing based Multivariate Hierarchical Agricultural Drought Index (MHADI) for India - Alka Rani; Vinay Kumar Sehgal; Rajkumar Dhakar; Abhilash; Bappa Das; Pragya (Theoretical and Applied Climatology, 2024)

Atypical sphingosine-1-phosphate metabolites—biological implications of alkyl chain length - Melanie Glueck; Alexandra Lucaciu; Julien Subburayalu; Roxane Isabelle Kestner; Waltraud Pfeilschifter; Rajkumar Vutukuri; Josef Pfeilschifter (Pflügers Archiv - European Journal of Physiology, 2024)
Sphingosine-1-phosphate (S1P) is a bioactive lipid signaling molecule with pleiotropic implications by both auto- and paracrine signaling. Signaling occurs by engaging five G protein-coupled receptors (S1P 1-5 ) or intracellular pathways. While the extensively studied S1P with a chain length of 18 carbon atoms (d18:1 S1P) affects lymphocyte trafficking, immune cell survival and inflammatory responses, the biological implication of atypical S1Ps such as d16:1 or d20:1 remains elusive. As S1P lipids have far-reaching implications in health and disease states in mammalian organisms, the previous contrasting results may be attributed to differences in S1P’s alkyl chain length. Current research is beginning to appreciate these less abundant atypical S1P moieties. This review provides an up-to-date foundation of recent findings on the biological implications of atypical S1P chain lengths and offers a perspective on future research endeavors on S1P alkyl chain length–influenced signaling and its implications for drug discovery.

Assessing sequence variation, haplotype analysis and molecular characterisation of aspartate kinase2 (ask2) gene regulating methionine biosynthesis in diverse maize inbreds - Hriipulou Duo; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Firoz Hossain (Molecular Genetics and Genomics, 2024)

Melt Granulation Techniques as an Alternative Manufacturing Technology for the Generic Development of Apixaban 5 mg Immediate-Release Tablets: A Case Study - S. Jailani; Prajakta Pathare; Sakshi Kunjir; Kishor Chakraborty; C. K. Dhanapal; Noohu Abdulla Khan; Rajkumar Malayandi (Journal of Pharmaceutical Innovation, 2024)

Evaluation of local finger millet (Eleusine coracana (L.) Gaertn.) landraces for salinity tolerance using growth and biochemical traits at the seedling stage - Sumaiya S. Shaikh; Nitin T. Gore; Ganesh D. Mankar; Rajkumar B. Barmukh; Pankaj S. Mundada; Suraj D. Umdale; Mahendra L. Ahire (Cereal Research Communications, 2024)

Isolation of Monocrotophos degrading bacterial consortium from agricultural soil for in vivo analysis of pesticide degradation - Ramesh Kande; Karthik Rajkumar; Pawan Kumar Anoor; Srinivas Naik; Sandeepta Burgula (Brazilian Journal of Microbiology, 2024)

Application of neuronal and retinal cell lines of Lates calcarifer for propagation of nervous necrosis virus - Sivaraj Mithra; Seepoo Abdul Majeed; Abdul Nafeez Ahmed; Selvam Suryakodi; Venkatesan Rajkumar; Allahbagash Badhusha; Kumarasamy Kanimozhi; Mohamed Jaffer Abdul Wazith; Gani Taju; Azeez Sait Sahul Hameed (Aquaculture International, 2024)

Fishery status of the green tiger shrimp (Penaeus semisulcatus) in Palk Bay, in the southeast coast of India: Local and global perspectives - Rajkumar Muthusamy; Saraswathy Lakshmi Pillai; Saravanan Raju; Ranjith Lakshmanan; Kavitha Mookaiah; Shoba Joe Kizhakudan (Ocean & Coastal Management, 2024)

Predicting forest fire probability in Similipal Biosphere Reserve (India) using Sentinel-2 MSI data and machine learning - Rajkumar Guria; Manoranjan Mishra; Richarde Marques da Silva; Minati Mishra; Celso Augusto Guimarães Santos (Remote Sensing Applications: Society and Environment, 2024)

Evaluation of large-scale deforestation susceptibility mapping in the mountainous region of the Himalayas: A case study of the Khangchendzonga Biosphere Reserve, India - Karma Detsen Ongmu Bhutia; Manoranjan Mishra; Rajkumar Guria; Biswaranjan Baraj; Arun Kumar Naik; Richarde Marques da Silva; Thiago Victor Medeiros do Nascimento; Celso Augusto Guimarães Santos (Remote Sensing Applications: Society and Environment, 2024)

Embryotoxicity and biochemical changes of clioquinol (CQ) and their impact on zebrafish (Danio rerio): An environmental safety concern - Selvam Naveenkumar; Chinnaperumal Kamaraj; Pradisha Prem; Rajagopalan Vijayalakshmi Boomija; Khalid A. Al-Ghanim; Vimal S; Perumal Vivekanandhan; Thamarai Rajkumar (Process Safety and Environmental Protection, 2024)

Multi-gene phylogeny and phenotypic analyses revealed an association of different Colletotrichum species with inflorescence dieback and leaf spot of arecanut in India - V.H. Prathibha; M.K. Rajesh; Akshay Dinesh; Balanagouda Patil; Daliyamol; N.R. Nagaraja; Rajkumar; A.A. Sabana; K.P. Gangaraj; K.P. Thejasri; Sunil S. Gangurde; Vinayaka Hegde (Physiological and Molecular Plant Pathology, 2024)

Green synthesis and evaluation of dual herb-extracted DHM-AgNPs: Antimicrobial efficacy and low ecotoxicity in agricultural and aquatic systems - Kalimuthu Nagarajan; Rajkumar Thamarai; Chinnaperumal Kamaraj; Khalid A. Al-Ghanim; Kalidass Subramaniam; Guilherme Malafaia (Journal of Environmental Management, 2024)

Rapid impact assessment of severe cyclone storm Michaung along coastal zones of Andhra and Tamil Nadu, India: A geospatial analysis - Manoranjan Mishra; Debdeep Bhattacharyya; Rajkumar Guria; Suman Paul; Richarde Marques da Silva; Celso Augusto Guimarães Santos (Journal of Environmental Management, 2024)

Examining the drivers of forest cover change and deforestation susceptibility in Northeast India using multicriteria decision-making models - Rajkumar Guria; Manoranjan Mishra; Biswaranjan Baraj; Shreerup Goswami; Celso Augusto Guimarães Santos; Richarde Marques da Silva; Karma Detsen Ongmu Bhutia (Environmental Monitoring and Assessment, 2024)

Seasonal variability of microplastic contamination in marine fishes of the state of Gujarat, India - Yagnesh B. Motivarash; Ashishkumar J. Bhatt; Rahul R. Jaiswar; Rehanavaz A. Makrani; Rajkumar M. Dabhi (Environmental Science and Pollution Research, 2024)

Euwallacea perbrevis (Schedl, 1951) and associated novel fungal symbiont, Fusarium sp.: A potential cause of wilting in cocoa, Theobroma cacao in India - Shivaji Hausrao Thube; R Thava Prakasa Pandian; M. Rajkumar; Merin Babu; A. Josephrajkumar; Santhoshkumar P; B.J. Nirmal Kumar; Vinayaka Hegde; Balanagouda Patil; H. Rajashekara; T. Prabhulinga; Babasaheb B. Fand; et al. (Crop Protection, 2024)

Hydrogeochemical Evaluation and Multivariate Statistical Analysis of Groundwater for Sustainable Groundwater Quality Management in the Industrial Corridor of Ranipet District, Tamil Nadu, India - Loganathan Krishnamoorthy; Vignesh Rajkumar Lakshmanan (Water, Air, & Soil Pollution, 2024)

Molecular analysis of opaque2 gene governing accumulation of lysine and tryptophan in maize endosperm - Gulab Chand; Vignesh Muthusamy; Rajkumar U. Zunjare; Subhra J. Mishra; Gaurav Sharma; Brijesh K. Mehta; Sohini Singh; Tanu Allen; Firoz Hossain (Euphytica, 2024)

A Comprehensive Review on Beneficial Effects of Foxtail Millet (Tiṉai) in Inflammatory Bowel Disease (Cōpai tōṭam) and its Progression to Colorectal Carcinogenesis (Kuṭal vippuruti) - Gayathri Gunalan; Rathinamala Rathinam; Shyamala Rajkumar; Lavanya Alagusolaiyan; Shunmugaram Shenbagaraj; Vinu Bharathi Balasubramaniam; Deepa Ravichandran; Saraswathi Balasubramanian; Siva Annamalai; Sakila Banu Abdul Rahim; Sathiyarajeswaran Parameswaran (Current Pharmacology Reports, 2024)

Toxic effects of dibutyl phthalate on testes of adult zebrafish: evaluation of oxidative stress parameters and histopathology - Swati S. Patel; Bhavesh J. Trangadia; Urvesh D. Patel; Rajkumar S. Delvadiya; Abdulkadir A. Makwana; Samir H. Raval; Dhaval T. Fefar (Environmental Science and Pollution Research, 2024)

In Silico Dose Adjustment of Zolpidem in Females Using Physiologically Based Pharmacokinetic Modeling and Simulations - Rajkumar Malayandi; Arka Karmakar; Pratik Dhake; Adarsh Malgave; Subramanian Natesan; Ravichandiran Velayutham (Sleep and Vigilance, 2024)

Unraveling molecular architecture, development and validation of Anthocyanin1 gene-based novel breeder-friendly markers for utilization in genomics-assisted breeding of blue maize - Gaurav Sharma; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Govinda Rai Sarma; Deepak R. Sapkal; Firoz Hossain (South African Journal of Botany, 2024)

Integrative genetic and molecular delineation of indeterminate gametophyte1 (ig1) gene governing paternal haploid induction in maize - Amitkumar D. Kyada; Rashmi Chhabra; Vignesh Muthusamy; Ravindra K. Kasana; Gaurav Sharma; Nisrita Gain; Jayanthi Madhavan; Rajkumar U. Zunjare; Firoz Hossain (South African Journal of Botany, 2024)

DeepNNet 15 for the prediction of biological waste to energy conversion and nutrient level detection in treated sewage water - T. Sathish; A. Vijayalakshmi; Raviteja Surakasi; N. Ahalya; M. Rajkumar; R. Saravanan; Sumarlin Shangdiar; Thandiwe Sithole; Kassian T.T. Amesho (Process Safety and Environmental Protection, 2024)

Insights into the population dynamics of phytophthora species associated with arecanut fruit rot disease - V.H. Prathibha; Balanagouda Patil; M.K. Rajesh; Sunil S Gangurde; M.N. Maruthi; K.P. Gangaraj; Thava Prakasa Pandian R; Daliyamol; M. Chaithra; Rajkumar; Vinayaka Hegde (Physiological and Molecular Plant Pathology, 2024)

Unraveling popping quality through insights on kernel physical, agro-morphological, and quality traits of diverse popcorn (Zea mays var. everta) inbreds from indigenous and exotic germplasm - Ikkurti Gopinath; Firoz Hossain; Selvakumar Thambiyannan; Neha Sharma; Hriipulou Duo; Ravindra K. Kasana; Ashvinkumar Katral; Rakesh Devlash; Sathya Sheela K.R. Veluchamy; Rajkumar U. Zunjare; Javaji C. Sekhar; Satish K. Guleria; et al. (Food Research International, 2024)

Distinct mechanisms are responsible for E. coli biofilm desorption upon T4 coliphage infection and nutrient deprivation - Tammy R. Johnson; Kennedi A. Armstrong; Bliss N. Broussard; Raj Boopathy; Rajkumar Nathaniel; John Doucet; Jonathan Willis; Himanshu S. Raje (Bioresource Technology Reports, 2024)

In vitro adventitious root culture system for optimal production of genistein in soybean (Glycine max L. Merrill) - Nandakumar Vidya; Krishnagowdu Saravanan; Rajkumar Vasanthkumar; Packiaraj Gurusaravanan; Ramalingam Radhakrishnan; Chinnaswamy Appunu; Muthukrishnan Arun (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Jamun Seed-Derived Nitrogen-Doped Carbon Dots: A Novel Microwave-Assisted Synthesis for Ultra-Bright Fluorescence and Mn7+ Detection - R. Swathi; G. Bhagavanth Reddy; Bandi Rajkumar; Dadigala Ramakrishna; P. Yadagiri Swamy (Journal of Fluorescence, 2024)

Effect of hybrid steel fibres on shear behaviour of self compacting RC beam - K. B. Ramkumar; C. Sudha; K. Gunasekaran; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2024)

Optimization of wet granulation process for manufacturing Rivaroxban generic immediate-release tablets using PBPK modeling and simulations - Jailani Shiekmydeen; Tanisha; Sonam Sharma; Kishor Chakraborty; Dhanapal Chidambaram Kannaiyan; Noohu Abdulla Khan; Rajkumar Malayandi (In Silico Pharmacology, 2024)

A Semi-Mechanistic Physiologically Based Biopharmaceutics Model to Describe Complex and Saturable Absorption of Metformin: Justification of Dissolution Specifications for Extended Release Formulation - Adithya Karthik Bhattiprolu; Sivacharan Kollipara; Rajkumar Boddu; Anand Arumugam; Sohel Mohammed Khan; Tausif Ahmed (AAPS PharmSciTech, 2024)

Lightning-related fatalities in India (1967–2020): a detailed overview of patterns and trends - Manoranjan Mishra; Tamoghna Acharyya; Rajkumar Guria; Nihar Ranjan Rout; Celso Augusto Guimarães Santos; Richarde Marques da Silva; Sanjay Srivastava; Ranjana Kumari; Alok Kumar Pradhan (Environment, Development and Sustainability, 2024)

New report of Pestalotiopsis microspora causing leaf blight disease in Eucalyptus (Eucalyptus camaldulensis L.) from India - Balanagouda Patil; C.T. Ganesh; Pavitra Kotari; Rajkumar Rathinavelu (Crop Protection, 2024)

Geomagnetically induced currents (GICs) during strong geomagnetic activity (storms, substorms, and magnetic pulsations) on 23–24 April 2023 - Irina Despirak; Pavel Setsko; Andris Lubchich; Rajkumar Hajra; Yaroslav Sakharov; Gurbax Lakhina; Vasiliy Selivanov; Bruce Tsatnam Tsurutani (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Study on cyclic behavior of concrete column steel beam connections - Madhu Paudel; C. Arunkumar; R. Rajkumar (Innovative Infrastructure Solutions, 2024)

Green biotherapeutics: overcoming challenges in plant-based expression platforms - Rishabh Rajkumar Jadhav; Deepa Khare (Plant Biotechnology Reports, 2024)

In vitro regeneration of cotton (Gossypium hirsutum L.) cultivar KC3 with controlled phenolic secretion by using Kappaphycus alvarezii sulfated polysaccharide extract and plant growth regulators - Packiaraj Gurusaravanan; Sathasivam Vinoth; Rajkumar Vasanthkumar; Muthukrishnan Arun; Muthukrishnan Saradhadevi; Subiramani Sivakumar; Narayanasamy Jayabalan (In Vitro Cellular & Developmental Biology - Plant, 2024)

Development of three-dimensional (3D) spheroid culture system from rainbow trout kidney cell line (RTK) for in vitro production of fish viral pathogen - S. Suryakodi; S. Mithra; A. Nafeez Ahmed; K. Kanimozhi; V. Rajkumar; G. Taju; S. Abdul Majeed; A. S. Sahul Hameed (Aquaculture International, 2024)

Assessment of groundwater quality using water quality index, multivariate statistical analysis and machine learning techniques in the vicinity of an open dumping yard - Arumugasamy Thangapandian Venkatesh; Sujatha Rajkumar; Uma Shankar Masilamani (Environment, Development and Sustainability, 2024)

Groundwater quality assessment using machine learning models: a comprehensive study on the industrial corridor of a semi-arid region - Loganathan Krishnamoorthy; Vignesh Rajkumar Lakshmanan (Environmental Science and Pollution Research, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Playing Hide-and-Seek with Tyrosine Kinase Inhibitors: Can We Overcome Administration Challenges? - Sivacharan Kollipara; Mahendra Chougule; Rajkumar Boddu; Ashima Bhatia; Tausif Ahmed (The AAPS Journal, 2024)

Information interaction and partial growth-based multi-population growable genetic algorithm for multi-dimensional resources utilization optimization of cloud computing - Guangyao Zhou; Yuanlun Xie; Haocheng Lan; WenHong Tian; Rajkumar Buyya; Kui Wu (Swarm and Evolutionary Computation, 2024)

Long-term tributyltin exposure alters behavior, oocyte maturation, and histomorphology of the ovary due to oxidative stress in adult zebrafish - Rajkumar S. Delvadiya; Urvesh D. Patel; Mihir R. Tank; Harshad B. Patel; Swati S. Patel; Bhavesh J. Trangadia (Reproductive Toxicology, 2024)

Synthesis of oxygen vacancies rich CeO2-xNx/GCN hybrid nanostructure with great active interfaces for electrochemical detection of antiviral levofloxacin in pharmaceutical samples - Chellakannu Rajkumar; Wan-Young Chung (Journal of Cleaner Production, 2024)

Enhanced productivity of nutrient-rich single cell protein from Paradendryphiella arenariae PG1 through valorization of agro-industrial waste: A Green symphony from Waste-to-Protein Approach - Priya Rajkumar Sagar; Gopalkumar G. Raol; Darshankumar Prajapati; Dhruv Kapdi; Bhavya Kiri (Bioresource Technology Reports, 2024)

Dynamic shoreline alterations and their impacts on Olive Ridley Turtle (Lepidochelys olivacea) nesting sites in Gahirmatha Marine Wildlife Sanctuary, Odisha (India) - Manoranjan Mishra; Saswati Pati; Suman Paul; Rodrigo Mikosz Gonçalves; Tamoghna Acharyya; Basudev Tripathy; Richarde Marques da Silva; Rajkumar Guria; Celso Augusto Guimarães Santos (Marine Pollution Bulletin, 2024)

Spatial analysis and machine learning prediction of forest fire susceptibility: a comprehensive approach for effective management and mitigation - Manoranjan Mishra; Rajkumar Guria; Biswaranjan Baraj; Ambika Prasad Nanda; Celso Augusto Guimarães Santos; Richarde Marques da Silva; FX Anjar Tri Laksono (Science of The Total Environment, 2024)

Zinc solubilization and organic acid production by the entomopathogenic fungus, Metarhizium pingshaense sheds light on its key ecological role in the environment - C.M. Senthil Kumar; Sharon D'Silva; R. Praveena; Anees Kaprakkaden; L.R. Athira Krishnan; M. Balaji Rajkumar; V. Srinivasan; R. Dinesh (Science of The Total Environment, 2024)

Unique genetic architecture of prolificacy in ‘Sikkim Primitive’ maize unraveled through whole-genome resequencing-based DNA polymorphism - Nitish Ranjan Prakash; Kuldeep Kumar; Vignesh Muthusamy; Rajkumar Uttamrao Zunjare; Firoz Hossain (Plant Cell Reports, 2024)

Allelic variation and haplotype diversity of Matrilineal (MTL) gene governing in vivo maternal haploid induction in maize - Suman Dutta; Rashmi Chhabra; Vignesh Muthusamy; Nisrita Gain; Rajkumar Subramani; Konsam Sarika; Elangbam L. Devi; Jayanthi Madhavan; Rajkumar U. Zunjare; Firoz Hossain (Physiology and Molecular Biology of Plants, 2024)

Studies on the concrete with composite cement and alccofine: from use of OPC towards low-carbon quaternary binder - B. Suresh; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2024)

Development and characterization of brain cell line from Trachinotus blochii and its application in virological and gene expression studies - A. Nafeez Ahmed; S. Mithra; S. Suryakodi; G. Taju; M. J. Abdul Wazith; K. Kanimozhi; V. Rajkumar; A. Badhusha; S. Abdul Majeed; A. S. Sahul Hameed (Journal of Fish Diseases, 2024)
A permanent cell line, SPB (Snubnose pompano brain) was established from Trachinotus blochii by the explant culture method. It has been sub‐cultured more than 75 passages and showed optimal growth at 28°C using L‐15 medium supplemented with 15% to 20% FBS. The SPB cells were cryopreserved at different passage levels for various applications. SPB cells were composed of fibroblastic and epithelial‐like cells. The SPB cells were tested for mycoplasma contamination which was found to be negative. The origin of the SPB cell line from T. blochii was confirmed by amplification of the mitochondrial cytochrome oxidase I (COI) gene. The transfection efficiency of SPB cell line is 15% assessed by expression of green fluorescent protein using pEGFP‐N1 plasmid. In addition, two CMV promotor plasmids pFNCPE42‐DNA and pcDNAVP28 were transfected to SPB cells and it shows high expression levels of FNCP of fish nodavirus and VP28 protein of white spot syndrome virus by immunostaining. The SPB cells showed susceptibility to SJNNV and the infection was confirmed by RT‐PCR, Western blot, ELISA, TCID 50 and RT‐qPCR. Experimental infection was carried out in T. blochii using SJNNV propagated in SPB cell line and found 100% mortality with clinical signs. The infection was confirmed by RT‐PCR. The SPB cell line can be used for propagation of fish viral pathogens and production of the recombinant proteins.

Oxidative desulfurization of fuels using alcohol-based DESs - Nisha Saini; Mansi Negi; Pooja Yadav; Rajkumar Singh (Environmental Science and Pollution Research, 2024)

Insights into zooxanthellae densities in corals Porites lutea and Pocillopora meandrina in Lakshadweep atolls - Sahab Nangammada; Rajkumar Rajan (Regional Studies in Marine Science, 2024)

Experimental investigation and optimization of dual fuel combustion using diesel/gasoline and Bio-oil extracted from Co-thermal liquefaction of paint/biomass wastes: An approach towards waste to energy - Balagurunathan Jayakishan; Sundararajan Rajkumar; G. Nagarajan (Journal of Cleaner Production, 2024)

Eco-friendly synthesis of palladium nanoparticles using Zaleya decandra: Assessing mosquito larvicidal activity, zebrafish embryo developmental toxicity, and impacts on freshwater sludge worm Tubifex tubifex - Selvam Naveenkumar; Chinnaperumal Kamaraj; Pradisha Prem; Ramalingam Karthik Raja; Arumugam Priyadharsan; Abdulwahed Fahad Alrefaei; Rasiravathanahalli Kaveriyappan Govindarajan; Rajkumar Thamarai; Vetriselvan Subramaniyan (Journal of Environmental Chemical Engineering, 2024)

Ecological and human health risk assessment of pharmaceutical compounds in the Sirsa River of Indian Himalayas - Arohi Dixit; Himanshu Pandey; Rajiv Rana; Anil Kumar; Rajkumar Herojeet; Renu Lata; Raj Mukhopadhyay; Santanu Mukherjee; Binoy Sarkar (Environmental Pollution, 2024)

Pseudomonas sp. AMGC1 takes on rice blast: Broad-spectrum antimicrobial activity underpins plant growth and disease tolerance. - Bibhas Rajkumar; Atifa Begum Mozumder; Joydeb Dey; Gauri Dutt Sharma; Saurabh Yadav; Himanshu Kishore Prasad (Biocatalysis and Agricultural Biotechnology, 2024)

Drone remote sensing of wheat N using hyperspectral sensor and machine learning - Rabi N. Sahoo; R. G. Rejith; Shalini Gakhar; Rajeev Ranjan; Mahesh C. Meena; Abir Dey; Joydeep Mukherjee; Rajkumar Dhakar; Abhishek Meena; Anchal Daas; Subhash Babu; Pravin K. Upadhyay; et al. (Precision Agriculture, 2024)

A comparative study on targeted gene expression in zebrafish and its gill cell line exposed to chlorpyrifos - Abdul Wazith M. J.; Taju G.; Abdul Majeed S.; Mithra S.; Nafeez Ahmed A.; Badhusha A.; Rajkumar V.; Sahul Hameed A. S. (In Vitro Cellular & Developmental Biology - Animal, 2024)

Evaluating hydrogeochemistry and heavy metal contamination of groundwater at Ranipet environs: employing multivariate statistics, agricultural indices, and health risk assessment - Loganathan Krishnamoorthy; Vignesh Rajkumar Lakshmanan (Environmental Science and Pollution Research, 2024)

Analysing the factors influencing groundwater quality with different pollution indices and PLS-SEM approach in the vicinity of an open dumping yard in Saduperi, Vellore, Tamil Nadu, India - Arumugasamy Thangapandian Venkatesh; Sujatha Rajkumar; Uma Shankar Masilamani (Environmental Science and Pollution Research, 2024)

A multi-temporal analysis of shoreline dynamics influenced by natural and anthropogenic factors: Erosion and accretion along the Digha Coast, West Bengal, India - Suman Paul; Manoranjan Mishra; Rajkumar Guria; Saswati Pati; Biswaranjan Baraj; Richarde Marques da Silva; Celso Augusto Guimarães Santos (Marine Pollution Bulletin, 2024)

Geo-ecological, shoreline dynamic, and flooding impacts of Cyclonic Storm Mocha: A geospatial analysis - Manoranjan Mishra; Rajkumar Guria; Suman Paul; Biswaranjan Baraj; Celso Augusto Guimarães Santos; Carlos Antonio Costa dos Santos; Richarde Marques da Silva (Science of The Total Environment, 2024)

Synergistic effect of biochar and plant growth promoting bacteria improve the growth and phytostabilization potential of Sorghum bicolor in Cd and Zn contaminated soils - Vadivel Anbuganesan; Ramasamy Vishnupradeep; Ninu Mehnaz; Adarsh Kumar; Helena Freitas; Mani Rajkumar (Rhizosphere, 2024)

Influence of shock waves on bifunctional nickel particles: Enhancing magnetic properties and supercapacitor applications - Arumugam Sonachalam; Rajkumar Sokkalingam; Devaraj Raja Giri; Abhishek Panghal; Susanta Sinha Roy; S.A. Martin Britto Dhas; Jagadeesh Ramadoss; Sasikala Ganapathy; Raghavendra Babu Baskaran; Jayavel Ramasamy (Environmental Research, 2024)

Whole genome sequencing of bacteriophage NINP13076 isolated against Salmonella enteritidis - R Naveen Kumar; Ashok Selvaraj; Tamilzhalagan Sembulingam; Virendra Panpatil; Kaliaperumal Venkatesh; S.D.G. Gowthami; Uday kumar Putchaa; Uma Devi Ranganathan; Hemalatha Rajkumar; Sudip Ghosh; Ramalingam Bethunaickan (Ecological Genetics and Genomics, 2024)

Polyester-based thin-film composite membranes for nanofiltration of saline water: A review - Shinyoung Park; Rajkumar Patel; Yun Chul Woo (Desalination, 2024)

Spatiotemporal analysis of lightning flash clusters and fatalities between 2000 and 2020 over West Bengal, India - Manoranjan Mishra; Rajkumar Guria; Tamoghna Acharyya; Umasankar Das; Celso Augusto Guimarães Santos; Richarde Marques da Silva; FX Anjar Tri Laksono; Ranjana Kumari (Natural Hazards, 2024)

Trends in Antarctic Snowmelt Onset for the Period 1988 to 2008 from Passive Microwave Data - Kamaljit Singh Rajkumar (Journal of the Indian Society of Remote Sensing, 2024)

Photovoltaic connected active switched boost quasi-Z-source (ASB-qZSI)–based multi-level inverter system using Q2OGEO approach - Rajkumar Anand; Ghanta Devadasu; Sankaramoorthy Muthubalaji (Environmental Science and Pollution Research, 2024)

Glucocorticoid receptor mediated sensitization of colon cancer to photodynamic therapy induced cell death - Ushasri Chilakamarthi; Namita S. Mahadik; Tithi Bhattacharyya; Palivela Siva Gangadhar; Lingamallu Giribabu; Rajkumar Banerjee (Journal of Photochemistry and Photobiology B: Biology, 2024)

A highly sensitive electrochemical sensor for Cr6+ ions detection using Ag NPs/rGO/quercetin modified glassy carbon electrode for water applications - G. Surendra Rajkumar; P. Senthil Kumar; Gayathri Rangasamy (Groundwater for Sustainable Development, 2024)

Metal Contamination of Different Water Categories and Surface Soil Near Thermal Power Plants at Varied Geographic Sites of India and Their Health Risk Assessment - Khaiwal Ravindra; Nitasha Vig; Neha Agarwal; Vivek Singh Malik; Elangovan Arumugam; Prabu Rajkumar; Elavarasu Govindasamy; Punita Kumar; Prabir Chatterjee; Ramachandra Kamath; Surekha R Kamath; Sharvanan E. Udayar; et al. (Water, Air, & Soil Pollution, 2024)

Effect of Pulsed Light Treatment for the Preservation of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; R. Pandiselvam; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; P. Preetha (Sugar Tech, 2024)

In vitro double haploid production through anther culture in niger (Guizotia abyssinica L.F. Cass) - Shrinkhla Maurya; Bhumika Sharma; Kajal Thakur; Suman Rawte; Nirmala Bharti Patel; Rajani Bisen; S. Rajkumar; Zenu Jha; M. Sujatha (In Vitro Cellular & Developmental Biology - Plant, 2024)

Agrosilvopastoral systems for improved crop and fodder productivity and soil health in the rainfed environments of South India - G. Venkatesh; K.A. Gopinath; D.B.V. Ramana; V. Visha Kumari; I. Srinivas; Arun K. Shanker; K.V. Rao; J.V.N.S. Prasad; K. Sammi Reddy; K.B. Sridhar; B. Sarkar; B.M.K. Raju; et al. (Agricultural Systems, 2024)

Anti-microbial efficacy of a scientifically developed and standardized herbal-alcohol sanitizer - Rajkumar Tulsawani; Kalyani Verma; Ekta Kohli; Purva Sharma; Yogesh Singh Meena; Amitabh; Sarkaraisamy Ponmariappan; Prashant Kumar; Rekha Maithani (Archives of Microbiology, 2024)

Synthesis, characterization, and evaluation of fluoride removal capacity of calcium-impregnated Euphorbia neriifolia carbon (Ca-Enc) - Rajkumar Subramanium; Ezhaveni Sathiyamoorthi; Saravanakumar Rajagopal; Rajavenkatesh Krishnamoorthy; Jintae Lee; Lakshman Kumar A (Environmental Science and Pollution Research, 2024)

Evaluation of overwash vulnerability and shoreline dynamics in cyclone-prone Sagar Island, Sundarbans (India) - Suman Paul; Manoranjan Mishra; Saswati Pati; Tamoghna Acharyya; Celso Augusto Guimarães Santos; Richarde Marques da Silva; Rajkumar Guria; FX Anjar Tri Laksono (Science of The Total Environment, 2024)

Nano-graphitic crystallites effect on the improved K-ion intercalation properties of Kigelia Africana fruit-derived hard carbon for potassium-ion batteries - N. Prasanna Naga Puneeth; K. Rajkumar; A. Soundarya; S.D. Kaushik; Yun Sung Lee; Sangho Park; R. Kalai Selvan (Chemical Engineering Journal, 2024)

Geomorphic evolution of the craton-derived Sone megafan in the southern Ganga plain, India: A tectono-climatic interplay - Aditya K Verma; Narendra K. Patel; Pitambar Pati; Manoj K. Jaiswal; Rajkumar Kashyap; Belligraham Narzary (CATENA, 2024)

Unveiling the Mechanisms Underpinning Alleviation of Mercury Toxicity by Static Magnetic Field Treatment in Soybean - Rajkumar Prajapati; Sunita Kataria; Rekha Gadre; Marco Landi; Meeta Jain (Journal of Plant Growth Regulation, 2024)

Remote sensing, GIS, and analytic hierarchy process-based delineation and sustainable management of potential groundwater zones: a case study of Jhargram district, West Bengal, India - Rajkumar Guria; Manoranjan Mishra; Surajit Dutta; Richarde Marques da Silva; Celso Augusto Guimarães Santos (Environmental Monitoring and Assessment, 2024)

Impact of THIONIL® on reducing water and soil micro-pollutant and enhancement of growth, survival, anti-vibrio, immunity and health indices of Litopenaeus vannamei in pond trial - Rajkumar Thamarai; Thiyagarajan Sivaprakasam; Chinnaperumal Kamaraj; Dhatchayani Harikrishnan; Jawahar sri Prakash Thiyagarajan; Shine Kadaikunnan; Jeyashree Swaminathan; Koteeswaran Mani; Rajkumar Prabhakaran; Vimal Sukumar; Kalidass Subramaniam (Environmental Monitoring and Assessment, 2024)

Humidity activated ultra-selective room temperature gas sensor based on W doped MoS2/RGO composites for trace level ammonia detection - S.P. Linto Sibi; M. Rajkumar; Mathankumar Manoharan; J. Mobika; V. Nithya Priya; R.T. Rajendra Kumar (Analytica Chimica Acta, 2024)

Dissolution Profiles Comparison Using Conventional and Bias Corrected and Accelerated f2 Bootstrap Approaches with Different Software’s: Impact of Variability, Sample Size and Number of Bootstraps - Rajkumar Boddu; Sivacharan Kollipara; Adithya Karthik Bhattiprolu; Karthik Parsa; Sanketh Kumar Chakilam; Krishna Reddy Daka; Ashima Bhatia; Tausif Ahmed (AAPS PharmSciTech, 2023)

Chitosan/PLA-loaded Magnesium oxide nanocomposite to attenuate oxidative stress, neuroinflammation and neurotoxicity in rat models of Alzheimer's disease - Manickam Rajkumar; Prabha Govindaraj; Karuppaiya Vimala; Ramasundaram Thangaraj; Soundarapandian Kannan (Metabolic Brain Disease, 2023)

Advances in drying techniques for retention of antioxidants in agro produces - V. A. Athira; E. Gokulvel; A. M. Nandhu Lal; V. V. Venugopalan; Rajkumar; T. Venkatesh (Critical Reviews in Food Science and Nutrition, 2023)

Reproductive biology of green tiger shrimp Penaeus semisulcatus De Haan, 1844 in Palk Bay, southeast coast of India - M. Rajkumar; S. Lakshmi Pillai; P. Rameshkumar; R. Saravanan; S. Thirumalaiselvan; Josileen Jose; K.S. Sobhana; M. Rosalind George (Regional Studies in Marine Science, 2023)

Surface roughness from in-situ measurements around Indian Antarctic stations - Megha Maheshwari; Kamaljit Singh Rajkumar; Jayaprasad Pallipad; Dhani Ram Rajak; Sandip Rashmikant Oza; Raj Kumar (Polar Science, 2023)

Does the peroral chromium administration in young Hariana calves reduce the risk of calf diarrhea by ameliorating insulin response, lactose intolerance, antioxidant status, and immune response? - Muneendra Kumar; Vinod Kumar; Yajuvendra Singh; Ashish Srivastava; Raju Kushwaha; Shalini Vaswani; Avinash Kumar; Shivam Khare; Brijesh Yadav; Rajkumar Yadav; Rajneesh Sirohi; Pankaj Kumar Shukla (Journal of Trace Elements in Medicine and Biology, 2023)

The Great Boundary Fault in the Indo-Gangetic foreland basin: A geomorphological perspective - Rajkumar Kashyap; Manoj K. Jaiswal; Pitambar Pati (Geomorphology, 2023)

A critical review of the recent trends in source tracing of microplastics in the environment - Kiruthika Mohan; Vignesh Rajkumar Lakshmanan (Environmental Research, 2023)

Transcriptome changes in shoot meristems of MUSA during different stages of cryopreservation - Chaw Su Su Htwe; Subramani Rajkumar; Pooja Pathania; Anuradha Agrawal (Cryobiology, 2023)

Tracking post-storage apple age with polarized light measurements - Damenraj Rajkumar; Rainer Künnemeyer; Jevon Longdell; Andrew McGlone (Postharvest Biology and Technology, 2023)

Antibacterial and biodegradable food packaging film from bacterial cellulose - Eun Jo Jang; Bandana Padhan; Madhumita Patel; Jitendra Kumar Pandey; Baojun Xu; Rajkumar Patel (Food Control, 2023)

Low expression of lipoxygenase 3 (LOX3) enhances the retention of kernel tocopherols in maize during storage - Shalma Maman; Vignesh Muthusamy; Ashvinkumar Katral; Rashmi Chhabra; Nisrita Gain; Shashidhar Bayappa Reddappa; Suman Dutta; Amolkumar Uddhaorao Solanke; Rajkumar Uttamrao Zunjare; Chirravuri Naga Neeraja; Devendra Kumar Yadava; Firoz Hossain (Molecular Biology Reports, 2023)

Application of green-synthesized cadmium oxide nanofibers and cadmium oxide/graphene nanosheet nanocomposites as alternative and efficient photocatalysts for methylene blue removal from aqueous matrix - Sundararajan Ashok Kumar; Daniel Rani Rosaline; Edson Luiz Foletto; Guilherme Luiz Dotto; Savariroyan Stephen Rajkumar Inbanathan; Gopalan Muralidharan (Environmental Science and Pollution Research, 2023)

Exploring the synergistic potential of higher alcohols and biodiesel in blended and dual fuel combustion modes in diesel engines: A comprehensive review - M. Gowthama Krishnan; Sundararajan Rajkumar; Jeyaseelan Thangaraja; Yuvarajan Devarajan (Sustainable Chemistry and Pharmacy, 2023)

A remarkable oxygen vacancy-rich rare earth aerogel with high activity towards electro and catalytic reduction of 5-nitroquinoline - Ramya Ramkumar; Chellakannu Rajkumar; Heeyeon Do; Haekyoung Kim; Woo Kyoung Kim (Journal of Cleaner Production, 2023)

Fabrication and characterisation of polycaprolactone/gelatin/chitosan (PCL/GEL/CHI) electrospun nano-membranes for wastewater purification - M.S. Baburaj; Midhu George Veeran; Diksha Painuly; S. Sreelekshmi; R.J. Rajkumar; Abi Santhosh Aprem (Desalination, 2023)

Voglibose attenuates cognitive impairment, Aβ aggregation, oxidative stress, and neuroinflammation in streptozotocin-induced Alzheimer’s disease rat model - Manickam Rajkumar; Soundarapandian Kannan; Ramasundaram Thangaraj (Inflammopharmacology, 2023)

Seen from the Stakeholder’s revelation — valuation of ecosystem services in a small tropical Indian estuary - Sreekanth Giri Bhavan; Shripad Bhat; Sajiya Mujawar; Praveen Koovalamkadu Velayudhan; Trivesh Mayekar; Amit Patil; Dhanya Mohan Lal; Gayatri Naik; Baban Ingole; Solomon Rajkumar; Parveen Kumar (Regional Studies in Marine Science, 2023)

Textile effluents decolourization potential of metal tolerant Aspergillus species and optimization of biomass concentration and temperature - Tan Phat Chau; R. Rajkumar; Abeer S Aloufi; Ramakrishnan Krishnan; Shan Ahamed Tharifkhan (Environmental Research, 2023)

Transcriptomic analysis reveals novel age-independent immunomodulatory proteins as a mode of cerebroprotection in P2X4 receptor knockout mice after ischemic stroke - Daylin Gamiotea-Turro; Chunxia C Cronin; Bruce T Liang; Rajkumar Verma (Purinergic Signalling, 2023)

Enhancement of nutritional quality in maize kernel through marker-assisted breeding for vte4, crtRB1, and opaque2 genes - Firoz Hossain; Sunil K. Jaiswal; Vignesh Muthusamy; Rajkumar U. Zunjare; Subhra J. Mishra; Gulab Chand; Vinay Bhatt; Jayant S. Bhat; Abhijit K. Das; Hema S. Chauhan; Hari S. Gupta (Journal of Applied Genetics, 2023)

Development of novel gene-based markers for waxy1 gene and their validation for exploitation in molecular breeding for enhancement of amylopectin in maize - Zahirul Alam Talukder; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Firoz Hossain (Journal of Applied Genetics, 2023)

Improvement in electrical energy efficiency of solar photovoltaic panel by passive refrigeration cooling system - M. Chandrasekar; S. Rajkumar; M. Varatharajulu (International Journal of Energy and Water Resources, 2023)

Nanoparticle-mediated cancer cell therapy: basic science to clinical applications - Jaya Verma; Caaisha Warsame; Rajkumar Kottayasamy Seenivasagam; Nirmal Kumar Katiyar; Eiman Aleem; Saurav Goel (Cancer and Metastasis Reviews, 2023)
Every sixth person in the world dies due to cancer, making it the second leading severe cause of death after cardiovascular diseases. According to WHO, cancer claimed nearly 10 million deaths in 2020. The most common types of cancers reported have been breast (lung, colon and rectum, prostate cases), skin (non-melanoma) and stomach. In addition to surgery, the most widely used traditional types of anti-cancer treatment are radio- and chemotherapy. However, these do not distinguish between normal and malignant cells. Additional treatment methods have evolved over time for early detection and targeted therapy of cancer. However, each method has its limitations and the associated treatment costs are quite high with adverse effects on the quality of life of patients. Use of individual atoms or a cluster of atoms (nanoparticles) can cause a paradigm shift by virtue of providing point of sight sensing and diagnosis of cancer. Nanoparticles (1–100 nm in size) are 1000 times smaller in size than the human cell and endowed with safer relocation capability to attack mechanically and chemically at a precise location which is one avenue that can be used to destroy cancer cells precisely. This review summarises the extant understanding and the work done in this area to pave the way for physicians to accelerate the use of hybrid mode of treatments by leveraging the use of various nanoparticles.

A Review on Pyrolysis of Agro-waste and Plastic Waste into Biofuels: Shifting to Bio-based Economy - Midhun Prasad K; Murugavelh Somasundaram; B Anand; R Shankar; Rajkumar P (BioEnergy Research, 2023)

Analysis of bio-optical active constituents for lentic ecosystem through spectral-spatial and in-vitro observation - Sri Vishnu Prasanth Balachandran Rajkumar; Ramamoorthy Sivakumar (Environmental Science and Pollution Research, 2023)

An appraisal of trace element concentration and environmental risk of sediments: a baseline study of sediments from Arasalar River Estuary, Tamil Nadu, India - Venkatesan Selvaraj; Parthasarathy Pandu; Singarasubramanian Ramachandran Saradhambal; Rajmohan Sankarappan; Rajkumar Anandarao (Environmental Science and Pollution Research, 2023)

Meta-QTL analysis and identification of candidate genes governing popping quality attributes in maize - Ikkurti Gopinath; Vignesh Muthusamy; Ashvinkumar Katral; Rajkumar U. Zunjare; Jayanthi Madhavan; Kondajji Rangappa Yathish; Javaji C. Sekhar; Firoz Hossain (South African Journal of Botany, 2023)

Identifying optimum residue levels for stable crop and water productivity and carbon sequestration under a conservation agriculture based rice-wheat system - Ram Swaroop Bana; Shanti Devi Bamboriya; Vipin Kumar; Samarth Godara; Donald S. Gaydon; Alison M. Laing; Rajkumar Dhakar; Y.S. Shivay; Vijay Singh Meena; Deepak Singh (Soil and Tillage Research, 2023)

Bioremediation efficiency of free and immobilized form of Aspergillus niger and Aspergillus tubigenesis biomass on tannery effluent - Tan Phat Chau; Laura Bulgariu; Mythili Saravanan; R. Rajkumar; Arunachalam Chinnathambi; Saleh H. Salmen; G.K. Jhanani (Environmental Research, 2023)

Interface and doping engineering of Co-based electrocatalysts for enhanced oxygen reduction and evolution reactions - Fangfang Fan; Qiulan Huang; Karuppasamy Kohila Rani; Xinglan Peng; Xiaotian Liu; Limin Wang; Zhongyun Yang; Dujuan Huang; Rajkumar Devasenathipathy; Du-Hong Chen; Youjun Fan; Wei Chen (Chemical Engineering Journal, 2023)

Evaluation of Effect of Tapping Frequency and Lime Coating on the Biochemical Changes and Fermentation Rate of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; R. Pandiselvam (Sugar Tech, 2023)

Performance evaluation of CMIP6 climate models for selecting a suitable GCM for future precipitation at different places of Tamil Nadu - Hemanandhini S; Vignesh Rajkumar L (Environmental Monitoring and Assessment, 2023)

Earth’s magnetotail variability during supersubstorms (SSSs): A study on solar wind–magnetosphere–ionosphere coupling - Rajkumar Hajra; Ezequiel Echer; Adriane Marques de Souza Franco; Mauricio José Alves Bolzan (Advances in Space Research, 2023)

Biopharmaceutics Risk Assessment—Connecting Critical Bioavailability Attributes with In Vitro, In Vivo Properties and Physiologically Based Biopharmaceutics Modeling to Enable Generic Regulatory Submissions - Tausif Ahmed; Sivacharan Kollipara; Rajkumar Boddu; Adithya Karthik Bhattiprolu (The AAPS Journal, 2023)

Plants, animals, and fisheries waste-mediated bioremediation of contaminants of environmental and emerging concern (CEECs)—a circular bioresource utilization approach - Kishore Kumar Krishnani; Veera Mallu Boddu; Rajkumar Debarjeet Singh; Puja Chakraborty; Ajit Kumar Verma; Lance Brooks; Himanshu Pathak (Environmental Science and Pollution Research, 2023)

Formation damage and improved recovery in kaolinitic high enthalpy gas fields with fabric geological settings - B. Kanimozhi; P. Rajkumar; S. Mahalingam; S. Senthil; D.S. Jayalakshmi; H. Girija Bai; Vivek Thamizhmani; Ramadoss Kesavakumar; Venkat Pranesh (Gas Science and Engineering, 2023)

Effect of packaging materials and storage temperature on the physicochemical and microbial properties of ultrasonicated mature coconut water during storage - Anjitha Jacob; I.P. Sudagar; R. Pandiselvam; P. Rajkumar; M. Rajavel (Food Control, 2023)

A novel technique of schedule tracker for parabolic dish concentrator - Rajkumar Malviya; Akash Patel; Ayush Singh; Santosh Jagadev; Prashant Baredar; Anil Kumar (Environmental Science and Pollution Research, 2023)

Enhanced quality control procedure for in-situ timeseries of marine-meteorological data - Nunna Kameshwari; TVS Udayabhaskar; Krishna Kishore Osuri; Rajkumar Lakkimsetty; Rama Rao E. Pattabhi (Dynamics of Atmospheres and Oceans, 2023)

A Nationwide Analysis of Aneurysmal Subarachnoid Hemorrhage Mortality, Complications, and Health Economics in the USA - Lefko T. Charalambous; Syed M. Adil; Shashank Rajkumar; Robert Gramer; Elayna Kirsch; Beiyu Liu; Ali Zomorodi; Mark McClellan; Shivanand P. Lad (Translational Stroke Research, 2023)

Identification of Location-Specific Male and Female Sugarcane Parents and Formulation of Breeding Strategies - Rajaprakasam Sudhagar; Shanmugam Rajkumar; Kandhasamy Ramachandiran; Naaganoor Ananthan Saravanan (Sugar Tech, 2023)

Provitamin A, lysine and tryptophan enrichment in shrunken2-based sweet corn genotypes through genomics-assisted breeding for crtRB1 and opaque2 genes - Bhavna Singh; Rajkumar U. Zunjare; Smriti Shrivastava; Gulab Chand; Nisrita Gain; Vinay Bhatt; Vignesh Muthusamy; Firoz Hossain (Molecular Biology Reports, 2023)

Radiation Oncology Virtual Education Rotation (ROVER) 2.0 for Residents: Implementation and Outcomes - Navjot K. Sandhu; Elham Rahimy; Ryan Hutten; Utkarsh Shukla; Anne Rajkumar-Calkins; Jacob A. Miller; Rie Von Eyben; Christopher R. Deig; Jean-Pierre Obeid; Rachel B. Jimenez; Emma C. Fields; Erqi L. Pollom; et al. (Journal of Cancer Education, 2023)

Dietary Chromium Picolinate Supplementation Improves Glucose Utilization in Transition Calf by Ameliorating Insulin Response - Shivam Khare; Muneendra Kumar; Vinod Kumar; Raju Kushwaha; Shalini Vaswani; Avinash Kumar; Rajkumar Singh Yadav; Shanker Kumar Singh; Yajuvendra Singh; Pankaj Kumar Shukla (Biological Trace Element Research, 2023)

Spatio-temporal patterns in the distribution of juvenile elasmobranchs in a tropical Indian Ocean estuary, Zuari- India - Sreekanth Giri Bhavan; Kiranya Bella; Akhilesh KV; Trivesh Mayekar; Chandrasekar Vasudevan; Solomon Rajkumar; Parveen Kumar (Marine Biodiversity, 2023)

Alpha-ketoglutarate supplementation and BiologicaL agE in middle-aged adults (ABLE)—intervention study protocol - Elena Sandalova; Jorming Goh; Zi Xiang Lim; Zhi Meng Lim; Diogo Barardo; Rajkumar Dorajoo; Brian K. Kennedy; Andrea B. Maier (GeroScience, 2023)
Targeting molecular processes of aging will enable people to live healthier and longer lives by preventing age-related diseases. Geroprotectors are compounds with the potential to increase healthspan and lifespan. Even though many of them have been tested in animal models, the translation to humans is limited. Alpha-Ketoglutarate (AKG) has been studied widely in model animals, but there are few studies testing its geroprotective properties in humans. ABLE is a double blinded placebo-controlled randomized trial (RCT) of 1 g sustained release Ca-AKG versus placebo for 6 months of intervention and 3 months follow up including 120 40–60-year-old healthy individuals with a higher DNA methylation age compared to their chronological age. The primary outcome is the decrease in DNA methylation age from baseline to the end of the intervention. A total of 120 participants will be randomized to receive either sustained release Ca-AKG or placebo. Secondary outcomes include changes in the inflammatory and metabolic parameters in blood, handgrip strength and leg extension strength, arterial stiffness, skin autofluorescence, and aerobic capacity from baseline to 3 months, 6 months, and 9 months. This study will recruit middle-aged participants with an older DNA methylation age compared to their chronological age, and test whether supplementation with Ca-AKG can reduce DNA methylation age. This study is unique in its inclusion of biologically older participants.

Morphological and microsatellite marker-based characterization and diversity analysis of novel vegetable soybean [Glycine max (L.) Merrill] - Priya Pardeshi; Pravin Jadhav; Sanjay Sakhare; Rajkumar Zunjare; Darasing Rathod; Priti Sonkamble; Ranjit Saroj; Philips Varghese (Molecular Biology Reports, 2023)

Cultivation of a marine diatom, Amphora sp., in municipal wastewater for enhancing lipid production toward sustainable biofuel production - Anandapadmanaban Baala Harini; Naduvil Veettil Sarangi; Natarajan Nisha; Renganathan Rajkumar (South African Journal of Botany, 2023)

Combined experimental and DFT investigation of temozolomide sensing properties of 2D− 2D interface of rich oxygen vacancies of WO3−x and sulfur-doped g-C3N4 nanosheets hybrids composites - Chellakannu Rajkumar; Pitchaimani Veerakumar; Pratap Mane; Haekyoung Kim; Brahmananda Chakraborty (Journal of Environmental Chemical Engineering, 2023)

Geological evolution of the Proterozoic Betul belt (∼2.16–0.95 Ga) of the Central Indian tectonic Zone: Its linkage to the assembly and dispersal of Columbia and Rodinia supercontinents - M. Lachhana Dora; Tushar Meshram; Srinivasa Rao Baswani; Vivek P Malviya; Dewashish Upadhyay; Mohd Shareef; Mohd Atif Raza; Sameer Ranjan; Rajkumar Meshram; Monaj Kumar Patnaik; Kirtikumar Randive (Gondwana Research, 2023)

Dual fuel combustion of 1-hexanol with diesel and biodiesel fuels in a diesel engine: An experimental investigation and multi criteria optimization using artificial neural network and TOPSIS algorithm - T. Anandavelu; Sundararajan Rajkumar; Vinoth Thangarasu (Fuel, 2023)

Federated Analysis in COINSTAC Reveals Functional Network Connectivity and Spectral Links to Smoking and Alcohol Consumption in Nearly 2,000 Adolescent Brains - Harshvardhan Gazula; Kelly Rootes-Murdy; Bharath Holla; Sunitha Basodi; Zuo Zhang; Eric Verner; Ross Kelly; Pratima Murthy; Amit Chakrabarti; Debasish Basu; Subodh Bhagyalakshmi Nanjayya; Rajkumar Lenin Singh; et al. (Neuroinformatics, 2023)

Differential expression of m5C RNA methyltransferase genes NSUN6 and NSUN7 in Alzheimer’s disease and traumatic brain injury - Adriana PerezGrovas-Saltijeral; Anto P. Rajkumar; Helen Miranda Knight (Molecular Neurobiology, 2023)
Epigenetic processes have become increasingly relevant in understanding disease-modifying mechanisms. 5-Methylcytosine methylations of DNA (5mC) and RNA (m 5 C) have functional transcriptional and RNA translational consequences and are tightly regulated by writer, reader and eraser effector proteins. To investigate the involvement of 5mC/5hmC and m 5 C effector proteins contributing to the development of dementia neuropathology, RNA sequencing data of 31 effector proteins across four brain regions was examined in 56 aged non-affected and 51 Alzheimer’s disease (AD) individuals obtained from the Aging, Dementia and Traumatic Brain Injury Study. Gene expression profiles were compared between AD and controls, between neuropathological Braak and CERAD scores and in individuals with a history of traumatic brain injury (TBI). We found an increase in the DNA methylation writers DNMT1 , DNMT3A and DNMT3B messenger RNA (mRNA) and a decrease in the reader UHRF1 mRNA in AD samples across three brain regions whilst the DNA erasers GADD45B and AICDA showed changes in mRNA abundance within neuropathological load groupings. RNA methylation writers NSUN6 and NSUN7 showed significant expression differences with AD and, along with the reader ALYREF , differences in expression for neuropathologic ranking. A history of TBI was associated with a significant increase in the DNA readers ZBTB4 and MeCP2 ( p < 0.05) and a decrease in NSUN6 ( p < 0.001) mRNA. These findings implicate regulation of protein pathways disrupted in AD and TBI via multiple pre- and post-transcriptional mechanisms including potentially acting upon transfer RNAs, enhancer RNAs as well as nuclear-cytoplasmic shuttling and cytoplasmic translational control. The targeting of such processes provides new therapeutic avenues for neurodegenerative brain conditions. Graphical abstract

Mechanical properties and bond behaviour of steel rebar and fly ash–slag based geopolymer concrete in pull-out test - T. Srividya; P. R. Kannan Rajkumar (Innovative Infrastructure Solutions, 2023)

Predicting habitat suitability of Litsea glutinosa: a declining tree species, under the current and future climate change scenarios in India - Rajit Gupta; Laxmi Kant Sharma; Muthu Rajkumar; Naseer Mohammad; Mohammed Latif Khan (Landscape and Ecological Engineering, 2023)

Electronic sensitization enhanced p-type ammonia gas sensing of zinc doped MoS2/RGO composites - S.P. Linto Sibi; M. Rajkumar; Kamaraj Govindharaj; J. Mobika; V. Nithya Priya; R.T. Rajendra Kumar (Analytica Chimica Acta, 2023)

Study of Neptune dayside magnetosheath fluctuations during Voyager-2 flyby - Ezequiel Echer; Adriane Marques de Souza Franco; Fabíola Pinho Magalhães; Mauricio J.A. Bolzan; Rajkumar Hajra (Advances in Space Research, 2023)

Remarkable photocatalytic performances towards pollutant degradation under sunlight and enhanced electrochemical properties of TiO2/polymer nanohybrids - Mariadhas Jarvin; Daniel Rani Rosaline; Thamizharasan Gopalakrishnan; Maniveldoss Beaula Ruby Kamalam; Edson Luiz Foletto; Guilherme Luiz Dotto; Savariroyan Stephen Rajkumar Inbanathan (Environmental Science and Pollution Research, 2023)

Antibacterial activity of essential oils from different parts of plants against Salmonella and Listeria spp. - Maninder Meenu; Bandana Padhan; Madhumita Patel; Rajkumar Patel; Baojun Xu (Food Chemistry, 2023)

Variation in anthocyanin pigmentation by R1-navajo gene, development and validation of breeder-friendly markers specific to C1-Inhibitor locus for in-vivo haploid production in maize - Nisrita Gain; Rashmi Chhabra; Shivani Chandra; Rajkumar U. Zunjare; Suman Dutta; Gulab Chand; Konsam Sarika; Elangbam L. Devi; Aruna Kumar; Jayanthi Madhavan; Vignesh Muthusamy; Firoz Hossain (Molecular Biology Reports, 2023)

Characterization of the Multiple Domains of Pex30 Involved in Subcellular Localization of the Protein and Regulation of Peroxisome Number - Nayan Moni Deori; Terence Infant; Rajkumar P. Thummer; Shirisha Nagotu (Cell Biochemistry and Biophysics, 2023)

Best Practices for Integration of Dissolution Data into Physiologically Based Biopharmaceutics Models (PBBM): A Biopharmaceutics Modeling Scientist Perspective - Sivacharan Kollipara; Adithya Karthik Bhattiprolu; Rajkumar Boddu; Tausif Ahmed; Siddharth Chachad (AAPS PharmSciTech, 2023)

A machine learning framework for evaluating the biodiesel properties for accurate modeling of spray and combustion processes - J. Thangaraja; Lars Zigan; Sundararajan Rajkumar (Fuel, 2023)

Expression of PKM2 in wound keratinocytes is coupled to angiogenesis during skin repair in vivo and in HaCaT keratinocytes in vitro - Khrystyna Sych; Simon P. Nold; Josef Pfeilschifter; Rajkumar Vutukuri; Jana Meisterknecht; Ilka Wittig; Stefan Frank; Itamar Goren (Journal of Molecular Medicine, 2023)
An injured skin is rapidly restored in a manner of wound healing. We have previously shown that intact insulin signaling and glucose uptake are fundamental to proper wound closure. Consequently, under exacerbated inflammation, compromised insulin action and glucose uptake lead to impaired healing. However, in spite of the increased attention to cell metabolism during tissue regeneration, metabolic mediators that govern cellular and physiological processes throughout skin repair remained largely elusive. Through assessment of mRNA using real-time PCR and protein blot analysis, we report that healing of cutaneous wounds comprise a boosted expression of genes involved in glycolysis, oxidative phosphorylation, pentose phosphate shunt, and glutamine anaplerosis. We further focused on the functional role of pyruvate kinase M (PKM) isoenzymes that catalyze the final and rate-limiting step of glycolysis. Whereas the expression of the metabolic constitutively active Pkm1 isozyme remained almost unchanged, Pkm2 is augmented during the inflammatory phase of healing. The immunohistochemistry and RNA in situ hybridization analysis showed a confined Pkm2 expression to keratinocytes of the hyperproliferative epithelium and, to a lesser extent, infiltrating neutrophils and monocytes as well as later on in macrophages. Notably, the expression of Pkm2 in keratinocytes facing the wound bed side colocalized with VEGF expression. The in vitro knockdown of PKM2 in HaCaT keratinocytes using small interfering (si) RNA confirmed an acute role for PKM2 in facilitating the complete induction of VEGF mRNA and protein expression in keratinocytes; this function is mainly HIF-1α independent. Key messages • Wound healing involves activation of glycolysis, oxidative phosphorylation, pentos-phosphate shunt, and replenishment of tri-carboxylic acid (TCA) cycle through glutamine anaplerosis. • The pyruvate kinase M2 (PKM2) isoform is upregulated during the inflammatory phase of cutaneous healing, mainly in keratinocytes of hyperproliferative epithelia. • In vivo, the expression of VEGF in wound keratinocytes is colocalized with PKM2. • PKM2 is required for full induction of VEGF in HaCaT keratinocytes in vitro.

Correction to: Accumulation, Chronicity, and Induction of Oxidative Stress Regulating Genes Through Allium cepa L. Functionalized Silver Nanoparticles in Freshwater Common Carp (Cyprinus carpio) - Krishnasamy Sekar Rajkumar; Ramkumar Arunachalam; Murugadas Anbazhagan; Sivagaami Palaniyappan; Srinivasan Veeran; Arun Sridhar; Thirumurugan Ramasamy (Biological Trace Element Research, 2023)

Accumulation, Chronicity, and Induction of Oxidative Stress Regulating Genes Through Allium cepa L. Functionalized Silver Nanoparticles in Freshwater Common Carp (Cyprinus carpio) - Rajkumar Krishnasamy Sekar; Ramkumar Arunachalam; Murugadas Anbazhagan; Sivagaami Palaniyappan; Srinivasan Veeran; Arun Sridhar; Thirumurugan Ramasamy (Biological Trace Element Research, 2023)

Constructing Z-scheme g-C3N4/TiO2 heterostructure for promoting degradation of the hazardous dye pollutants - M. Vijayan; Velu Manikandan; Chellakannu Rajkumar; Ashraf Atef Hatamleh; Bassam Khalid Alnafisi; G. Easwaran; Xinghui Liu; K. Sivakumar; Haekyoung Kim (Chemosphere, 2023)

Developing a numerical model to analyze the production process of PMEDM - G. Rajkumar; M. Saravanan; P. Marimuthu (Resources Policy, 2023)

Potentiation of novel porphyrin based photodynamic therapy against colon cancer with low dose doxorubicin and elucidating the molecular signalling pathways responsible for relapse - Ushasri Chilakamarthi; Namita S. Mahadik; Devulapally Koteshwar; Narra Vamsi Krishna; Lingamallu Giribabu; Rajkumar Banerjee (Journal of Photochemistry and Photobiology B: Biology, 2023)

High doses of nano-polystyrene aggravate the oxidative stress, DNA damage, and the cell death in onions - Sukhendu Maity; Rajkumar Guchhait; Sukanta De; Kousik Pramanick (Environmental Pollution, 2023)

A comparative study on geoeffective and non-geoeffective corotating interaction regions - Jibin V. Sunny; Archana Giri Nair; Megha Babu; Rajkumar Hajra (Advances in Space Research, 2023)

A Comprehensive Review on the Role of ZSCAN4 in Embryonic Development, Stem Cells, and Cancer - Madhuri Thool; Pradeep Kumar Sundaravadivelu; S. Sudhagar; Rajkumar P. Thummer (Stem Cell Reviews and Reports, 2022)

Correction to: Pollen staining is a rapid and cost‑effective alternative to marker‑assisted selection for recessive waxy1 gene governing high amylopectin in maize - Zahirul A. Talukder; Vignesh Muthusamy; Rajkumar U. Zunjare; Rashmi Chhabra; Shashidhar B. Reddappa; Subhra J. Mishra; Nitish R. Prakash; Nisrita Gain; Gulab Chand; Firoz Hossain (Physiology and Molecular Biology of Plants, 2022)

Characterization of crtRB1- and vte4-based biofortified sweet corn inbreds for seed vigour and physico-biochemical traits - Hema S. Chauhan; Vignesh Muthusamy; Tuhin Rashmi; Sudipta Basu; Anjali Anand; Brijesh K. Mehta; Nisrita Gain; Rajkumar U. Zunjare; Ashok K. Singh; Hari S. Gupta; Firoz Hossain (Journal of Applied Genetics, 2022)

Effect of mineral admixtures on mechanical and thermal properties of geopolymer mortar at elevated temperature - J. Baskara Sundararaj; P. R. Kannan Rajkumar; M. Sivasakthi; M. Jegan (Innovative Infrastructure Solutions, 2022)

Analysis of temperature distribution over pipe surfaces of air-based cavity linear receiver for cross-linear concentration solar power system - Akash Patel; Archana Soni; Prashant Baredar; Rajkumar Malviya (Environmental Science and Pollution Research, 2022)

Genome-wide analysis suggests the potential role of lncRNAs during seed development and seed size/weight determination in chickpea - Niraj Khemka; Mohan Singh Rajkumar; Rohini Garg; Mukesh Jain (Planta, 2022)

CRISPR and iPSCs: Recent Developments and Future Perspectives in Neurodegenerative Disease Modelling, Research, and Therapeutics - Tirthankar Sen; Rajkumar P. Thummer (Neurotoxicity Research, 2022)

Determination of focal depths of moderate earthquakes in Northeast Indian region using depth phase sPn - Rajkumar; Sanjay K. Prajapati; Sanjit K. Pal; H. N. Srivastava (Natural Hazards, 2022)

Mitochondrial ribosomal small subunit (MRPS) MRPS23 protein–protein interaction reveals phosphorylation by CDK11-p58 affecting cell proliferation and knockdown of MRPS23 sensitizes breast cancer cells to CDK1 inhibitors - Revathi Paramasivam Oviya; Krishna Priya Thangaretnam; Balaji Ramachandran; Priya Ramanathan; Subramani Jayavelu; Gopisetty Gopal; Thangarajan Rajkumar (Molecular Biology Reports, 2022)

Combined geospatial, geophysical and hydrochemical studies on coastal aquifer at Muttom–Mandaikadu area, Tamilnadu, India - Rajkumar Stanly; Srinivas Yasala; Nithya C. Nair; Arunbose Subash (Environmental Science and Pollution Research, 2022)

Anti-lung cancer properties of cyanobacterial bioactive compounds - Mirza S. Baig; Sajjan Rajpoot; Tomokazu Ohishi; Rajkumar Savai; Sascha Seidel; Nina A. Kamennaya; Evgeny E. Bezsonov; Alexander N. Orekhov; Pratik Mahajan; Kundan Solanki; Uzma Saqib (Archives of Microbiology, 2022)

Economic feasibility of subsurface drainage (SSD) to control waterlogging and soil salinity under different scenarios in the Tungabhadra project command, Karnataka, India - Karegoudar A V; Vishwanath J; Rajkumar R H; Anand S R; Polisgowdar B S; Ayyanagowdar M S; Nemichandrapp M; Kaledhonkar M J (Irrigation and Drainage, 2022)
The Tungabhadra irrigation command area (TBP) in Karnataka, India, has three scenarios: the head, mid and tail reach command areas. The head reach has ample good quality canal water availability, and the mid reach area has limited canal water availability. In recent decades, rice–rice monocropping in vertisols, especially by these head and mid reach farmers, has led to not only water shortages but also the development of waterlogging and secondary soil salinization in the tail (lower) reach of the command due to seepage. As the soil salinity in the head reach was less severe, a slightly wider drain spacing of 60 m was adopted over 15 ha. In the case of the mid reach, salinity was slightly higher than the head reach but slightly less than the tail reach, hence 50 m drain spacing was laid out over 24 ha. Due to the slightly higher soil salinity at the tail end of the command, a closer drain spacing of 40 m was adopted over 11 ha. In all these scenarios, the drain depth was 1.0 m. Despite differences in irrigation water availability and different soil salinity conditions, the study clearly indicated over six seasons that the SSD system is a viable solution for the reclamation of waterlogged saline soils and enhancing rice productivity in all three scenarios of the TBP command.

GC-MS analysis, antidiabetic and antioxidant activity of methanolic extract of pluteus cervinus : an in vitro and in silico approach - Liju Raju; Jeslin C Jenny; Santra Merin Saju; E. Rajkumar (Natural Product Research, 2022)

Evolution of an intermediate C4 photosynthesis in the non-foliar tissues of the Poaceae - Parimalan Rangan; Dhammaprakash P. Wankhede; Rajkumar Subramani; Viswanathan Chinnusamy; Surendra K. Malik; Mirza Jaynul Baig; Kuldeep Singh; Robert Henry (Photosynthesis Research, 2022)

Pollen staining is a rapid and cost-effective alternative to marker-assisted selection for recessive waxy1 gene governing high amylopectin in maize - Zahirul A. Talukder; Vignesh Muthusamy; Rajkumar U. Zunjare; Rashmi Chhabra; Shashidhar B. Reddappa; Subhra J. Mishra; Nitish R. Prakash; Nisrita Gain; Gulab Chand; Firoz Hossain (Physiology and Molecular Biology of Plants, 2022)

Radial basis function neural network and salp swarm algorithm for paddy leaf diseases classification in Thanjavur, Tamilnadu geographical region - Thirugnanasambandam Gayathri Devi; Ganesan Rajkumar; Anandan Srinivasan; Selvarajan Sudha (Acta Geophysica, 2022)

Teak (Tectona grandis L.f.) demonstrates robust adaptability to climate change scenarios in central India - Naseer Mohammad; Sk Mujibar Rahaman; Masjuda Khatun; Muthu Rajkumar; Sanjoy Garai; Ashish Ranjan; Sharad Tiwari (Vegetos, 2022)

Remarkable sunlight-driven photocatalytic performance of Ag-doped ZnO nanoparticles prepared by green synthesis for degradation of emerging pollutants in water - Mariyadhas Jarvin; Sundararajan Ashok Kumar; Daniel Rani Rosaline; Edson Luiz Foletto; Guilherme Luiz Dotto; Savariroyan Stephen Rajkumar Inbanathan (Environmental Science and Pollution Research, 2022)

Methane emissions from dairy farms: case study from a coastal district in South India - Govind Pradeep; C. S. Shaijumon; R. Rajkumar; Jayadev Pradeep (Environment, Development and Sustainability, 2022)

Correction to: Biology, morphology and molecular characterization of Rhaphipodus subopacus (Coleoptera: Cerambycidae): a new pest of cocoa (Theobroma cacao Linnaus) - Shivaji Hausrao Thube; Sangamesh Hiremath; R. Thava Prakasa Pandian; A. Josephrajkumar; Dnyaneshwar M. Firake; M. Rajkumar; Vinayaka Hegde (Applied Entomology and Zoology, 2022)

Biology, morphology and molecular characterization of Rhaphipodus subopacus (Coleoptera: Cerambycidae): a new pest of cocoa (Theobroma cacao Linnaus) - Shivaji Hausrao Thube; Sangamesh Hiremath; R. Thava Prakasa Pandian; A. Josephrajkumar; Dnyaneshwar M. Firake; M. Rajkumar; Vinayaka Hegde (Applied Entomology and Zoology, 2022)

A review on design, evaluation, and performance of emulsified asphalt-treated bases using recycled aggregates - Chakravarthi Sarella; Rajkumar Galipelli; Shankar Sabavath (Environmental Science and Pollution Research, 2022)

Spatio-temporal assessment and monitoring of chlorophyll-a in lake water through geo-informatics algorithm approach (GAA) - Sri Vishnu Prasanth Balachandran Rajkumar; Ramamoorthy Sivakumar (Arabian Journal of Geosciences, 2022)

Genetic parameters of growth traits, trend of production and reproduction traits, and meat quality status of Ghagus, an indigenous chicken of India - Santosh Haunshi; Rajkumar Ullengala; Leslie Leo Prince; Kannaki Ramasamy; Kandeepan Gurunathan; Suresh Devatkal; Rudra Nath Chatterjee (Tropical Animal Health and Production, 2022)

First record of Fusarium falciforme (FSSC 3 + 4) a relevant human pathogen causing root decay of arecanut, Areca catechu L - R. Thava Prakasa Pandian; Shivaji Hausrao Thube; Babu Merin; V. H. Pratibha; M. Rajkumar; Priyank Hanuman Mhatre; Vinayaka Hegde (Journal of Plant Diseases and Protection, 2022)

Mass spectrometric profiling of tryptic digests of trifluoroethanol extracts from core needle biopsies of breast cancer tissues is a viable sample screening tool for biomarker discovery - Prarthana Gopinath; Gopal Gopisetty; Sridevi Veluswami; Shirley Sundersingh; Rajkumar Thangarajan (Journal of Proteins and Proteomics, 2022)

Depositional architecture of sub-aqueous part of a tide-dominated delta and its palaeogeographic implications: Laisong Formation (Barail Group), Indo-Myanmar Ranges, western Manipur - Pramod Kumar; Kshetrimayum Lakshmirani Devi; Partha Pratim Chakraborty; Hemanta Singh Rajkumar (Journal of Earth System Science, 2022)

Elevated skin senescence in young mice causes delayed wound healing - Rex Jeya Rajkumar Samdavid Thanapaul; Maria Shvedova; Grace Haeun Shin; Jack Crouch; Daniel S. Roh (GeroScience, 2022)

Natural regeneration potential of Andaman Padauk (Pterocarpus dalbergioides) in sustaining the tropical forests of Andaman & Nicobar Islands, India - Iyyappan Jaisankar; R. Jayakumara Varadan; Bosco Augustine Jerard; Ganguly Nabanita; Muthu Rajkumar; Ayyam Velmurugan; S. K. Zamir Ahmed; Ezekiel Manasseh Moses (European Journal of Forest Research, 2022)

Biodiesel blends: a comprehensive systematic review on various constraints - Rajkumar Kamaraj; Yarrapragada K.S.S. Rao; Balakrishna B (Environmental Science and Pollution Research, 2022)

Comparative assessment of organic solvent extraction on non-specific immune defences of skin mucus from freshwater fish - Arun Sridhar; Francisco A. Guardiola; Rajkumar Krishnasamy Sekar; Sathiya Deepika Murugesan; Sivagaami Palaniyappan; Dinesh Babu Manikandan; Manikandan Arumugam; Thirumurugan Ramasamy (Aquaculture International, 2022)

Inferring genetic diversity and population structure of India’s National Teak (Tectona grandis L.f.) Germplasm Bank - Naseer Mohammad; Ankur Dahayat; Yogesh Pardhi; Muthu Rajkumar; Shamim Akhtar Ansari; Fatima Shirin (Genetic Resources and Crop Evolution, 2022)

Sedimentary petrography and ichnology of the Barail Group along the Old Cachar road, Manipur, India - Moni Oinam; Hemanta Singh Rajkumar; Ibotombi Soibam; Nishila Oinam; Echeni Heni (Arabian Journal of Geosciences, 2022)

Phylodynamic and genetic diversity of parvoviruses of cats in southern India - Bhaswanth Karanam; Mouttou Vivek Srinivas; Jayalakshmi Vasu; Antony Prabhakar Xavier; Rajkumar Karuppiah; Venkatesa Permal Shanmugam; Hirak Kumar Mukhopadhyay (VirusDisease, 2022)

Pex30 undergoes phosphorylation and regulates peroxisome number in Saccharomyces cerevisiae - Nayan Moni Deori; Terence Infant; Pradeep Kumar Sundaravadivelu; Rajkumar P. Thummer; Shirisha Nagotu (Molecular Genetics and Genomics, 2022)

Kouphichnium isp. from the Priabonian–Rupelian of Manipur, India - Anup S Choudhurimayum; Andrew K Rindsberg; Hemanta S Rajkumar; Moni Oinam; Ibotombi Soibam (Journal of Earth System Science, 2022)

Alteration of miR-362-5p and miR-454-3p expression elicits diverse responses in breast cancer cell lines - Raghu Aarthy; Arunagiri Kuha Deva Magendhra Rao; Krishna Patel; Velusami Sridevi; Thangarajan Rajkumar; Harsha Gowda; Samson Mani (Molecular Biology Reports, 2022)

Wasp Venom Peptide (Polybia MP-1) Shows Antimicrobial Activity Against Multi Drug Resistant Bacteria Isolated from Mastitic Cow Milk - Pallavi Shah; Sameer Shrivastava; Purnima Gogoi; Sonal Saxena; Saumya Srivastava; Rajkumar James Singh; Basant Godara; Naveen Kumar; Gyanendra Kumar Gaur (International Journal of Peptide Research and Therapeutics, 2022)

In-Silico Design of a Novel Tridecapeptide Targeting Spike Protein of SARS-CoV-2 Variants of Concern - Sajjan Rajpoot; Kundan Solanki; Ashutosh Kumar; Kam Y. J. Zhang; Soni Savai Pullamsetti; Rajkumar Savai; Syed M. Faisal; Qiuwei Pan; Mirza S. Baig (International Journal of Peptide Research and Therapeutics, 2022)

Agro-morphological variability and genetic diversity in linseed (Linum usitatissimum L.) germplasm accessions with emphasis on flowering and maturity time - Ankit Saroha; Deepa Pal; Vikender Kaur; Sandeep Kumar; Arti Bartwal; J. Aravind; J. Radhamani; S. Rajkumar; Rajesh Kumar; Sunil S. Gomashe; Abhishek Sengupta; Dhammaprakash Pandhari Wankhede (Genetic Resources and Crop Evolution, 2022)

Metagenomic analysis of lichen-associated bacterial community profiling in Roccella montagnei - Vishnu Raja Vijayakumar; Karthikeyan Saravanan; Maharaja Somasundaram; Rajkumar Jayaraj; Panneerselvam Annamalai; Thajuddin Nooruddin; Dhanasekaran Dharumadurai (Archives of Microbiology, 2022)

Simplified Model-Dependent and Model-Independent Approaches for Dissolution Profile Comparison for Oral Products: Regulatory Perspective for Generic Product Development - Sivacharan Kollipara; Rajkumar Boddu; Tausif Ahmed; Siddharth Chachad (AAPS PharmSciTech, 2022)

An Overview on Promising Somatic Cell Sources Utilized for the Efficient Generation of Induced Pluripotent Stem Cells - Arnab Ray; Jahnavy Madhukar Joshi; Pradeep Kumar Sundaravadivelu; Khyati Raina; Nibedita Lenka; Vishwas Kaveeshwar; Rajkumar P Thummer (Stem Cell Reviews and Reports, 2021)

Pharmaceuticals in the Aquatic Environment and Their Endocrine Disruptive Effects in Fish - Chayan Biswas; Sukhendu Maity; Madhuchhanda Adhikari; Ankit Chatterjee; Rajkumar Guchhait; Kousik Pramanick (Proceedings of the Zoological Society, 2021)

Synthetic Antimicrobial Peptide Polybia MP-1 (Mastoparan) Inhibits Growth of Antibiotic Resistant Pseudomonas aeruginosa Isolates From Mastitic Cow Milk - Pallavi Shah; Sameer Shrivastava; Rajkumar James Singh; Purnima Gogoi; Sonal Saxena; Saumya Srivastava; Naveen Kumar; Gyanendra Kumar Gaur (International Journal of Peptide Research and Therapeutics, 2021)

Generation of energy from salinity gradients using capacitive reverse electro dialysis: a review - Govindarasu Ramasamy; Praveen Kumaar Rajkumar; Meyyappan Narayanan (Environmental Science and Pollution Research, 2021)

Temporal trends in frost occurrence and their prediction models using multivariate statistical techniques for two diverse locations of Northern India - Santanu Kumar Bal; Rajkumar Dhakar; P. Vijaya Kumar; Adita Mishra; V. P. Pramod; M. A. Sarath Chandran; V. M. Sandeep; A. V. M. Subba Rao; K. K. Gill; Rajendra Prasad (Theoretical and Applied Climatology, 2021)

Interaction of plastic particles with heavy metals and the resulting toxicological impacts: a review - Sukhendu Maity; Chayan Biswas; Sambuddha Banerjee; Rajkumar Guchhait; Madhuchhanda Adhikari; Ankit Chatterjee; Kousik Pramanick (Environmental Science and Pollution Research, 2021)

Correction to: Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)

Effect of Dietary Supplementation of Organic Trace Minerals at Reduced Concentrations on Performance, Bone Mineralization, and Antioxidant Variables in Broiler Chicken Reared in Two Different Seasons in a Tropical Region - Rama Rao Savaram Venkata; Prakash Bhukya; Mantena Venkata Lakshmi Narasimha Raju; Rajkumar Ullengala (Biological Trace Element Research, 2021)

Functional interplay between plastic polymers and microbes: a comprehensive review - Sukhendu Maity; Sambuddha Banerjee; Chayan Biswas; Rajkumar Guchhait; Ankit Chatterjee; Kousik Pramanick (Biodegradation, 2021)

Efficacy of Clonal Propagation in Andaman Padauk ( Pterocarpus dalbergioides ): Augmenting Conservation of an Endemic Ornamental Timber Species of Andaman & Nicobar Islands, India - Iyyappan Jaisankar; R Jayakumara Varadan; S Vijayakumar; Nitiprasad Namdeorao Jambhulkar; Bosco Augustine Jerard; Nabanita Ganguly; Muthu Rajkumar; Ezekiel Manasseh Moses; Putcha Simhachalam (Forest Science, 2021)
The population of Andaman padauk (Pterocarpus dalbergioides Roxb.), an endemic ornamental timber species, is fast depleting in the Andaman Islands. Afforestation through seedlings is hindered by low germination and high mortality rates. This study attempts to assess the efficacy of clonal propagation methods to hasten mass multiplication by trying out different combinations of growth hormones, concentration, and dipping duration in semi-hardwood stem cuttings and different combinations of growth hormone concentration and substrate in air layering. Dipping the cuttings in indole-3-butyric acid (IBA) 1,500 ppm for 24 hours and spraying the modified stem-cut layers with IBA 2,000 ppm and binding with top soil and decomposed coir dust turned out to be the best treatment combination for cutting and air layering, respectively. Among the considered factors, the concentration of growth hormone is crucial for cutting, as the performance is enhanced with concentration under a given growth hormone and dipping duration. Similarly, the substrate is crucial for air layering, as modified stem-cut air layers bound with top soil and decomposed coir dust not only achieve the best performance, but also catalyze IBA for further improvement when other substrates remain unresponsive. Successful outcome of both clonal propagation techniques gives hope for disseminating the species across the tropics at global level.

Bioethanol production from seagrass waste, through fermentation process using cellulase enzyme isolated from marine actinobacteria - J. Rajkumar; E. Dilipan; M. Ramachandran; A. Panneerselvam; N. Thajuddin (Vegetos, 2021)

Quantification of greenhouse gas emissions from managed biofuel plantations in a semi-arid landscape of Southern India - G. R. Rao; P. Sathi Reddy; M. Rajkumar (Tropical Ecology, 2021)

Emerging COVID-19 Neurological Manifestations: Present Outlook and Potential Neurological Challenges in COVID-19 Pandemic - Saikat Dewanjee; Jayalakshmi Vallamkondu; Rajkumar Singh Kalra; Nagaprasad Puvvada; Ramesh Kandimalla; P. Hemachandra Reddy (Molecular Neurobiology, 2021)

Allelic variation in sugary1 gene affecting kernel sweetness among diverse-mutant and -wild-type maize inbreds - Rashmi Chhabra; Vignesh Muthusamy; Nisrita Gain; Ashvinkumar Katral; Nitish R. Prakash; Rajkumar U. Zunjare; Firoz Hossain (Molecular Genetics and Genomics, 2021)

Development of multinutrient-rich biofortified sweet corn hybrids through genomics-assisted selection of shrunken2, opaque2, lcyE and crtRB1 genes - Aanchal Baveja; Vignesh Muthusamy; Kusuma Kumari Panda; Rajkumar Uttamrao Zunjare; Abhijit Kumar Das; Rashmi Chhabra; Subhra Jyotshna Mishra; Brijesh Kumar Mehta; Supradip Saha; Firoz Hossain (Journal of Applied Genetics, 2021)

An Insight into the Role of UTF1 in Development, Stem Cells, and Cancer - Khyati Raina; Chandrima Dey; Madhuri Thool; S Sudhagar; Rajkumar P Thummer (Stem Cell Reviews and Reports, 2021)

Estimation and Validation of Actual Evapotranspiration (ETa) of Maize Wheat Cropping System Using SSEBop Model Over IARI Research Farm, New Delhi, India - Joydeep Mukherjee; Anuradha Sharma; Rajkumar Dhakar; V. K. Sehgal; D. Chakraborty; D. K. Das (Journal of the Indian Society of Remote Sensing, 2021)

Identification, ADMET evaluation and molecular docking analysis of Phytosterols from Banaba (Lagerstroemia speciosa (L.)Pers) seed extract against breast cancer - Liju Raju; Raju Lipin; Rajkumar Eswaran (In Silico Pharmacology, 2021)

Biofabrication of ecofriendly copper oxide nanoparticles using Ocimum americanum aqueous leaf extract: analysis of in vitro antibacterial, anticancer, and photocatalytic activities - Dinesh Babu Manikandan; Manikandan Arumugam; Srinivasan Veeran; Arun Sridhar; Rajkumar Krishnasamy Sekar; Balaji Perumalsamy; Thirumurugan Ramasamy (Environmental Science and Pollution Research, 2021)

Activity profile of innate immune-related enzymes and bactericidal of freshwater fish epidermal mucus extract at different pH - Arun Sridhar; Rajkumar Krishnasamy Sekar; Dinesh Babu Manikandan; Manikandan Arumugam; Srinivasan Veeran; Thirumurugan Ramasamy (Environmental Science and Pollution Research, 2021)

Development and validation of multiplex-PCR assay to simultaneously detect favourable alleles of shrunken2, opaque2, crtRB1 and lcyE genes in marker-assisted selection for maize biofortification - Aanchal Baveja; Rashmi Chhabra; Kusuma K. Panda; Vignesh Muthusamy; Rajkumar U. Zunjare; Firoz Hossain (Journal of Plant Biochemistry and Biotechnology, 2021)

Evaluation of Antibacterial Activity of Magainin and Mastoparan and Its Novel Hybrid Against MDR E. coli Isolates of Neonatal Calves - Shailendri Gupta; Abhishek; Sameer Shrivastava; Rajkumar James Singh; Purnima Gogoi; Bablu Kumar (International Journal of Peptide Research and Therapeutics, 2021)

Trace and major minerals of (natural and manufactured) sand: the importance of manufactured sand for construction purposes and the preservation of rivers - Marcos A. E. Chaparro; Shanmugasundaram Gnanasaravanan; Pachamuthu Rajkumar (Innovative Infrastructure Solutions, 2021)

Mitoapocynin, a mitochondria targeted derivative of apocynin induces mitochondrial ROS generation and apoptosis in multiple cell types including cardiac myoblasts: a potential constraint to its therapeutic use - Amena Mahmood; Padmini Bisoyi; Rajkumar Banerjee; Md Yousuf; Shyamal K. Goswami (Molecular and Cellular Biochemistry, 2021)

An automated image analysis platform for the study of weakly -adhered cells - Zhijing Wan; Ben T. MacVicar; Shea Wyatt; Diana E. Varela; Rajkumar Padmawar; Dennis K. Hore (Biofouling, 2021)

Molecular characterization of elite maize (Zea mays L.) inbreds using markers associated with iron and zinc transporter genes - Devender Sharma; Rashmi Chhabra; Vignesh Muthusamy; Rajkumar U. Zunjare; Firoz Hossain (Genetic Resources and Crop Evolution, 2021)

Backyard poultry farming for sustained production and enhanced nutritional and livelihood security with special reference to India: a review - U. Rajkumar; S. V. Rama Rao; M. V. L. N. Raju; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Inheritance of growth traits and impact of selection on carcass and egg quality traits in Vanashree, an improved indigenous chicken - Santosh Haunshi; Rajkumar U.; C. Paswan; L. L. L. Prince; R. N. Chatterjee (Tropical Animal Health and Production, 2021)

Effects of graded levels of mineral mixtures (Aquamin® and Agrimin®) supplemented diets on growth, survival, proximate composition, and carcass mineralization of juvenile freshwater prawn, Macrobrachium malcolmsonii (H Milne-Edwards 1844) - Thirumurugan Ramasamy; Srinivasan Veeran; Arun Sridhar; Rajkumar Krishnasamy Sekar; Dinesh Babu Manikandan; Manikandan Arumugam; Subramanian Periasamy (Tropical Animal Health and Production, 2021)

Biomechanical Regulation of Hematopoietic Stem Cells in the Developing Embryo - Paulina D. Horton; Sandeep P. Dumbali; Krithikaa Rajkumar Bhanu; Miguel F. Diaz; Pamela L. Wenzel (Current Tissue Microenvironment Reports, 2021)
Purpose of Review The contribution of biomechanical forces to hematopoietic stem cell (HSC) development in the embryo is a relatively nascent area of research. Herein, we address the biomechanics of the endothelial-to-hematopoietic transition (EHT), impact of force on organelles, and signaling triggered by extrinsic forces within the aorta-gonad-mesonephros (AGM), the primary site of HSC emergence. Recent Findings Hemogenic endothelial cells undergo carefully orchestrated morphological adaptations during EHT. Moreover, expansion of the stem cell pool during embryogenesis requires HSC extravasation into the circulatory system and transit to the fetal liver, which is regulated by forces generated by blood flow. Findings from other cell types also suggest that forces external to the cell are sensed by the nucleus and mitochondria. Interactions between these organelles and the actin cytoskeleton dictate processes such as cell polarization, extrusion, division, survival, and differentiation. Summary Despite challenges of measuring and modeling biophysical cues in the embryonic HSC niche, the past decade has revealed critical roles for mechanotransduction in governing HSC fate decisions. Lessons learned from the study of the embryonic hematopoietic niche promise to provide critical insights that could be leveraged for improvement in HSC generation and expansion ex vivo.

Pioglitazone modulates doxorubicin resistance in a in vivo model of drug resistant osteosarcoma xenograft - Aparna Natarajan; Balaji Ramachandran; Gopal Gopisetty; Subramani Jayavelu; Shirley Sundersingh; Thangarajan Rajkumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Long-Term Observation of the Arctic Sea Ice Melt Onset from Microwave Radiometry - Rajkumar Kamaljit Singh; Thoudam Vilip Singh; Urikhinbam Somas Singh (Journal of the Indian Society of Remote Sensing, 2021)

A new potential variety of cultivated melon (Cucumis melo L.) from north western India - Anjula Pandey; S. Rajkumar (Genetic Resources and Crop Evolution, 2021)

Low expression of carotenoids cleavage dioxygenase 1 (ccd1) gene improves the retention of provitamin-A in maize grains during storage - Suman Dutta; Vignesh Muthusamy; Rashmi Chhabra; Aanchal Baveja; Rajkumar U. Zunjare; Tapan K. Mondal; Devendra K. Yadava; Firoz Hossain (Molecular Genetics and Genomics, 2021)

Synthesis of Green/Blue Light Emitting Quinolines by Aza-D-A Reaction Using InCl3 Catalyst - Rajkumar Romeshkumar Singh; Thokchom Prasanta Singh; Ningthoujam Premananda Singh; Shanta Singh Naorem; Okram Mukherjee Singh (Journal of Fluorescence, 2021)

Current evidence on the impact of medication optimization or pharmacological interventions on frailty or aspects of frailty: a systematic review of randomized controlled trials - Farhad Pazan; Mirko Petrovic; Antonio Cherubini; Graziano Onder; Alfonso J. Cruz-Jentoft; Michael Denkinger; Tischa J. M. van der Cammen; Jennifer M. Stevenson; Kinda Ibrahim; Chakravarthi Rajkumar; Marit Stordal Bakken; Jean-Pierre Baeyens; et al. (European Journal of Clinical Pharmacology, 2021)
Background Frailty and adverse drug effects are linked in the fact that polypharmacy is correlated with the severity of frailty; however, a causal relation has not been proven in older people with clinically manifest frailty. Methods A literature search was performed in Medline to detect prospective randomized controlled trials (RCTs) testing the effects of pharmacological interventions or medication optimization in older frail adults on comprehensive frailty scores or partial aspects of frailty that were published from January 1998 to October 2019. Results Twenty-five studies were identified, 4 on comprehensive frailty scores and 21 on aspects of frailty. Two trials on comprehensive frailty scores showed positive results on frailty although the contribution of medication review in a multidimensional approach was unclear. In the studies on aspects related to frailty, ten individual drug interventions showed improvement in physical performance, muscle strength or body composition utilizing alfacalcidol, teriparatide, piroxicam, testosterone, recombinant human chorionic gonadotropin, or capromorelin. There were no studies examining negative effects of drugs on frailty. Conclusion So far, data on a causal relationship between drugs and frailty are inconclusive or related to single-drug interventions on partial aspects of frailty. There is a clear need for RCTs on this topic that should be based on a comprehensive, internationally consistent and thus reproducible concept of frailty assessment.

Water deficit-induced oxidative stress and differential response in antioxidant enzymes of tolerant and susceptible tea cultivars under field condition - M. Nalina; S. Saroja; M. Chakravarthi; R. Rajkumar; B. Radhakrishnan; K. N. Chandrashekara (Acta Physiologiae Plantarum, 2021)

Mercury-Induced Inhibition of Tyrosine Phosphorylation of Sperm Proteins and Altered Functional Dynamics of Buck Spermatozoa: an In Vitro Study - Bhawna Kushawaha; Rajkumar Singh Yadav; Dilip Kumar Swain; Pradeep K Rai; Satish Kumar Garg (Biological Trace Element Research, 2020)

Genetic analysis of growth and egg production traits in synthetic colored broiler female line using animal model - L. Leslie Leo Prince; K. S. Rajaravindra; U. Rajkumar; B. L. N. Reddy; C. Paswan; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2020)

A novel leaf rust resistance gene introgressed from Aegilops markgrafii maps on chromosome arm 2AS of wheat - K. Rani; B. R. Raghu; S. K. Jha; Priyanka Agarwal; Niharika Mallick; M. Niranjana; J. B. Sharma; A. K. Singh; N. K. Sharma; S. Rajkumar; S. M. S. Tomar; Vinod (Theoretical and Applied Genetics, 2020)

Influence of T-, C- and S- cytoplasms on male sterility and their utilisation in baby corn hybrid breeding - Saikat Pal; Rajkumar Uttamrao Zunjare; Vignesh Muthusamy; Hriipluou Duo; Munegowda Manoj Gowda; Prolay Kumar Bhowmick; Ravindra Kasana; Vinay Bhatt; Firoz Hossain (Euphytica, 2020)

Evaluation of groundwater quality and human health risks from fluoride and nitrate in semi-arid region of northern India - Gagandeep Singh; Madhuri S. Rishi; Rajkumar Herojeet; Lakhvinder Kaur; Kirti Sharma (Environmental Geochemistry and Health, 2020)

Development of production management strategies for a long-duration rice variety: Rajendra Mahsuri—using crop growth model, DSSAT, for the state of Bihar, India - Ranjeet K. Jha; Prasanta K. Kalita; Rajkumar Jat (Paddy and Water Environment, 2020)

Morphological characterization and analysis of genetic diversity and population structure in Citrus × jambhiri Lush. using SSR markers - M. R. Rohini; M. Sankaran; S. Rajkumar; K. Prakash; A. Gaikwad; R. Chaudhury; S. K. Malik (Genetic Resources and Crop Evolution, 2020)

The association between metabolic syndrome and Hepatitis C virus infection in the United States - Preetha Rajkumar; Alok Kumar Dwivedi; Christopher Alfred Dodoo; Navkiran Kaur Shokar; Jennifer Salinas; Rajkumar Lakshmanaswamy (Cancer Causes & Control, 2020)

Tumor-derived exosomes in the regulation of macrophage polarization - Mirza S. Baig; Anjali Roy; Sajjan Rajpoot; Dongfang Liu; Rajkumar Savai; Sreeparna Banerjee; Manabu Kawada; Syed M. Faisal; Rohit Saluja; Uzma Saqib; Tomokazu Ohishi; Kishore K. Wary (Inflammation Research, 2020)

Genome-wide analysis of glutathione S-transferase gene family in chickpea suggests its role during seed development and abiotic stress - Rajesh Ghangal; Mohan Singh Rajkumar; Rohini Garg; Mukesh Jain (Molecular Biology Reports, 2020)

Facile architecture of highly effective nanofibrous membrane adsorbent via electrospun followed by hydrothermal carbonization for potential application in dye removal from water - Rajkumar Sadasivam; Gopinath Packirisamy (Environmental Science and Pollution Research, 2020)

Novel thiazolinyl-picolinamide based palladium(II) complex-impregnated urinary catheters quench the virulence and disintegrate the biofilms of uropathogens - Deeksha Rajkumar; Durairajan Rubini; M. Sudharsan; D. Suresh; Paramasivam Nithyanand (Biofouling, 2020)

An Insight into Reprogramming Barriers to iPSC Generation - Krishna Kumar Haridhasapavalan; Khyati Raina; Chandrima Dey; Poulomi Adhikari; Rajkumar P. Thummer (Stem Cell Reviews and Reports, 2020)

Modulated Protein Binding Ability of Anti-Diabetic Drugs in Presence of Monodispersed Gold Nanoparticles and its Inhibitory Potential towards Advanced Glycated End (AGE) Product Formation - Imocha Rajkumar Singh; Sivaprasad Mitra (Journal of Fluorescence, 2020)

Effect of Marine Alga (Turbinaria Ornata) Mixed Diet on Some Aspects of Biology of Post Larval Macrobrachium Rosenbergii - Gopalan Rajkumar; Periyakali Saravana Bhavan; Veeran Srinivasan; Annamalai Asaikkutti; Rajendran Udayasuriyan; Madhayan Karthik; Thangavelu Satgurunathan (Proceedings of the Zoological Society, 2019)

Feasibility of Controlled Drainage in Saline Vertisols of TBP Command Area of Karnataka, India - A.V. Karegoudar; J. Vishwanath; S.R. Anand; R.H. Rajkumar; S.K. Ambast; M.J. Kaledhonkar (Irrigation and Drainage, 2019)
Subsurface drainage (SSD) improves crop productivity in canal command areas suffering from waterlogging and salinity problems. However, excessive drainage of paddy fields under conventional SSD is known to cause irrigation water shortage during critical growth stages of rice and also results in excessive leaching of nitrogenous fertilizers particularly at the tail end of the irrigation command. To overcome these problems farmers of the Tungabhadra Project (TBP) irrigation command used to block the outlets of lateral drains of the SSD system. In order to provide a lasting solution to this problem through a controlled drainage approach, a comparative field study was conducted on clay loam soil at the Agricultural Research Station (ARS), Gangavathi, over four seasons. In general, there was a reduction in drain discharge depth of 64% in the case of controlled drainage over conventional SSD, with an average irrigation water saving of about 17%. Average nitrogen loss was also reduced by 50.4% compared to conventional drainage. Paddy grain yield improvement was slightly higher (from 3.84 to 5.14 t ha −1 ) for conventional compared to controlled conditions (3.76–4.83 t ha −1 ). © 2019 John Wiley & Sons, Ltd. © 2019 John Wiley & Sons, Ltd.

Spatio-temporal trend in heat waves over India and its impact assessment on wheat crop - Debasish Chakraborty; Vinay Kumar Sehgal; Rajkumar Dhakar; Mrinmoy Ray; Deb Kumar Das (Theoretical and Applied Climatology, 2019)

Evaluation of heavy metal contamination in soil using geochemical indexing approaches and chemometric techniques - H. Rajkumar; P. K. Naik; M. S. Rishi (International Journal of Environmental Science and Technology, 2019)

Water pollution and observation of acquired antibiotic resistance in Bayou Lafourche, a major drinking water source in Southeast Louisiana, USA - Kyle Bird; Raj Boopathy; Rajkumar Nathaniel; Gary LaFleur (Environmental Science and Pollution Research, 2019)

Bioaccumulation of TBT and Its Cellular Toxic Effects on the Freshwater Prawn Macrobrachium rosenbergii - Peranandam Revathi; Palanisamy Iyapparaj; Rajkumar A. Vasanthi; Natesan Munuswamy; Arunachalam Palavesam (Bulletin of Environmental Contamination and Toxicology, 2019)

Rewiring the functional complexity between Crc, Hfq and sRNAs to regulate carbon catabolite repression in Pseudomonas - Krishna Bharwad; Shalini Rajkumar (World Journal of Microbiology and Biotechnology, 2019)

Molecular diversity and genetic variability of kernel tocopherols among maize inbreds possessing favourable haplotypes of γ-tocopherol methyl transferase (ZmVTE4) - Abhijit Kumar Das; Sunil Kumar Jaiswal; Vignesh Muthusamy; Rajkumar Uttamrao Zunjare; Hema Singh Chauhan; Gulab Chand; Supradip Saha; Firoz Hossain (Journal of Plant Biochemistry and Biotechnology, 2019)

Prevalence of Nutritional Anemia and Hyperhomocysteinemia in Urban Elderly - Sai Santhosh Vadakattu; Laxmi Rajkumar Ponday; Arlappa Nimmathota; Balakrishna Nagalla; Divya Shoshanni Kondru; Prasad Undrajavarapu; Bhoja Raju Banavath; Sivakesava Rao Kommula; Ravinder Punjal; Suryanarayana Palla (Indian Journal of Clinical Biochemistry, 2019)

Succinate irrepressible periplasmic glucose dehydrogenase of Rhizobium sp. Td3 and SN1 contributes to its phosphate solubilization ability - Bhagya Iyer; Shalini Rajkumar (Archives of Microbiology, 2019)

Altered lipid metabolism in post-traumatic epileptic rat model: one proposed pathway - Niraj Kumar Srivastava; Somnath Mukherjee; Rajkumar Sharma; Jharana Das; Rohan Sharma; Vikas Kumar; Neeraj Sinha; Deepak Sharma (Molecular Biology Reports, 2019)

Multiple infections caused by white spot syndrome virus and Enterocytozoon hepatopenaei in pond‐reared Penaeus vannamei in India and multiplex PCR for their simultaneous detection - S. Thamizhvanan; S. Sivakumar; S. Santhosh Kumar; D. Vinoth Kumar; S. Suryakodi; K. Balaji; T. Rajkumar; S. Vimal; S. Abdul Majeed; G. Taju; A. S. Sahul Hameed (Journal of Fish Diseases, 2019)
White leg shrimp, Penaeus vannamei , were collected on a monthly basis from grow‐out ponds located at Tamil Nadu and Andhra Pradesh states along the east coast of India for screening of viral and other pathogens. Totally 240 shrimp samples randomly collected from 92 farms were screened for white spot syndrome virus (WSSV), infectious hypodermal and haematopoietic necrosis virus (IHHNV), infectious myonecrosis virus (IMNV) and Enterocytozoon hepatopenaei (EHP). The number of shrimp collected from shrimp farms ranged from 6 to 20 based on the body weight of the shrimp. All the shrimp collected from one farm were pooled together for screening for pathogens by PCR assay. Among the samples screened, 28 samples were WSSV‐positive, one positive for IHHNV and 30 samples positive for EHP. Among the positive samples, four samples were found to be positive for both WSSV and EHP, which indicated that the shrimp had multiple infections with WSSV and EHP. This is the first report on the occurrence of multiple infections caused by WSSV and EHP. Multiplex PCR (m‐PCR) protocol was standardized to detect both pathogens simultaneously in single reaction instead of carrying out separate PCR for both pathogens. Using m‐PCR assay, naturally infected shrimp samples collected from field showed two prominent bands of 615 and 510 bp for WSSV and EHP, respectively.

Evaluation of the Neuroprotective Effect of Sirt3 in Experimental Stroke - Rajkumar Verma; Rodney M. Ritzel; Joshua Crapser; Brett D. Friedler; Louise D. McCullough (Translational Stroke Research, 2019)

Changes in daily maximum temperature extremes across India over 1951–2014 and their relation with cereal crop productivity - Debasish Chakraborty; Vinay Kumar Sehgal; Rajkumar Dhakar; Eldho Varghese; Deb Kumar Das; Mrinmoy Ray (Stochastic Environmental Research and Risk Assessment, 2018)

A new strain of white spot syndrome virus affecting Litopenaeus vannamei in Indian shrimp farms - S Sivakumar; S Vimal; S Abdul Majeed; S Santhosh Kumar; G Taju; N Madan; T Rajkumar; S Thamizhvanan; K V Shamsudheen; V Scaria; S Sivasubbu; A S Sahul Hameed (Journal of Fish Diseases, 2018)
White spot syndrome virus ( WSSV )‐infected shrimp samples collected from grow‐out ponds located at Nellore, Andhra Pradesh, India, showed WSSV negative and positive by PCR using primer sets specific to ORF 119 and VP 28 gene of WSSV , respectively. This indicated the deletion of genetic fragments in the genome of WSSV . The WSSV isolate along with lab strain of WSSV was subjected to next‐generation sequencing. The sequence analysis revealed a deletion of 13,170 bp at five positions in the genome of WSSV ‐ NS (new strain) relative to WSSV ‐ TH and WSSV ‐ LS (lab strain). The PCR analysis using the ORF 's specific primer sets revealed the complete deletion of 10 ORF s in the genome of WSSV ‐ NS strain. The primer set was designed based on sequence covering ORF 161/162/163 to amplify a product of 2,748 bp for WSSV ‐ LS and 402 bp for WSSV ‐ NS . Our surveillance programme carried out since 2002 revealed the replacement of WSSV ‐ LS by WSSV ‐ NS in Indian shrimp culture system.

Effect of supplementing germinated sprouts of pulses on performance, carcass variables, immune and oxidative stress indicators in broiler chickens reared during tropical summer season - S. V. Rama Rao; B. Prakash; U. Rajkumar; M. V. L. N. Raju; T. Srilatha; E. P. K. Reddy (Tropical Animal Health and Production, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

Marker-assisted introgression of opaque2 allele for rapid conversion of elite hybrids into quality protein maize - Firoz Hossain; Vignesh Muthusamy; Neha Pandey; Ashish K. Vishwakarma; Aanchal Baveja; Rajkumar U. Zunjare; Nepolean Thirunavukkarasu; Supradip Saha; Kanchikeri M. Manjaiah; Boddupalli M. Prasanna; Hari S. Gupta (Journal of Genetics, 2018)

Transcriptomic changes in Echinochloa colona in response to treatment with the herbicide imazamox - Alice A. Wright; Rajkumar Sasidharan; Liisa Koski; Marianela Rodriguez-Carres; Daniel G. Peterson; Vijay K. Nandula; Jeffery D. Ray; Jason A. Bond; David R. Shaw (Planta, 2018)

Neoplasia in goldlined seabream, Rhabdosargus sarba (Forsskål, 1775) - V Singaravel; A Gopalakrishnan; K Raja; M Rajkumar; H W Ferguson (Journal of Fish Diseases, 2018)

Anti-proliferative, structure–activity relationship of pyridinylchalcones and chromanones - Cherupally Dayakar; Pathi Suman; Kommera Rajkumar; Thampunuri Ramalinga Murthy; Shasi Vardhan Kalivendi; Bhimapaka China Raju (Medicinal Chemistry Research, 2018)

Trends and Change-Point in Satellite Derived Phenology Parameters in Major Wheat Growing Regions of North India During the Last Three Decades - Debasish Chakraborty; Vinay Kumar Sehgal; Rajkumar Dhakar; Deb Kumar Das; Rabi Narayan Sahoo (Journal of the Indian Society of Remote Sensing, 2018)

Combination of cationic dexamethasone derivative and STAT3 inhibitor (WP1066) for aggressive melanoma: a strategy for repurposing a phase I clinical trial drug - Samaresh Sau; Sujan Kumar Mondal; Sushil K. Kashaw; Arun K. Iyer; Rajkumar Banerjee (Molecular and Cellular Biochemistry, 2017)

Probabilistic assessment of phenophase-wise agricultural drought risk under different sowing windows: a case study with rainfed soybean - Rajkumar Dhakar; M. A. Sarath Chandran; Shivani Nagar; V. Visha Kumari (Environmental Monitoring and Assessment, 2017)

Studies on the occurrence of infectious myonecrosis virus in pond‐reared Litopenaeus vannamei (Boone, 1931) in India - A S Sahul Hameed; S Abdul Majeed; S Vimal; N Madan; T Rajkumar; S Santhoshkumar; S Sivakumar (Journal of Fish Diseases, 2017)
Whiteleg shrimp, Litopenaeus vannamei, with clinical sign of muscle opaqueness with reddish colour at the distal abdominal segments were observed in farms located in West Bengal State, India. The mortality of shrimp in all disease outbreak ponds ranged from 20% to 50%, and mortality increased gradually. The RT ‐ PCR assay of these samples using primer sets specific to infectious myonecrosis virus ( IMNV ) revealed its presence in the disease outbreak ponds. The IMNV infection was reproduced in healthy shrimp by intramuscular injection to satisfy River's postulates. The virus caused mortality in intramuscularly challenged shrimp, but failed to cause mortality by oral route. Tissue distribution of IMNV in infected shrimp by RT ‐ PCR assay revealed the presence of this virus in haemolymph, gill, hepatopancreas and muscle. This study confirms that the disease outbreak which occurred in the shrimp farms located at Purba Medinipur District, West Bengal, India, was due to IMNV .

Development and validation of multiplex-PCR assay for simultaneous detection of rare alleles of crtRB1 and lcyE governing higher accumulation of provitamin A in maize - Rajkumar Uttamrao Zunjare; Rashmi Chhabra; Firoz Hossain; Vignesh Muthusamy; Aanchal Baveja; Hari Shanker Gupta (Journal of Plant Biochemistry and Biotechnology, 2017)

Distribution of recombinant VP28 protein in tissues and its immunomodulatory effect against white spot syndrome virus in whiteleg shrimp, Litopenaeus vannamei (Boone, 1931) - G. Taju; N. Madan; S. Abdul Majeed; T. Rajkumar; M. A. Farook; S. Vimal; A. Nazeer Basha; A. S. Sahul Hameed (Aquaculture International, 2017)

Protein Sparing Effect of Dietary Rumen Protected Lysine Plus Methionine in Growing Murrah Buffaloes (Bubalus bubalis) - Rajkumar Gami; S. S. Thakur; M. S. Mahesh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Adhesion of Lactobacilli and their anti-infectivity potential - Ashok Kumar Yadav; Ashish Tyagi; Ashwani Kumar; Surbhi Panwar; Sunita Grover; Asha Chandola Saklani; Rajkumar Hemalatha; Virender Kumar Batish (Critical Reviews in Food Science and Nutrition, 2017)

Auxin biosynthetic intermediate genes and their role in developmental growth and plasticity in higher plants - Raj Kiran Bala; Rajkumar Murugesan; Sivanesan Subramanian; Anuradha Dhanasekaran (Journal of Plant Biochemistry and Biotechnology, 2017)

Dietary Supplementation of Magnesium Oxide (MgO) Nanoparticles for Better Survival and Growth of the Freshwater Prawn Macrobrachium rosenbergii Post-larvae - Veeran Srinivasan; Periyakali Saravana Bhavan; Gopalan Rajkumar; Thangavelu Satgurunathan; Thirunavukkarasu Muralisankar (Biological Trace Element Research, 2017)

Microsatellite-based genetic diversity analyses of sugary1-, shrunken2- and double mutant- sweet corn inbreds for their utilization in breeding programme - Brijesh Mehta; Firoz Hossain; Vignesh Muthusamy; Aanchal Baveja; Rajkumar Zunjare; Shailendra K. Jha; Hari S. Gupta (Physiology and Molecular Biology of Plants, 2017)

Perspectives of long non-coding RNAs in cancer - Arunagiri Kuha Deva Magendhra Rao; Thangarajan Rajkumar; Samson Mani (Molecular Biology Reports, 2017)

Alleviation of environmental stress in plants: The role of beneficial Pseudomonas spp. - M. Rajkumar; L. Benedict Bruno; J. Rajesh Banu (Critical Reviews in Environmental Science and Technology, 2017)

Lead Modulates Calcium Entry and Beta-Adrenoceptors Signaling to Produce Myometrial Relaxation in Rats - Udayraj P. Nakade; Abhishek Sharma; Soumen Choudhury; Rajkumar Singh Yadav; Satish Kumar Garg (Biological Trace Element Research, 2017)

Grading of proximal internal carotid artery (ICA) stenosis by Doppler/duplex ultrasound (DUS) and computed tomographic angiography (CTA): correlation and interrater reliability in real-life practice - Oliver Matz; Omid Nikoubashman; Parajuli Rajkumar; Andreas Keuler; Martin Wiesmann; Jörg B. Schulz; Arno Reich (Acta Neurologica Belgica, 2017)

In vitro immature embryo germination and propagation of Vanda stangeana Rchb. f., an orchid endemic to India - Bembemcha Pebam; Rajkumar Kishor; V. Narmatha Bai (Horticulture, Environment, and Biotechnology, 2016)

Durantol - a phytosterol antifungal contributor from Duranta repens Linn. For organic Management of Sorghum Downy Mildew - Heminder Singh; Farhan Zameer; Shaukath Ara Khanum; Rajkumar H. Garampalli (European Journal of Plant Pathology, 2016)

Serotonin transporter gene (SLC6A4) polymorphisms are associated with response to fluoxetine in south Indian major depressive disorder patients - Aarthi Manoharan; Deepak Gopal Shewade; Ravi Philip Rajkumar; Surendiran Adithan (European Journal of Clinical Pharmacology, 2016)

Development of microsatellite markers and their use in genetic diversity and population structure analysis in Casuarina - A. R. K. Kullan; A. V. Kulkarni; R. Suresh Kumar; R. Rajkumar (Tree Genetics & Genomes, 2016)

Erratum to: Two Stagonosporopsis species identified as causal agents of gummy stem blight epidemics of gherkin cucumber (Cucumis sativus) in Karnataka, India - Rajkumar H. Garampalli; Mangala K. Gopalakrishna; Hao-Xi Li; Marin Talbot Brewer (European Journal of Plant Pathology, 2016)

Two Stagonosporopsis species identified as causal agents of gummy stem blight epidemics of gherkin cucumber (Cucumis sativus) in Karnataka, India - Rajkumar H. Garampalli; Mangala K. Gapalkrishna; Hao-Xi Li; Marin Talbot Brewer (European Journal of Plant Pathology, 2016)

Lidocaine Transdermal Patch: Pharmacokinetic Modeling and In Vitro–In Vivo Correlation (IVIVC) - Phani Krishna Kondamudi; Phani Prasanth Tirumalasetty; Rajkumar Malayandi; Srinivas Mutalik; Raviraj Pillai (AAPS PharmSciTech, 2016)

Erratum to: A flow cytometry-based reporter assay identifies macrolide antibiotics as nonsense mutation read-through agents - Michal Caspi; Anastasia Firsow; Raja Rajkumar; Nir Skalka; Itay Moshkovits; Ariel Munitz; Metsada Pasmanik-Chor; Hagar Greif; Dalia Megiddo; Revital Kariv; Daniel W. Rosenberg; Rina Rosin-Arbesfeld (Journal of Molecular Medicine, 2016)

A flow cytometry-based reporter assay identifies macrolide antibiotics as nonsense mutation read-through agents - Michal Caspi; Anastasia Firsow; Raja Rajkumar; Nir Skalka; Itay Moshkovitz; Ariel Munitz; Metsada Pasmanik-Chor; Hagar Greif; Dalia Megido; Revital Kariv; Daniel W. Rosenberg; Rina Rosin-Arbesfeld (Journal of Molecular Medicine, 2016)

Identification and agro-morphological characterization of rice genotypes resistant to sheath blight - Susmita Dey; Jyothi Badri; V. Prakasam; V. P. Bhadana; K. B. Eswari; G. S. Laha; C. Priyanka; Aku Rajkumar; T. Ram (Australasian Plant Pathology, 2016)

Application of environmetrics statistical models and water quality index for groundwater quality characterization of alluvial aquifer of Nalagarh Valley, Himachal Pradesh, India - Rajkumar Herojeet; Madhuri S. Rishi; Renu Lata; Ranjna Sharma (Sustainable Water Resources Management, 2016)

Erratum to: Association of Autophagy in the Cell Death Mediated by Dihydrotestosterone in Autoreactive T Cells Independent of Antigenic Stimulation - Ting Jia; Annadurai Anandhan; Chandirasegaran Massilamany; Rajkumar A. Rajasekaran; Rodrigo Franco; Jay Reddy (Journal of Neuroimmune Pharmacology, 2016)

Response of upland cotton (G.hirsutum L.) genotypes to drought stress using drought tolerance indices - Chandrakant Singh; Vijay Kumar; Indivar Prasad; Vishal R. Patil; B. K. Rajkumar (Journal of Crop Science and Biotechnology, 2016)

Geospatial approach for assessment of biophysical vulnerability to agricultural drought and its intra-seasonal variations - Vinay Kumar Sehgal; Rajkumar Dhakar (Environmental Monitoring and Assessment, 2016)

Yield Enhancement Through Fertilizer Placement by Machine Below the Seed in Rain-fed Soybean Crop Under Vertisols - Devvrat Singh; Rajkumar Ramteke; I. R. Khan (Agricultural Research, 2016)

PNPLA3 Polymorphism and Nonalcoholic Fatty Liver Disease - Olena Kolesnikova; Valeriya Nemtsova; Rajkumar Rajendram (Exposure and Health, 2016)

Predicting Irrigated and Rainfed Rice Yield Under Projected Climate Change Scenarios in the Eastern Region of India - A. V. M. Subba Rao; Arun K. Shanker; V. U. M. Rao; V. Narsimha Rao; A. K. Singh; Pragyan Kumari; C. B. Singh; Praveen Kumar Verma; P. Vijaya Kumar; B. Bapuji Rao; Rajkumar Dhakar; M. A. Sarath Chandran; et al. (Environmental Modeling & Assessment, 2016)

Association of Autophagy in the Cell Death Mediated by Dihydrotestosterone in Autoreactive T Cells Independent of Antigenic Stimulation - Ting Jia; Annandurai Anandhan; Chandirasegaran Massilamany; Rajkumar A. Rajasekaran; Rodrigo Franco; Jay Reddy (Journal of Neuroimmune Pharmacology, 2015)

Assessment of terminal heat tolerance ability of wheat genotypes based on physiological traits using multivariate analysis - Shivani Nagar; V. P. Singh; Ajay Arora; Rajkumar Dhakar; Shiv Ramakrishnan (Acta Physiologiae Plantarum, 2015)

Semi-automated Lung Field Segmentation in Scoliosis Radiographs: An Exploratory Study - Rucha Deshpande; Rajkumar Elagiri Ramalingam; Panagiotis Chatzistergos; Vinay Jasani; Nachiappan Chockalingam (Journal of Medical and Biological Engineering, 2015)

Estimation of Sea Ice Freeboard from SARAL/AltiKa Data - Megha Maheshwari; C. Mahesh; Kamaljit Singh Rajkumar; J. Pallipad; D. Ram Rajak; Sandip R. Oza; Raj Kumar; Rashmi Sharma (Marine Geodesy, 2015)

Concurrent Use of OSCAT and AltiKa to Characterize Antarctic Ice Surface Features - Kamaljit Singh Rajkumar; Megha Maheshwari; Jayaprasad Pallipad; Dhani Ram Rajak; Raj Kumar; Sandip Rashmikant Oza (Marine Geodesy, 2015)

Growth and Yield Responses of Soybean to Climate Change - Rajkumar Ramteke; Girish Kumar Gupta; Dev Vrat Singh (Agricultural Research, 2015)

Attribute of trace fossils of Laisong flysch sediments, Manipur, India - Kumar S Khaidem; Hemanta S Rajkumar; Ibotombi Soibam (Journal of Earth System Science, 2015)

Rapid Diagnosis and Simultaneous Identification of Tuberculous and Bacterial Meningitis by a Newly Developed Duplex Polymerase Chain Reaction - Khushboo J. Nagdev; Sharda P. Bhagchandani; Shradha S. Bhullar; Rajkumar C. Kapgate; Rajpal S. Kashyap; Nitin H. Chandak; Hatim F. Daginawala; Hemant J. Purohit; Girdhar M. Taori (Indian Journal of Microbiology, 2015)

Molecular diversity of Bipolaris oryzae infecting Oryza sativa in India - A. Kandan; J. Akhtar; B. Singh; D. Dixit; D. Chand; A. Roy; S. Rajkumar; P. C. Agarwal (Phytoparasitica, 2015)

Terbinafine hydrochloride loaded nanoemulsion based gel for topical application - V. V. S. Narayana Reddy Karri; Suresh Kumar Raman; Gowthamarajan Kuppusamy; Shashank Mulukutla; Shanmugam Ramaswamy; Rajkumar Malayandi (Journal of Pharmaceutical Investigation, 2015)

Photoinduced Electron Transfer Reactions of Ruthenium(II) Phenanthroline Complexes with Dimethylaniline in Aqueous and Micellar Media - Ramanathan Sangiliapillai; Ramdass Arumugam; Rajkumar Eswaran; Rajagopal Seenivasan (Journal of Fluorescence, 2015)

Effects of water temperature on survival, growth, digestive enzyme activities, and body composition of the leopard coral grouper Plectropomus leopardus - Zhijing Sun; Sudong Xia; Shouming Feng; Zhenkui Zhang; Mohammad Mustafizur Rahman; Mayalagu Rajkumar; Shuguang Jiang (Fisheries Science, 2015)

Tissue distribution of hepatopancreatic parvo‐like virus of shrimp in freshwater rice‐field crab, P aratelphusa hydrodomous ( H erbst) - N Madan; T Rajkumar; N Sundar Raj; M A Farook; K S N Nambi; S Abdul Majeed; A S Sahul Hameed (Journal of Fish Diseases, 2014)
An attempt was made to determine the replication efficiency of hepatopancreatic parvo‐like virus ( HPV ) of shrimp in different organs of freshwater rice‐field crab P aratelphusa hydrodomous ( H erbst) using bioassay, PCR , RT ‐ PCR , ELISA , Western blot and q‐ PCR analyses. Another attempt was made to use this crab as an alternative to penaeid shrimp for the large‐scale production of HPV . This crab was found to be highly susceptible to HPV by intramuscular injection. The systemic HPV infection was confirmed by PCR and W estern blot analyses in freshwater crab. The expression of capsid protein gene in different organs of infected crab was revealed by RT ‐ PCR analysis. Indirect ELISA was used to quantify the capsid protein in different organs of the crab. The copy number of HPV in different organs of the infected crab was quantified by q‐ PCR . The results revealed a steady decrease in C T values in different organs of the infected crab during the course of infection. The viral inoculum that was prepared from different organs of the infected crab caused significant mortality in post‐larvae of tiger prawn, P enaeus monodon ( F abricius). The results revealed that this rice‐field crab could be used as an alternative host for HPV replication and also for large‐scale production of HPV .

Mining of gene-based SNPs from publicly available ESTs and their conversion to cost-effective genotyping assay in sorghum [Sorghum bicolor (L.) Moench] - Yemane Girma; Dadakhalandar Doddamani; Bashasab Fakrudin; Rajkumar; Sadik Ahmed Wasik Ahmed; Sheweta Gujar; Suvarna Patil; Gurusiddesh Hiremath (Journal of Crop Science and Biotechnology, 2014)

Fertility and apparent genetic anticipation in Lynch syndrome - Douglas Stupart; Aung Ko Win; Mark Jenkins; Ingrid M. Winship; Paul Goldberg; Rajkumar Ramesar (Familial Cancer, 2014)

Haplotype-based study of the association of alcohol and acetaldehyde-metabolising genes with alcohol dependence (with or without comorbid anxiety symptoms) in a Cape Mixed Ancestry population - Andrew Crawford; Shareefa Dalvie; Sarah Lewis; Anthony King; Israel Liberzon; George Fein; Karestan Koenen; Rajkumar Ramesar; Dan J. Stein (Metabolic Brain Disease, 2014)

Establishing postprandial bio-equivalency and IVIVC for generic metformin sustained release small sized tablets - Chandramohan Eaga; Shivakumar Mantri; Rajkumar Malayandi; Phani Krishna Kondamudi; Sumon Chakraborty; S. V. N. Raju; Deepika Aggarwal (Journal of Pharmaceutical Investigation, 2014)

Effect of a Previous Washing Step with Tannic Acid on the Quality of Minced Horse Mackerel ( Trachurus trachurus ) During Frozen Storage - Faisal Rashid Sofi; S. M. Zofair; Vijay Kumar Reddy Surasani; K. K. Sabha Nissar; Rajkumar Ratankumar Singh (Journal of Aquatic Food Product Technology, 2014)

Photoinduced Electron Transfer Reactions of Ruthenium(II)-Complexes Containing Amino Acid with Quinones - Rajkumar Eswaran; Swarnalatha Kalayar; Muthu Mareeswaran Paulpandian; Rajagopal Seenivasan (Journal of Fluorescence, 2014)

Seasonality of the common cutworm Spodoptera litura in a soybean ecosystem - M. Punithavalli; A. N. Sharma; M. Balaji Rajkumar (Phytoparasitica, 2014)

Biopharmaceutical considerations and characterizations in development of colon targeted dosage forms for inflammatory bowel disease - Rajkumar Malayandi; Phani Krishna Kondamudi; P. K. Ruby; Deepika Aggarwal (Drug Delivery and Translational Research, 2014)

First perissodactyl footprints from Flysch deposits of the Barail Group (Lower Oligocene) of Manipur, India - Hemanta Singh Rajkumar; Hendrik Klein (Journal of Earth System Science, 2014)

Morphological and Molecular Analysis Calls for a Reappraisal of the Red Rain Cells of Kerala - Rajkumar Gangappa; Mark J. Burchell; Stuart I. Hogg (Current Microbiology, 2014)

Preliminary studies on the characterization of clay minerals in the Sundarban mangrove core sediments, West Bengal, India - K. Rajkumar; AL. Ramanathan; P. N. Behera; S. Chidambaram (Arabian Journal of Geosciences, 2014)

Expressed sequence tags and molecular cloning and characterization of gene encoding pinoresinol/lariciresinol reductase from Podophyllum hexandrum - Dhammaprakash Pandhari Wankhede; Dipul Kumar Biswas; Subramani Rajkumar; Alok Krishna Sinha (Protoplasma, 2013)

Molecular cloning, characterization and heterologous expression of bile salt hydrolase (Bsh) from Lactobacillus fermentum NCDO394 - Rajesh Kumar; Hemalatha Rajkumar; Manoj Kumar; Sudarshan Reddy Varikuti; Ramakrishna Athimamula; Mohd. Shujauddin; Ramesh Ramagoni; Narendrababu Kondapalli (Molecular Biology Reports, 2013)

Newer antipsychotics and upcoming molecules for schizophrenia - Melvin George; Radhika Amrutheshwar; Ravi Philip Rajkumar; Shivanand Kattimani; Steven Aibor Dkhar (European Journal of Clinical Pharmacology, 2013)

Molecular mapping of genomic regions harbouring QTLs for root and yield traits in sorghum (Sorghum bicolor L. Moench) - Rajkumar; B. Fakrudin; S. P. Kavil; Y. Girma; S. S. Arun; D. Dadakhalandar; B. H. Gurusiddesh; A. M. Patil; M. Thudi; S. B. Bhairappanavar; Y. D. Narayana; P. U. Krishnaraj; et al. (Physiology and Molecular Biology of Plants, 2013)

Prospective biomarkers of stem cells of human endometrium and fallopian tube compared with bone marrow - S. Indumathi; R. Harikrishnan; J. S. Rajkumar; D. Sudarsanam; M. Dhanasekaran (Cell and Tissue Research, 2013)

Plasticity and banking potential of cultured adipose tissue derived mesenchymal stem cells - M. Dhanasekaran; S. Indumathi; R. Poojitha; A. Kanmani; J. S. Rajkumar; D. Sudarsanam (Cell and Tissue Banking, 2013)

Evaluating the effectiveness of conservation site networks under climate change: accounting for uncertainty - Robert Bagchi; Mike Crosby; Brian Huntley; David G. Hole; Stuart H. M. Butchart; Yvonne Collingham; Mohit Kalra; Jagadish Rajkumar; Asad Rahmani; Mitra Pandey; Hum Gurung; Le Trong Trai; et al. (Global Change Biology, 2013)
We forecasted potential impacts of climate change on the ability of a network of key sites for bird conservation (Important Bird Areas; IBA s) to provide suitable climate for 370 bird species of current conservation concern in two Asian biodiversity hotspots: the Eastern Himalaya and Lower Mekong. Comparable studies have largely not accounted for uncertainty, which may lead to inappropriate conclusions. We quantified the contribution of four sources of variation (choice of general circulation models, emission scenarios and species distribution modelling methods and variation in species distribution data) to uncertainty in forecasts and tested if our projections were robust to these uncertainties. Declines in the availability of suitable climate within the IBA network by 2100 were forecast as ‘extremely likely’ for 45% of species, whereas increases were projected for only 2%. Thus, we predict almost 24 times as many ‘losers’ as ‘winners’. However, for no species was suitable climate ‘extremely likely’ to be completely lost from the network. Considerable turnover (median = 43%, 95% CI = 35–69%) in species compositions of most IBA s were projected by 2100. Climatic conditions in 47% of IBA s were projected as ‘extremely likely’ to become suitable for fewer priority species. However, no IBA was forecast to become suitable for more species. Variation among General Circulation Models and Species Distribution Models contributed most to uncertainty among forecasts. This uncertainty precluded firm conclusions for 53% of species and IBA s because 95% confidence intervals included projections of no change. Considering this uncertainty, however, allows robust recommendations concerning the remaining species and IBA s. Overall, while the IBA network will continue to sustain bird conservation, climate change will modify which species each site will be suitable for. Thus, adaptive management of the network, including modified site conservation strategies and facilitating species' movement among sites, is critical to ensure effective future conservation.

Repression of oxalic acid-mediated mineral phosphate solubilization in rhizospheric isolates of Klebsiella pneumoniae by succinate - Mahendrapal Singh Rajput; G. Naresh Kumar; Shalini Rajkumar (Archives of Microbiology, 2013)

Outcome definitions and clinical predictors influence pharmacogenetic associations between HTR3A gene polymorphisms and response to clozapine in patients with schizophrenia - A. P. Rajkumar; B. Poonkuzhali; A. Kuruvilla; A. Srivastava; M. Jacob; K. S. Jacob (Psychopharmacology, 2012)

Cx43, ZO-1, alpha-catenin and beta-catenin in cataractous lens epithelial cells - Anshul I Arora; Kaid Johar; Devarshi U Gajjar; Darshini A Ganatra; Forum B Kayastha; Anuradha K Pal; Alpesh R Patel; S Rajkumar; Abhay R Vasavada (Journal of Biosciences, 2012)

Effect of feeding different levels of energy and protein on performance of Aseel breed of chicken during juvenile phase - Santosh Haunshi; Arun Kumar Panda; Ullengala Rajkumar; Mahendra Kumar Padhi; Mattam Niranjan; Rudra Nath Chatterjee (Tropical Animal Health and Production, 2012)

Protective effect of aqueous extract of Spinacia oleracea leaves in experimental paradigms of inflammatory bowel disease - Kishor Vasant Otari; Priyanka Subhash Gaikwad; Rajkumar Virbhadrappa Shete; Chandrashekhar Devidas Upasani (Inflammopharmacology, 2012)

Microrhizome induction in Acorus calamus Linn. — An important medicinal and aromatic plant - Ningthoujam Sandhyarani Devi; Rajkumar Kishor; Gurumayum Jitendra Sharma (Horticulture, Environment, and Biotechnology, 2012)

Ione kipgenii (Orchidaceae), a new species from Manipur, India - Rajkumar Kishor; Krishna Chowlu; S. P. Vij (Kew Bulletin, 2012)

Isolation and Characterization of Heavy Metal Resistant Bacteria from Barak River Contaminated with Pulp Paper Mill Effluent, South Assam - Bibhas Rajkumar; G. D. Sharma; A. K. Paul (Bulletin of Environmental Contamination and Toxicology, 2012)

Evaluation of two Indian native chicken breeds for reproduction traits and heritability of juvenile growth traits - Santosh Haunshi; Murugesan Shanmugam; Mahendra Kumar Padhi; Matam Niranjan; Ullengala Rajkumar; Maddula Ramakoti Reddy; Arun Kumar Panda (Tropical Animal Health and Production, 2012)

A Pilot Program in Collaboration with African American Churches Successfully Increases Awareness of the Importance of Cancer Research and Participation in Cancer Translational Research Studies among African Americans - Gerardo Colon-Otero; Monica Albertie; Mary Lesperance; Jennifer A. Weis; Alton Coles; Nina Smith; Lynette Mills; Timothy Woodward; Alvaro Moreno Aspitia; Prakash Vishnu; Floyd Willis; Amber Isley; et al. (Journal of Cancer Education, 2012)

Cytotoxicity of cyanide in primary culture of rat hepatocytes and its interaction with alpha-ketoglutarate - Rahul Bhattacharya; Janardhanan Hariharakrishnan; Ravindra M. Satpute; Rajkumar Tulsawani (Molecular & Cellular Toxicology, 2012)

Climate change and crop yields in the Indian Cardamom Hills, 1978–2007 CE - Muthusamy Murugan; Paddu Krishnappa Shetty; Raju Ravi; Aavudai Anandhi; Arulappan Joseph Rajkumar (Climatic Change, 2012)

Optimization of electro-oxidation process for the treatment of Reactive Orange 107 using response surface methodology - K. Rajkumar; Muthuchamy Muthukumar (Environmental Science and Pollution Research, 2012)

Protection of Borehole Water Quality in Sub-Saharan Africa using Minimum Safe Distances and Zonal Protection - Yasmin Rajkumar; Yongxin Xu (Water Resources Management, 2011)

Rapid Real-Time PCR Assay for Culture and Tissue Identification of Geomyces destructans: the Etiologic Agent of Bat Geomycosis (White Nose Syndrome) - Sudha Chaturvedi; Robert J. Rudd; April Davis; Tanya R. Victor; Xiaojiang Li; Kim A. Appler; Sunanda S. Rajkumar; Vishnu Chaturvedi (Mycopathologia, 2011)

Genetic Structure of Indian Valerian (Valeriana jatamansi) Populations in Western Himalaya Revealed by AFLP - Subramani Rajkumar; Sunil Kumar Singh; Akshay Nag; Paramvir S. Ahuja (Biochemical Genetics, 2011)

Clonal propagation of triploid Acorus calamus Linn. Using dual-phase culture system - Ningthoujam Sandhyarani; Rajkumar Kishor; Gurumayum Jitendra Sharma (Journal of Crop Science and Biotechnology, 2011)

An examination of male and female odds ratios by BMI, cigarette smoking, and alcohol consumption for cancers of the oral cavity, pharynx, and larynx in pooled data from 15 case–control studies - Jay H. Lubin; Joshua Muscat; Mia M. Gaudet; Andrew F. Olshan; Maria Paula Curado; Luigino Dal Maso; Victor Wünsch-Filho; Erich M. Sturgis; Neonilia Szeszenia-Dabrowska; Xavier Castellsague; Zuo-Feng Zhang; Elaine Smith; et al. (Cancer Causes & Control, 2011)

A new gonad-infecting species of Philometra Costa, 1845 (Nematoda: Philometridae) from the marine fish Terapon jarbua (Forsskål) (Terapontidae) off the eastern coast of India - František Moravec; Ayyaru Gopalakrishnan; Mayalagu Rajkumar; Ayyapan Saravanakumar; Sinduja Kaliyamoorthy (Systematic Parasitology, 2011)

Genetic analysis of juvenile growth and carcass traits in a full diallel mating in selected colored broiler lines - Ullengala Rajkumar; R. P. Sharma; M. K. Padhi; K. S. Rajaravindra; B. L. N. Reddy; M. Niranjan; T. K. Bhattacharya; S. Haunshi; R. N. Chatterjee (Tropical Animal Health and Production, 2011)

Characterization of Solang valley watershed in western Himalaya for bio-resource conservation using remote sensing techniques - Amit Kumar; Amit Chawla; S. Rajkumar (Environmental Monitoring and Assessment, 2011)

RT-PCR and real-time PCR analysis of E2A-PBX1, TEL-AML1, mBCR-ABL and MLL-AF4 fusion gene transcripts in de novo B-lineage acute lymphoblastic leukaemia patients in south India - NATARAJAN SUDHAKAR; KAMALALAYAM RAGHAVAN RAJALEKSHMY; THANGARAJAN RAJKUMAR; KARUNAKARAN NIRMALA NANCY (Journal of Genetics, 2011)

Chromosome identification and karyotype analysis of Podophyllum hexandrum Roxb. ex Kunth using FISH - Akshay Nag; Subramani Rajkumar (Physiology and Molecular Biology of Plants, 2011)

Photoluminescence Electron-Transfer Quenching of Rhenium(I) Complexes with Organic Sulfides - M. Rajkumar; J. Bhuvaneswari; M. Velayudham; E. Rajkumar; S. Rajagopal (Journal of Fluorescence, 2011)

Gingers of Manipur: diversity and potentials as bioresources - Gurumayum Jitendra Sharma; Pukhrambam Chirangini; Rajkumar Kishor (Genetic Resources and Crop Evolution, 2011)

New discovery of coral rubbings in the north-western Gulf of Kachchh, Gujarat, Western India — GIS based evaluation - J. Sesh Serebiah; M. Rajkumar; Jun Sun; B. A. Venmathi Maran; A. Saravanakumar; G. A. Thivakaran (Journal of Ocean University of China, 2011)

Polymorphism in the Prolactin Promoter and Its Association with Growth Traits in Chickens - T. K. Bhattacharya; R. N. Chatterjee; R. P. Sharma; M. Niranjan; U. Rajkumar; B. L. N. Reddy (Biochemical Genetics, 2011)

Genome organization in coffee as revealed by EST PCRRFLP, SNPs and SSR analysis - Manoj Kumar Mishra; Patrizia Tornincasa; Barbara De Nardi; Elisa Asquini; René Dreos; Lorenzo Del Terra; Rajkumar Rathinavelu; Paola Rovelli; Alberto Pallavicini; Giorgio Graziosi (Journal of Crop Science and Biotechnology, 2011)

First record of three giant marine Bathynomids (Crustacea, Isopoda, Cirolanidae) from India - R. Sankar; M. Rajkumar; Jun Sun; A. Gopalakrishnan; T. M. Vasanthan; G. Ananthan; J. P. Trilles (Acta Oceanologica Sinica, 2011)

Biodiversity of brackish water amphipods (crustacean) in two estuaries, southeast coast of India - Nityananda Mondal; Mayalagu Rajkumar; Jun Sun; Sourav Kundu; P. S. Lyla; Seyed Ajmal Khan; Jean Paul Trilles (Environmental Monitoring and Assessment, 2010)

Differential expression of Toll-like receptor mRNA in White Leghorn and indigenous chicken of India - Kannaki T. Ramasamy; Maddula R. Reddy; Dhanutha N. Raveendranathan; Shanmugam Murugesan; Rudra N. Chatterjee; Rajkumar Ullengala; Santosh Haunshi (Veterinary Research Communications, 2010)

Assessment of Genetic Relatedness of Crossbred Chicken Populations Using Microsatellite Markers - Rudra Nath Chatterjee; Tarun K. Bhattacharya; Meenakshi Dange; U. Rajkumar (Biochemical Genetics, 2010)

Bloom forming species of phytoplankton in two coastal waters in the Southeast coast of India - K. Thillai Rajasekar; M. Rajkumar; Jun Sun; V. Ashok Prabu; P. Perumal (Journal of Ocean University of China, 2010)

Seasonal variations of phytoplankton diversity in the Coleroon coastal waters, southeast coast of India - Rajasekar K. Thillai; M. Rajkumar; Jun Sun; Prabu V. Ashok; P. Perumal (Acta Oceanologica Sinica, 2010)

AFLP-Based Genetic Diversity Assessment of Commercially Important Tea Germplasm in India - R. K. Sharma; M. S. Negi; S. Sharma; P. Bhardwaj; R. Kumar; E. Bhattachrya; S. B. Tripathi; D. Vijayan; A. R. Baruah; S. C. Das; B. Bera; R. Rajkumar; et al. (Biochemical Genetics, 2010)

Influence of organic supplements on production of shoot and callus biomass and accumulation of bacoside in Bacopa monniera (L.) Pennell. - Anuradha Parale; Rajkumar Barmukh; Tukaram Nikam (Physiology and Molecular Biology of Plants, 2010)

Influence of Silver Nanoparticles on 2,3-Bis(Chloromethyl)Anthracene-1,4,9,10-Tetraone - Mahalingam Umadevi; N. A. Sridevi; A. S. Sharmila; Beulah J. M. Rajkumar; M. Briget Mary; P. Vanelle; T. Terme; O. Khoumeri (Journal of Fluorescence, 2010)

Forest structure of arid zone mangroves in relation to their physical and chemical environment in the western Gulf of Kachchh, Gujarat, Northwest coast of India - Ayyappan Saravanakumar; Mayalagu Rajkumar; Jun Sun; Jebaraj Sesh Serebiah; Gobi Alagiri Thivakaran (Journal of Coastal Conservation, 2009)

Effects of selected heavy metals (Pb, Cu, Ni, and Cd) in the aquatic medium on the restoration potential and accumulation in the stem cuttings of the terrestrial plant, Talinum triangulare Linn - K. Rajkumar; S. Sivakumar; P. Senthilkumar; D. Prabha; C. V. Subbhuraam; Y. C. Song (Ecotoxicology, 2009)

Fishery resources in arid zone mangroves in gulf of Kachchh, Gujarat, northwest coast of India - A. Saravanakumar; M. Rajkumar; J. Sesh Serebiah; G. A. Thivakaran (Journal of Ocean University of China, 2009)

Isolation and development of a molecular sex marker for Bassiana duperreyi, a lizard with XX/XY sex chromosomes and temperature-induced sex reversal - Alexander E. Quinn; Rajkumar S. Radder; Stephen D. Sarre; Arthur Georges; Tariq Ezaz; Richard Shine (Molecular Genetics and Genomics, 2009)

Induction of multiple shoots in a monopodial orchid hybrid (Aerides vandarum Reichb.f × Vanda stangeana Reichb.f) using thidiazuron and analysis of their genetic stability - Rajkumar Kishor; H. Sunitibala Devi (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Fluorescence Quenching of 1,4-Dihydroxy-2,3-Dimethyl-9,10-Anthraquinone by Silver Nanoparticles: Size Effect - M. Umadevi; P. Vanelle; T. Terme; Beulah J. M. Rajkumar; V. Ramakrishnan (Journal of Fluorescence, 2009)

Intergeneric hybrid of two rare and endangered orchids, Renanthera imschootiana Rolfe and Vanda coerulea Griff. ex L. (Orchidaceae): Synthesis and characterization - Rajkumar Kishor; Gurumayum Jitendra Sharma (Euphytica, 2009)

High Level of Genetic Diversity Among the Selected Accessions of Tea (Camellia sinensis) from Abandoned Tea Gardens in Western Himalaya - S. Karthigeyan; S. Rajkumar; R. K. Sharma; Ashu Gulati; R. K. Sud; P. S. Ahuja (Biochemical Genetics, 2008)

Spectral Investigations of Solvatochromism and Preferential Solvation on 1,4-Dihydroxy-2,3-Dimethyl-9,10-Anthraquinone - M. Umadevi; P. Vanelle; T. Terme; Beulah J.M. Rajkumar; V. Ramakrishnan (Journal of Fluorescence, 2008)

Molecular characterization of reciprocal crosses of Aerides vandarum and Vanda stangeana (Orchidaceae) at the protocorm stage - Rajkumar Kishor; H. S. Devi; K. Jeyaram; M. R. K. Singh (Plant Biotechnology Reports, 2008)

Plant species diversity along an altitudinal gradient of Bhabha Valley in western Himalaya - Amit Chawla; S. Rajkumar; K. N. Singh; Brij Lal; R. D. Singh; A. K. Thukral (Journal of Mountain Science, 2008)

A Common Transport System for Methionine, l-methionine-dl-Sulfoximine (MSX), and Phosphinothricin (PPT) in the Diazotrophic Cyanobacterium Nostoc muscorum - Arvind Kumar Singh; Mayashree B. Syiem; Rajkumar S. Singh; Samrat Adhikari; Amar Nath Rai (Current Microbiology, 2008)

Molecular mapping of genomic regions harboring QTLs for stalk rot resistance in sorghum - P. Srinivasa Reddy; B. Fakrudin; Rajkumar; S. M. Punnuri; S. S. Arun; M. S. Kuruvinashetti; I. K. Das; N. Seetharama (Euphytica, 2008)

Genetics of rate limiting disease reaction to Alternaria solani in Tomato - E. S. Rao; A. D. Munshi; P. Sinha; Rajkumar (Euphytica, 2008)

Maternally derived egg yolk steroid hormones and sex determination: Review of a paradox in reptiles - Rajkumar S. Radder (Journal of Biosciences, 2007)

Benthic macrofaunal assemblage in the arid zone mangroves of gulf of Kachchh-Gujarat - A. Saravanakumar; J. Sesh Serebiah; G. A. Thivakaran; M. Rajkumar (Journal of Ocean University of China, 2007)

A linkage and family-based association analysis of a potential neurocognitive endophenotype of bipolar disorder - Jonathan Savitz; Lize van der Merwe; Mark Solms; Rajkumar Ramesar (NeuroMolecular Medicine, 2007)

A linkage and family-based association analysis of a potential neurocognitive endophenotype of bipolar disorder - Jonathan Savitz; Lize Merwe; Mark Solms; Rajkumar Ramesar (NeuroMolecular Medicine, 2007)

A brain-behaviour initiative for South Africa: the time is right - Dan J. Stein; Willie Daniels; Robin Emsley; Brian Harvey; Jonathan Blackburn; Paul Carey; George Ellis; Nicola Illing; Alan Flisher; Hanlie Moolman-Smook; Kelvin Mwaba; Rajkumar Ramesar; et al. (Metabolic Brain Disease, 2006)

The language of lizards: interpreting the function of visual displays of the Indian rock lizard, Psammophilus dorsalis (Agamidae) - Rajkumar S. Radder; Srinivas K. Saidapur; Richard Shine; Bhagyashri A. Shanbhag (Journal of Ethology, 2006)

Identification of two RAPD markers genetically linked to a recessive allele of a Fusarium wilt resistance gene in pigeonpea (Cajanus cajan L. Millsp.) - H. Kotresh; B. Fakrudin; S. M. Punnuri; B. K. Rajkumar; M. Thudi; H. Paramesh; H. Lohithswa; M. S. Kuruvinashetti (Euphytica, 2006)

Molecular Analysis of Korean Isolate of Barley Yellow Mosaic Virus - Kui Jae Lee; Min Kyung Choi; Wang Hyu Lee; Mani Rajkumar (Virus Genes, 2006)

Type 1 (11; 22)(q24: q12) translocation is common in Ewing’s sarcoma/ peripheral neuroectodermal tumour in south Indian patients - T. Parija; S. Shirley; S. Uma; K. R. Rajalekshmy; S. Ayyappan; T. Rajkumar (Journal of Biosciences, 2005)

Characterization of a Novel Cr6+ Reducing Pseudomonas sp. with Plant Growth–Promoting Potential - M. Rajkumar; R. Nagendran; Kui Jae Lee; Wang Hyu Lee (Current Microbiology, 2005)

Ovicidal activity of Solanum trilobatum L. (Solanaceae) leaf extract against Culex quinquefasciatus Say and Culex tritaeniorhynchus Giles (Diptera: Culicidae) - S. Rajkumar; A. Jebanesan (International Journal of Tropical Insect Science, 2004)

Factors influencing offspring traits in the oviparous multi-clutched lizard,Calotes versicolor (Agamidae) - Rajkumar S. Radder; Bhagyashri A. Shanbhag (Journal of Biosciences, 2004)

Iontophoretic in Vivo Transdermal Delivery of β-Blockers in Hairless Rats and Reduced Skin Irritation by Liposomal Formulation - Rajkumar Conjeevaram; Ayyappa Chaturvedula; Guru V. Betageri; Gangadhar Sunkara; Ajay K. Banga (Pharmaceutical Research, 2003)

The importance of alcohol-induced muscle disease - Victor R. Preedy; Kay Ohlendieck; Junko Adachi; Michael Koll; Alan Sneddon; Ross Hunter; Rajkumar Rajendram; David Mantle; Timothy J. Peters (Journal of Muscle Research and Cell Motility, 2003)

Lowering body temperature induces embryonic diapause during prolonged egg retention in the lizard, Calotes versicolor - Bhagyashri A. Shanbhag; Srinivas K. Saidapur; Rajkumar S. Radder (The Science of Nature, 2003)

Molecular characterization of some Indian Basmati and other elite rice genotypes using fluorescent-AFLP - R. Aggarwal; V. Shenoy; J. Ramadevi; R. Rajkumar; L. Singh (Theoretical and Applied Genetics, 2002)

Electrically Modulated Transdermal Delivery of Fentanyl - Rajkumar Conjeevaram; Ajay K. Banga; Lei Zhang (Pharmaceutical Research, 2002)

Diverse prevalence of large deletions within the OA1 gene in ocular albinism type 1 patients from Europe and North America - M. Bassi; Arthur Bergen; Pierre Bitoun; Stephen Charles; Maurizio Clementi; Richard Gosselin; Jane Hurst; Richard Lewis; Birgit Lorenz; Thomas Meitinger; Ludwine Messiaen; Rajkumar Ramesar; et al. (Human Genetics, 2001)

Studies on the production of extracellular protease by Alcaligenes faecalis - E. Berla Thangam; G. Suseela Rajkumar (World Journal of Microbiology and Biotechnology, 2000)

gβ- and gγ-turns in proteins revisited: A new set of amino acid turn-type dependent positional preferences and potentials - Kunchur Guruprasad; Sasidharan Rajkumar (Journal of Biosciences, 2000)

Leads to cancer control based on cancer patterns in a rural population in South India - R. Rajkumar; R. Sankaranarayanan; A. Esmi; R. Jayaraman; J. Cherian; D.M. Parkin (Cancer Causes & Control, 2000)

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)

Binding of Shigella to rat and human intestinal mucin - Ramachandran Rajkumar; Halagowder Devaraj; Sivasithamparam Niranjali (Molecular and Cellular Biochemistry, 1998)

Retinitis pigmentosa locus on 17q (RP17): fine localization to 17q22 and exclusion of the PDEG and TIMP2 genes - Soraya Bardien; Rajkumar Ramesar; Shomi Bhattacharya; J. Greenberg (Human Genetics, 1997)